Identification of a highly conserved and surface-exposed B-cell epitope in snake venom L-amino acid oxidases - Thamyres Silva de Assis; Tamara Gabriela Fernandes Costa; Letícia Lopes-de-Souza; Fernanda Costal-Oliveira; Carolina R. Rodrigues; Camila Rosa Campos; Clara Guerra-Duarte; Mírian Ívens Fagundes; Ricardo A. Machado-de-Ávila; Vânia M.M. Braga; Carlos Chávez-Olórtegui (Toxicon, 2026)

The facile and environmentally friendly synthesis of metallic nanoparticles-carbon black nanocomposite electrocatalysts for hydrogen evolution reaction - R. Gonçalves; R.C. Oliveira; R.A.C. Amoresi; R.F. Von Stein; L.O. Laier; A.D. Rodrigues; E.C. Pereira; Paulo José Sousa Maia (Journal of Environmental Chemical Engineering, 2026)

A comparative evaluation of new prebiotic candidates. Part 2: In vitro assays using faecal inoculum from IBD patients - Sergio Martínez-Gómez; Joana Sousa; Ana Cordeiro; Sónia G. Barbosa; Ricardo Franco-Duarte; Ana C. Pinheiro; Ligia R. Rodrigues; Sara C. Silvério; Remedios Yáñez; José Luis Alonso (Food Research International, 2026)

Bioinspired pullulan-based adhesive coacervate films for targeted buccal delivery of peptides - Margarida M.A. Sacramento; Nazanin Z. Ezazi; Eleftheria Pantazoglou; Philip Mark Lund; Marco van de Weert; Zhongyang Zhang; Rui Vitorino; Floriane Bahuon; Ragna Berthelsen; Stephen T. Buckley; Gavrielle R. Untracht; Peter Eskil Andersen; et al. (Carbohydrate Polymers, 2026)

Kogia Records in Brazilian Equatorial and Southwestern Atlantic Oceans - Joao Pedro M. Mura; Raphael B. Machado; Yasmin P. Viana; Natalia Rodrigues‐Soares; Giovanne A. Ferreira; Larissa Kelmer L. Kascher; Barbara S. Silva; Lucia O. Alencar; Gabrieli M. Rodrigues; Franciele R. de Castro; Daniela F. Godoy; Jose L. Pizzorno; et al. (Marine Mammal Science, 2026)
The pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales are cryptic cetaceans characterized by inconspicuous surfacing behavior, small group sizes, and deep‐diving habits, making visual detection particularly challenging. Here, we present the first broad‐scale passive acoustic monitoring (PAM) assessment of Kogia spp. occurrence along the Brazilian coast, spanning both the Equatorial Atlantic Ocean (EAO) and Southwestern Atlantic Ocean (SWAO). Across 25 survey campaigns, 504 survey days, and more than 6441 h of acoustic recordings, 94 acoustic detections were identified, predominantly within the Brazilian Equatorial Margin (BEM), resulting in substantially higher detection‐per‐unit‐effort values in the EAO than in the SWAO. Two rare visual‐acoustic encounters of Kogia sima were also documented, including one detection incorporated into the dataset. A total of 2796 echolocation clicks were analyzed, exhibiting the characteristic narrow‐band high‐frequency acoustic profile of Kogia spp. (mean peak frequency = 126.2 ± 3.8 kHz; mean −3 dB bandwidth = 4.7 ± 2.56 kHz; mean inter‐click interval = 141 ± 97 ms). Detections occurred across a broad bathymetric range (9–4411 m), and kernel density analyses revealed spatial heterogeneity in occurrence patterns, with recurrent detection areas concentrated within the BEM. Collectively, these findings demonstrate the effectiveness of PAM for studying elusive deep‐diving cetaceans and provide an important baseline for future ecological monitoring, impact assessment, and conservation efforts targeting Kogia spp. in the western Atlantic.

Intestinal Histomorphometric Alterations During Experimental Strongyloidiasis in Mice Treated with Rosmarinus officinalis Essential Oil - Lorena Q. A. Tanaka; Kamilla A. M. Dutra; Nicolas M. H. da Silva; Izadora M. Assis; Gabriela A. C. Duarte; João B. A. Souza; Eleuza R. Machado; Ana Paula S. Perez; Rosângela M. Rodrigues (Acta Parasitologica, 2026)
Purpose Strongyloidiasis is an intestinal helminthiasis that can induce structural alterations in the intestinal mucosa during infection. The present study evaluated histomorphometric alterations of the small intestine in mice experimentally infected with Strongyloides venezuelensis and treated with Rosmarinus officinalis essential oil. Methods Infected animals were treated orally with R. officinalis essential oil (200 or 400 mg/kg), ivermectin or control treatments. Histomorphometric parameters of the small intestine were evaluated, including villus height, epithelial height, crypt depth, muscular layer thickness, brush border height and goblet cell counts. Parasitological parameters were also assessed to characterize the infection model. Results Histomorphometric analysis demonstrated that treatment with essential oil at 200 mg/kg was associated with recovery of villus and epithelial height, increased brush border and goblet cell numbers, as well as attenuation of muscular layer hypertrophy, suggesting preservation of mucosal structure during infection. The 400 mg/kg dose, although associated with greater reduction in parasite burden, was accompanied by increased crypt depth, indicating more intense proliferative remodeling of the intestinal mucosa. Ivermectin promoted the greatest reduction in parasite burden with marked elimination of eggs and females. Conclusion These findings indicate that R. officinalis essential oil modulates intestinal mucosal architecture during experimental strongyloidiasis and highlight its potential influence on host intestinal responses during infection.

Multi-scale characterization of fault zones in the Groningen gas field: Implications for fault reactivation - Job P.B. Arts; Liviu Matenco; André R. Niemeijer; Martyn R. Drury; Ernst Willingshofer; Fadi H. Nader; Dallyn Rodrigues (Journal of Structural Geology, 2026)

First report of Blastanosphaira kokkoda Javaux and Knoll 2017 from the Ediacaran of the Araras Group, Brazil (Western Gondwana): biostratigraphic and paleoenvironmental implications - Diego R. Rodrigues Cruz; Silane A. Ferreira da Silva-Caminha; Evelyn Aparecida Mecenero Sanchez; Rogério Roque Rubert; Gabriel Fernandes Coelho; Tainah Alves de Matos; Andressa Luiza Pereira de Camargo; Vinicius Santos do Valle; Juliana Okubo (Journal of South American Earth Sciences, 2026)

A comparative evaluation of new prebiotic candidates. Part 1: Chemical and structural characterization, digestibility, and in vitro fermentation using faecal inoculum from healthy donors - Sergio Martínez-Gómez; Joana Sousa; Ana Cordeiro; Sónia G. Barbosa; Ricardo Franco-Duarte; Ana C. Pinheiro; Ligia R. Rodrigues; Sara C. Silvério; Remedios Yáñez; José Luis Alonso (Food Research International, 2026)

Urban aerosols and the intensification of maximum air temperature in a tropical Amazonian city - Rafael Palácios; Marco A. Franco; Fernando G. Morais; Maurício Moura; Francisco de Souza Oliveira; Glauber Cirino; Breno Imbiriba; Leone F.A. Curado; João Basso; Thiago R. Rodrigues; Amaury de Souza; Julia Cohen; et al. (Urban Climate, 2026)

Spatial Scale Modulates the Effect of Habitat Amount on Diversity Patterns of Arachnid Assemblages Across Different Brazilian Ecosystems - André F. A. Lira; Adriano M. DeSouza; Thayna R. Brito‐Almeida; Hugo L. L. Neves; Gilberto G. Rodrigues; Carlos Henrique De‐Oliveira‐Nogueira; Ubiratã F. Souza; Alessandra R. S. Andrade; Rafael G. Jansen; Ana Lúcia Tourinho; Leonardo S. Carvalho; Laís M. Pordeus; et al. (Journal of Biogeography, 2026)
Aim We evaluated how native vegetation cover influences the diversity of arachnid assemblages across multiple spatial scales in major Brazilian ecosystems. Location Brazil (Amazon and Atlantic rainforests, Cerrado savanna and Caatinga dry forest). Taxon Arachnida (Opiliones, Pseudoscorpiones and Scorpiones). Methods We sampled arachnids at 120 sites using active search and litter sifting. Native vegetation cover was quantified at three spatial scales (100, 200 and 300 m buffers) using GIS data. Assemblage structure was assessed using abundance, species richness, and Hill numbers ( q = 0, 1 and 2). Generalized linear mixed models were used to evaluate responses across taxonomic groups and ecosystems. Results We recorded 3986 individuals from 179 species. Diversity responses to native vegetation cover were taxon‐, ecosystem‐ and scale‐dependent. Positive effects of vegetation cover were stronger and more consistent in rainforest than in savanna and dry forest ecosystems. In rainforests, most responses occurred at smaller spatial scales (100–200 m), whereas no significant effects were detected in the savanna. Opiliones richness showed limited variation with vegetation cover but differed in dominance structure among ecosystems. Scorpion assemblages were characterized by low richness and high dominance, while pseudoscorpions exhibited low evenness in more species‐rich sites, particularly in the Amazon. Main Conclusions Native vegetation cover plays an important role in structuring arachnid diversity in Brazil, but its effects vary across taxa, ecosystems and spatial scales. These findings highlight the need for taxon‐ and scale‐specific conservation strategies and reinforce the importance of multi‐scale approaches to biodiversity conservation in Neotropical landscapes under increasing anthropogenic pressure.

First drone‐based in situ observation of mating behaviour in the Groovebelly Stingray ( D. hypostigma ) in the Southwestern Atlantic - R. M. Ferreira; N. L. F. Araujo; L. N. dos Santos; A. F. S. Rodrigues (Journal of Fish Biology, 2026)
We report the first in situ observation of mating behaviour in the endangered Groovebelly Stingray ( Dasyatis hypostigma ), endemic to the Southwestern Atlantic. Recorded by drone in May 2025 off Ilhabela, Brazil, the event involved one female and four males, lasting ~3 min and comprising close following and pre‐copulatory biting, without agonistic interactions. The interaction comprised a partial behavioural sequence of close following and pre‐copulatory biting, without agonistic interactions between males. This record provides novel insights into the species' reproductive strategy and highlights the value of non‐invasive drone surveys for elasmobranch research.

Reproductive toxicity induced by a repeated 28-day oral exposure to a commercial mixture of the herbicides S-metolachlor and flumioxazin in male rats - Renata K. Carvalho; Diego S. Reis; Ana Luísa G. Santiago; Bruna M. Rodrigues; Jacqueline A. Leite; Walter D. Júnior; Virgínia Damin; Monica L. Andersen; Maingredy R. Souza; Paulo C. Ghedini; Hericles M. Campos; Daniela M. Silva; et al. (Chemico-Biological Interactions, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Anti-inflammatory potential of the CISACN adduct in LPS-induced murine models - Louise M. de Lima; Francisco A. A. F. Gadelha; Laércia K. D. Paiva Ferreira; Cosmo I. D. Vieira; João B. de Oliveira; Larissa A. M. Paiva Ferreira; Matheus Victor de Souza Laurentino; Bruno Vinícius da Silva Moura; Teresa Carolliny M. L. Rodrigues; Tayná R. Olegário; Luciana Scotti; Marcus T. Scotti; et al. (Inflammopharmacology, 2026)

Brazil’s science–policy effort to monitor native vegetation restoration - André L. Giles; Marina G. Freitas; Ana L. V. Espada; Pedro Constantino; Bruno S. Francisco; Silvia B. Rodrigues; Alexandre B. Sampaio; Isis F. de Freitas; Gabriela C. S. Bueno; Raquel C. A. Lacerda; R. Edson; Kirsten Silvius; et al. (Ambio, 2026)
In its early years, the UN Decade on Ecosystem Restoration has mobilized unprecedented global commitments. Yet, measuring restoration success remains contested, particularly in megadiverse countries where the absence of standardized indicators and assessment protocols often leads to subjective decisions by environmental agencies. Here, we present a core set of leading indicators developed through a pioneering Brazil-led science–policy collaboration between environmental agencies and research institutions. The indicators capture early vegetation recovery within four years and whether restoration trajectories are sustained or at risk of reversal. The initiative also establishes a framework that bridges science and policy to deliver practical monitoring tools. It offers a model for other megadiverse countries with complex governance, showing how simple, standardized indicators can translate restoration pledges into measurable results for the UN Decade.

The Role of Gene Flow in the Diversification of the Monkey Treefrog Complex Across the South American Dry Diagonal - Felipe Camurugi; Vinícius A. São Pedro; Felipe Magalhães; Marcelo Gehara; Eliana F. Oliveira; Gabriel C. Costa; Frank T. Burbrink; Edward A. Myers; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Zoologica Scripta, 2026)
Understanding Neotropical megadiversity remains challenging due to fundamental taxonomic issues, including identifying and describing cryptic species and their distribution, and the limited knowledge of key factors driving biological diversification. Such challenges are especially prominent in diverse clades with high levels of cryptic species, such as many Neotropical frogs. Herein, we conduct a mitochondrial phylogenetic study on monkey treefrogs in the genus Pithecopus and a multilocus analysis of the P. hypochondrialis species group throughout its distribution in the South American dry diagonal (DD). Our goals were to infer the main lineages and identify historical factors that led to their divergence. Among nine currently recognised species, we found 14 well‐structured mitochondrial lineages in two main clades, which diversified during the Paleogene/Neogene transition. The lowland clade is widely distributed in the DD, and our multilocus analysis suggests it comprises seven geographically structured lineages: P. azureus , two lineages of P. hypochondrialis , two species and one lineage for the P. nordestinus complex, and Pithecopus sp. Considering the geomorphological history of the region, diversification may have been promoted by allopatric speciation during Miocene paleogeographic events, especially the Brazilian Plateau compartmentalization and fluctuations in the São Francisco River water volume. Furthermore, gene flow between some lineages may be explained by niche conservatism and demographic expansions during the late Pleistocene, a period marked by climatic fluctuations and biome shifts. Our results reinforce the importance of both Neogene tectonic activity and Quaternary climatic fluctuations in shaping the Neotropical biota.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

Chemical pretreatment enhances vacuum filtration of slime-rich iron ore tailings - P. Muñoz; A. Azevedo; R. Rodrigues; J. Rubio (Minerals Engineering, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Dietary replacement of whole soybean grain with micronized defatted soybean meal in dairy cow diets: effects on intake, digestibility, ruminal parameters, and milk yield and composition - Thiago Thiarles Braw André Furlan R Maciel; Eliane Sayuri Miyagi Okada; Euclides Reuter De Oliveira; Jefferson Rodrigues Gandra; Vera Lúcia Banys; Thaís Da Silva Fernandes; Andréa Maria de Araújo Gabriel; Claudia Andrea Lima Cardoso; Vicente Ribeiro Rocha Júnior; Ranney Késia Oliveira de Jesus Silva; Flávio Pinto Monção (Tropical Animal Health and Production, 2026)
This study aimed to evaluate effects of replacing whole soybean grain with micronized defatted soybean meal (MDSM) in diets of lactating dairy cows on performance, digestion, metabolism, and milk yield and composition. Ten primiparous Jersey cows with an initial body weight (BW) of 410 ± 9 kg and 105 ± 5 days in milk were used. Five replacement levels (0, 25, 50, 75, and 100% of dietary DM) of whole soybean grain with MDSM were evaluated. The experiment was conducted as two simultaneous 5×5 Latin squares, each composed of five animals, five treatments, and five experimental periods, totaling 80 days. Each period lasted 16 days, including 12 days for adaptation and 4 days for data collection. No differences were observed among experimental diets for dry matter intake (mean = 14.58 kg day -1 ; p = 0.08) or organic matter intake (mean = 13.60 kg day -1 ; p = 0.08). Increasing dietary inclusion of MDSM resulted in greater crude protein intake, with the highest intake observed at 14% MDSM inclusion. A linear increase (P < 0.05) was observed in digestibility of dry matter, organic matter, crude protein, ether extract, and starch as MDSM inclusion increased. The inclusion level that maximized short-chain fatty acid production was 9.22%. Milk yield corrected to 3.5% fat increased linearly with increasing MDSM inclusion. Inclusion of MDSM did not affect milk fat (p = 0.41), protein (p = 0.86), or lactose (p = 0.88) concentrations. Complete replacement of whole soybean grain with MDSM in diets of Jersey cows increased milk yield, improved feed efficiency, and did not alter milk composition. Additionally, it enhanced digestibility of dry matter, organic matter, crude protein, and starch.

Molecular surveillance and genomic characterization of enterovirus D68 in southern Portugal, 2024–2025 - Sérgio Santos-Silva; Guilherme Moreira; André Palma; Soraia Rodrigues; Margarida Simões; Raquel Guerreiro; Maria S.J. Nascimento; João R. Mesquita (Archives of Virology, 2026)
Enterovirus D68 (EV-D68) is a re-emerging respiratory pathogen that is increasingly associated with severe respiratory disease and occasional neurological complications, yet its circulation in Portugal remains poorly documented. In the present study, we investigated the presence of EV-D68 in respiratory samples collected in southern Portugal (Algarve region) from October 2024 to February 2025. Screening of 150 respiratory samples from patients (115 from children and 35 from adults), all previously positive for rhinovirus/enterovirus, revealed eight EV-D68–positive cases, corresponding to a detection rate of 5.44%, spanning a broad age range from infancy to the elderly. Clinical manifestations ranged from mild respiratory illness to severe conditions, including pneumonia and acute respiratory distress syndrome. Neurological manifestations, including complex febrile seizures and encephalomyelitis, were also observed in EV-D68–positive patients. Some cases involved coinfections, while others presented with EV-D68 as the sole detected respiratory pathogen. Genomic characterization from one isolate revealed a VP1 fragment belonging to clade B3, and a complete genome from another isolate clustered within clade A2. Phylogenetic analysis confirmed clustering with contemporary European isolates. These findings provide preliminary evidence of EV-D68 detection in southern Portugal and document the presence of clades A2 and B3 among the characterized samples. The results illustrate the heterogeneous clinical presentations observed in affected patients and highlight the value of continued molecular monitoring and genomic characterization of EV-D68.

Traditional Chinese medicine techniques for the management of fibromyalgia: a systematic review of randomized controlled trials - Helena L. Silva; Andreia V. Santos; Alexandra B. Monteiro; Maria R. Sousa; Jorge Magalhães Rodrigues (Advances in Traditional Medicine, 2026)

Supervised Learning for Collagen Segmentation in Bright-Field Histology: A Comparative Evaluation of U-Net and MLP - Evelyn R. Silva; Lívia B. Souza; Fernanda S. Tenorio; Nilsa R. Damaceno-Rodrigues; Rita C. Marqueti; Karina R. Casali; Tatiana S. Cunha; Matheus C. Moraes (Annals of Biomedical Engineering, 2026)
Purpose Quantifying collagen in histological slides is essential for diagnosing and monitoring fibrosis. However, the combination of PicroSirius Red staining with polarized light microscopy, one of the standard techniques, requires expensive equipment and time-consuming procedures. This study investigated whether supervised machine learning algorithms applied to bright-field images could provide an automated and accurate method for collagen segmentation, reducing the dependence on polarized imaging. Methods A total of 140 histological images of renal, cardiac, and tendinous tissues from mice and rats stained with PicroSirius Red were analyzed. The images were fragmented into smaller patches, and the green channel was selected for non-polarized analysis. The reference standard was generated from polarized images binarized using ImageJ. Two supervised models were evaluated: (1) a Multilayer Perceptron (MLP) trained using five features (RGB intensities, median filter, and Wavelet), and (2) a U-Net architecture adapted to the image dimensions. Results Both models performed well, with the best results observed in rat tendon samples (Dice and precision > 80%). Performance was lower in mouse kidney images, possibly due to weaker staining and thinner collagen fibers. Overall, the MLP slightly outperformed the U-Net, which still showed comparable results. Conclusion The proposed methodology proved effective for collagen segmentation highlighting the potential of supervised learning to reduce costs and processing time in histological analysis. Future improvements include expanding the dataset and refining the reference standard to enhance robustness in biological tissue evaluation.

Hybrid evolutionary meta-optimization assisted by recurrent neural networks for interpretable parametric symbolic models - Flavio Adalberto Gomes; Wanderson Rainer H. Araujo; Marcio R. Cunha Reis; Geovanne Pereira Furriel; Guilherme Alberto S. Ribeiro; Viviane M. Gomes Pacheco; Marcella Scoczynski R. Martins; Clóves Gonçalves Rodrigues; Antonio Paulo Coimbra; Wesley Pacheco Calixto (Swarm and Evolutionary Computation, 2026)

Coffee silverskin fermentation in a single step for sustainable production of carbohydrate-based mixture rich in pectic oligosaccharides - Ana Cordeiro; Andreia Fernandes; Andreia S. Ferreira; Elisabete Coelho; Manuel A. Coimbra; António M. Peres; Lígia R. Rodrigues; Cláudia Amorim (Food and Bioproducts Processing, 2026)

Synthesis and application of silver-doped glass waste pellets for drinking water treatment - J. S. C. Vieira; J. D. A. do Ano; A. R. Pereira; A. da Costa Reis; F. W. Carvalho; I. A. da Silva; M. R. de Melo Rodrigues; E. M. V. de Carvalho; D. L. P. Macuvele; G. J. Muchave (International Journal of Environmental Science and Technology, 2026)

Ischemic preconditioning with active reperfusion does not improve high-intensity intermittent exercise in youth team sport players - Gustavo R. Mota; Izabela A. Santos; Anderson Luiz Rodrigues; Bernardo N. Ide; Tom Citherlet; Jeffer E. Sasaki; Moacir Marocolo (European Journal of Applied Physiology, 2026)
Purpose We investigated whether an active protocol of ischemic preconditioning (IPC-A) would improve high-intensity intermittent exercise performance in youth team sport players. Methods Fifteen male amateur team sport players (15.5 ± 0.5 yrs) attended four different preconditioning sessions before the YoYo Intermittent Recovery Test level 1 (YYIR1) interspersed by seven days in a counterbalanced randomized cross-over design. IPC protocol consisted of three cycles of 5 min occlusion (220 mmHg) and 5 min reperfusion (0 mmHg) in both thighs. SHAM was similar to the IPC protocol, but ‘occlusion’ pressure was set up at 20 mmHg. Active protocols (IPC-A/ SHAM-A) were similar to the IPC/SHAM, but participants exercised (intermittent run) during the ‘reperfusion’ phases instead of resting. Six minutes after the protocol, the participants performed the YYIR1. Results The distance covered in the YYIR1 did not differ ( p = 0.46) among the protocols: IPC (917 ± 204 m) vs. IPC-A (931 ± 211 m) vs. SHAM (968 ± 201 m) vs. SHAM-A (933 ± 204 m). Blood lactate concentration, and mean heart rate did not differ either ( p > 0.05) among the protocols. Conclusions Active ischemic preconditioning involving exercise during reperfusion phase does not improve high-intensity intermittent exercise performance nor alter physiological or perceptual responses in youth team sport players.

The emergence of pathogens on fish in an impacted estuary and the role of non‐native piranhas in a potential bacterial infectious outbreak - Ryan Andrades; Helder C. Guabiroba; Kathiani V. Bastos; Vítor L. A. Rodrigues; Marcelo R. D. Santos; Clarisse M. Arpini; Mayra Cunha Flecher; Helen A. Pichler; Ciro C. Vilar; Maurício Hostim‐Silva; Jean‐Christophe Joyeux (Journal of Fish Biology, 2026)
As many tropical aquatic ecosystems worldwide, the Doce River estuary (DRE, southeastern Brazil) has increasingly faced multiple anthropogenic threats, including deforestation, mining, species introduction and water management. The 2015 collapse of the Fundão iron ore tailings dam severely changed water properties and increased heavy metal concentration in sediment. However, the potential synergistic effects of the observed threats on fish populations remain largely unknown. After detecting an elevated number of fin lesions in DRE fishes, we used the catfish Genidens genidens (Cuvier, 1829) to investigate whether such mutilations originated from fin‐nipping by non‐native piranha or emerged as a result of fin rot disease through bacterial infection. One third of the examined individuals had fin lesions in the DRE, whereas no conspecific exhibited such lesions in two control estuaries where piranhas are absent; lesions were restricted to the caudal fin, a region known to be targeted by fin‐nipping piranhas. Independently of the presence of fin lesion, culture of fins and livers indicated higher prevalence and variety of bacterial strains in DRE individuals than in a control area. Piranhas likely contribute to the fin lesions in DRE fishes. However, the higher prevalence and variety of bacterial pathogens as well as of liver and kidney disorders identified in fin‐healthy and mutilated fishes of the DRE suggest that the heavily metal‐polluted conditions in the DRE may be associated with the emergence of bacterial infections in fish.

Modeling Future Climate Impacts on Brazil’s Operational Wind and Solar Energy Capacity - Felipe Husadel Poyer; Francisco Lopes Lima; Rodrigo Santos Costa; André Rodrigues Gonçalves; Fernando R. Martins; André F. P. Lucena; Enio Bueno Pereira (Environmental Modeling & Assessment, 2026)
Over the past decade, the Brazilian electricity sector has undergone a profound transformation, driven by the large-scale deployment of wind and solar photovoltaic power plants, a trend that is expected to continue in the years ahead. Although the transition to these variable renewable energy resources helps to reduce greenhouse gas emissions and mitigate the climate crisis, they are vulnerable to the very climate changes they help to avert. This study uses projections from CMIP6 global climate models under two future scenarios (SSP2-4.5 and SSP5-8.5) to assess potential impacts on power generation in the existing centralized wind and solar power facilities in Brazil. The study innovates by assessing the effects of climate change on the future performance of the power plants using measured historical capacity factors as a proxy, thereby eliminating the need for climate bias correction and standardized manufacturer power curves. Projections indicate a nationwide increase in wind potential between 6% and 15% by the end of the century, contributing to an extended wind season in the northeastern region and a stronger seasonality in the southern region. In contrast, the photovoltaic potential reveals modest change; the positive effects of increasing surface radiation are counterbalanced by the negative effects of warmer air temperatures across the assessed scenarios. These findings offer valuable insights for strengthening Brazil’s energy security under future climate conditions.

Exploring EnMAP hyperspectral images and ensemble deep learning for classifying forest land-cover types in Brazil - Matheus Pinheiro Ferreira; Matheus Santos Fuza; José M. S. M Viveiros; Tomás Ferranti; Dário Oliveira; Giulio Brossi Santoro; Paulo Guilherme Molin; Catherine Torres de Almeida; Angélica F. Resende; Danilo R. A. de Almeida; Yelu Zeng; Ricardo Ribeiro Rodrigues; et al. (International Journal of Remote Sensing, 2026)

Stratigraphic review of the Permian Santa Brígida formation, in the Recôncavo-Tucano-Jatobá Rift - U.C.F.F. Brito Conceição; C.F.A. Rodrigues; R. Dino; L.S.G. Teixeira; O.M.C. Oliveira; M.J. Lemos de Sousa; A.F. Brito (Journal of South American Earth Sciences, 2026)

Assessment of soil loss and amount of sediment exported and deposited in Upper Grande River Basin (Brazil) considering different scenarios - R. Cassaro; J.Z. Lima; R.R.M. Ferreira; V.G.S. Rodrigues (Journal of South American Earth Sciences, 2026)

Absence of anti-HEV antibodies in donkeys in Algeria: a first serological survey - Soraia Rodrigues; Abdeldjalil Dahmane; Mouad Debbous; Ricardo Figueiredo; Samari Houssem; Nassiba Reghaissia; Guilherme Moreira; João R. Mesquita (Veterinary Research Communications, 2026)
Paslahepevirus balayani (Hepatitis E virus, HEV) is an emerging zoonotic pathogen with a wide host range, yet its circulation in African equids remains poorly understood. This study provides the first serological investigation of HEV in donkeys in Algeria, aiming to assess exposure levels and identify potential infection-related risk factors. Between 2019 and 2024, 183 donkeys were sampled across three northeastern provinces (Mila, Souk-Ahras, and Tébessa), representing diverse agroecological conditions and including both working donkeys and animals used in cross-border smuggling. Individual data on age, sex, health status, body condition, movement history, and season were recorded. Sera were screened using a proprietary recombinant antigen, which is highly conserved across different HEV strains. All samples tested negative for anti-HEV antibodies. The sample size exceeded the minimum required to detect the highest seroprevalence previously reported in donkeys (12.22%), supporting the epidemiological significance of the negative findings. The absence of seropositivity may reflect limited regional exposure to known HEV reservoirs, local husbandry practices, and environmental conditions that reduce infection risk. These results suggest that HEV is currently not circulating at detectable levels in donkeys from northeastern Algeria. Broader studies, including molecular approaches and additional species, are recommended to clarify HEV ecology in the region.

Design and Evaluation of the Antibacterial Peptide FK18: a Therapeutic Approach for Mastitis in Dairy Animals - Tamaeh Monteiro-Alfredo; Camila de O. Gutierrez; Claudiane V. Almeida; Vinicius C. da Silva; Patrícia Gomes; Caio F. R. de Oliveira; Elisângela S. Madalozzo; Edson Crusca; Raquel M. Q. Orozco; Lucas Lima; Marlon H. Cardoso; Octávio L. Franco; et al. (Probiotics and Antimicrobial Proteins, 2026)

Targeting hypertension through natural phenolics: The multifaceted role of cinnamic acid and its derivatives - Samuel S. P. de Araujo; Brenda L. B. dos Santos; Waldilleny R. A. de Moura; Leonardo G. Rodrigues; Luiz G. S. Branco; Helio C. Salgado; Renato N. Soriano; Marina de T. Durand; João Paulo J. Sabino (Pflügers Archiv - European Journal of Physiology, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Hyperdominant Trees Reveal Savanna Vulnerability Under Climate Change - Facundo Alvarez; Ben Hur Marimon‐Junior; Beatriz Schwantes Marimon; Wesley Jonatar Alves da Cruz; Norberto Gomes Ribeiro Júnior; Raiane Gonçalves Béu; Polyanna da Conceição Bispo; Aldair de Souza Medeiros; Glécio Machado Siqueira; Marcelo Leandro Bueno; Fabiana de Gois Aquino; Frederico Augusto Guimarães Guilherme; et al. (Global Change Biology, 2026)
The Cerrado biome, spanning ~2 million km 2 , is one of the most extensive and biodiverse tropical savannas, yet it is paradoxically dominated by only 30 hyperdominant tree species (~2% of all species, > 50% of all stems). However, their vulnerability to climate change and the effectiveness of current conservation efforts remain uncertain. By combining (i) species distribution models calibrated with edaphic‐climatic predictors and occurrence data for hyperdominant Cerrado trees with (ii) functional‐trait analyses related to ecological strategies (leaf economics, bark investment, ecophysiology, drought tolerance, regeneration, and dispersal), we identified the biomass production and reproductive traits that best predict species persistence under high‐emission scenarios (RCP8.5). Currently, only 427,980 km 2 (~17.4%) of the modeled potential environmental suitability falls within protected areas; under future climate scenarios, this protected suitable area is projected to decline by ~45.9% to 231,377 km 2 (~18.1%). This loss, resulting from land conversion with the expansion of agricultural frontiers and fire events, highlights a mismatch in current regional conservation priorities, overlooking the needs of the Cerrado and its associated biodiversity. Given ongoing land‐use change and that 58% of remaining native vegetation occurs on private lands, this mismatch highlights the urgent need to align conservation and agricultural policy. Functional trait analyses revealed a clear gradient from acquisitive “fast” to conservative “slow” strategies, reflecting trade‐offs in water‐use efficiency and biomass allocation, with leaf structural and reproductive traits best predicting species resilience to climate change. Our results indicate that a small subset of hyperdominant species not only forms current community structure but also signals the biome's resilience/vulnerability to climate change. Conservation planning should prioritize identified climate refuges and be based on functional traits to buffer the loss of functional and structural integrity in one of the world's richest and most threatened savanna ecosystems.

Hypothalamic Atrophy and Textural Changes in Polyglutamine Ataxias - Livia Rodrigues; Thiago J. R. Rezende; Alberto R. M. Martinez; Breno Massuyama; Jose Luiz Pedroso; Orlando G. P. Barsottini; Juan Eugenio Iglesias; Simone Appenzeller; Letícia Rittner; Marcondes C. França (The Cerebellum, 2026)
Background. Spinocerebellar ataxia (SCA) presents a complex genetic landscape, with over 40 subtypes. These autosomal dominant disorders manifest late onset and severe disability, primarily impacting the cerebellum but also involving other nervous system structures. While a single study has linked hypothalamic atrophy to SCA3, further research is needed to confirm and/or expand this association. This study aimed to investigate hypothalamic involvement in PolyQ SCAs, focusing on SCA 1, 2, 3, and 6. Methods. We studied 135 adult patients with genetically confirmed SCA (SCA1, SCA2, SCA3, and SCA6) and 117 healthy controls. Hypothalamic subregions were segmented using H-SynEx, and both volumetric and texture features were extracted from MR images. Group differences were assessed with the Mann–Whitney U test, and associations with disease duration and severity (measured by SARA) were examined using Spearman’s rank correlation. Results. Significant atrophy of hypothalamic subregions was observed in SCA1, SCA3, and SCA6 when compared with controls, with the anterior subregion being affected in all cases. Texture analysis revealed widespread alterations in SCA1, SCA3, and SCA6 across all subregions. In SCA1 and SCA3, both volumetric and texture measures correlated with disease duration and SARA scores. These findings suggest that hypothalamic involvement in SCAs is complex and may occur before overt clinical manifestations. Key words: Ataxia, Polyglutamine disease, Hypothalamus, MRI, Volumetry

Circulation-driven dispersal and retention affect blue whiting recruitment dynamics in the Northeast Atlantic Ocean - Costanza Cappelli; Hjálmar Hátún; Jan Arge Jacobsen; André W. Visser; Flemming Thorbjørn Hansen; Jonas B. Mortensen; Sara Accornero; Francisca Rodrigues; Brian R. MacKenzie (Frontiers in Marine Science, 2026)
Environmental drivers of early life-stage survival are critical to understanding recruitment variability and improving ecosystem-based fisheries management. We investigate how regional ocean circulation influences blue whiting ( Micromesistius poutassou ) recruitment in the Northeast Atlantic by combining multi-decadal transport analyses with Lagrangian particle simulations. Using ocean reanalysis, we compute 28-year (1993-2020) volume transport indices across the Ellett Line, a hydrographic section through the main spawning grounds, and we relate them to interannual variation in recruit per spawner. We also simulate larval dispersal from main spawning areas (Porcupine Bank, Rockall Trough, Rockall Plateau, Hebrides) during the six highest and lowest recruit-per-spawner years using an agent-based particle-tracking model. Statistical models show that higher recruit per spawners are produced in years with stronger northward flow along the Hebrides-Rockall Trough (upper 0–100 m), whereas transport over Rockall Plateau is weaker and exhibits no consistent relationship with recruit per spawner. Complementary particle-tracking simulations reveal that high-recruit-per-spawner years are characterized by larger northward advection of eggs and larvae from the Hebrides, as well as increased local retention over Porcupine Bank. In contrast, low-recruit-per-spawner years exhibit more meandering drift in the Rockall region and a modest southward dispersal from Porcupine Bank. These results suggest that both effective transport to known northern nursery areas and retention in productive spawning regions can enhance early survival, depending on spawning location. We propose that large-scale ocean-climate variability (e.g., changes in subpolar gyre circulation driven by wind stress curl) modulates these transport mechanisms, thereby influencing whether early life stages are delivered to favorable habitats or lost to suboptimal areas. Our findings provide a mechanistic link between climate-driven circulation changes and fish recruitment variability, underscoring a potential benefit of incorporating oceanographic processes into ecosystem-based fisheries management strategies.

Quantification and characterization of collagen in experimentally induced wounds treated with different types of platelet-rich plasma gel - G. Haro de Melo; F. M. Moreira; G. G. Mori; L. F. Bento; D. V. Barrionuevo; C. B. Laposy; R. Giuffrida; A. F. F. Rodrigues; G. A. T. Ozaki; D. A. F. da Silva; F. L. Pacagnelli; R. M. B. Nogueira (Cell and Tissue Banking, 2026)
Due to its high concentration of growth factors, platelet-rich plasma (PRP) has become the subject of much research, either as an isolated or adjuvant treatment for wound repair. The fractal dimension has been used as an innovative method for the characterization and quantification of tissue structural alterations without any interference from the evaluator. The objective of this study was characterizing collagen types I and III in experimentally induced wounds and treated with different PRP sources by means of fractal dimension and other histological analyzes using blades stained with picrocirius-red and hematoxylin-eosin (HE). In statistical analysis, the variables presented a non-parametric distribution; thus, Mann-Whitney and Kruskall-Wallis tests ( p < 0,05) were performed using the Student-Newman-Keuls method. It was observed an increase of the collagen fibers by measuring the area with Threshold Color in the different treatments, especially with autologous PRP ( p = 0.009) and heterologous PRP ( p = 0.016). The fractal dimension of type I collagen had a significant increase for the autologous group ( p = 0.028) in relation to the control, but, on average ( p < 0.05), type III collagen was higher than type I. Fractal dimension was efficient to separately characterize type I and type III collagen fibers. In this study, collagenization was higher in autologous when compared to heterologous and homologous PRP treatments.

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Rethinking the ageing process of spirits: Nutshells as a sustainable alternative to wood - Lara Campos; Pedro R. Soares; Francisco Barroso; Marta H.F. Henriques; Ivo Rodrigues (Food Chemistry, 2026)

Photoelectrocatalytic degradation of carbendazim using titanium‑tungsten oxide in a pilot-scale flow reactor - Joyce F. de Carvalho; Juliana de Almeida; Helena R. Tambelli; Ana Julia S. Rego; Maria Luiza P. da Silva; Débora N. Okamoto; Milene C. Codolo; Christiane de Arruda Rodrigues (Chemical Engineering Journal, 2026)

Rehydrated ground corn silage as alternative to feedlot lambs: feeding behavior and performance - Leandro A. S. da Silva; Cláudia L. S. Lima; Gleidson G. P. de Carvalho; Henry D. R. Alba; Maria L. G. M. L. de Araújo; Cláudia H. da Cruz; Carlindo S. Rodrigues; Dalton H. Pereira; José E. de Freitas Júnior; Manuela S. L. Tosto; Douglas dos S. Pina (Tropical Animal Health and Production, 2026)

Intake, digestibility and rumen fermentation in Nellore bulls grazing degraded or recovered pastures of Urochloa ssp. or the grass intercropped with pigeon pea - A.J. Furtado; A.L. Abdalla Filho; F. Perna Junior; R. Pasquini Neto; G.V. Silva; A.A.G. Lobo; L.M. Coelho; J.F. Bruno; A. Berndt; A.F. Pedroso; S.R. Medeiros; P.P.A. Oliveira; et al. (Animal Feed Science and Technology, 2026)

Seasonal biochemical fingerprints of outdoor cultivated Spirulina (Limnospira platensis) and Microchloropsis gaditana: insights into compositional and functional shifts - Diana Lopes; Ana S.P. Moreira; Tiago Conde; Andreia Ferreira; Kayane Oliveira; Alexandra Conde; Helena R. Rocha; Marta Coelho; Ana Gomes; Manuela Pintado; Ana Alexandra Ramos; Hugo Pereira; et al. (Algal Research, 2026)

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Differential effects of adolescent fatty acid amide hydrolase and monoacylglycerol lipase inhibition on adolescent and adult behaviors in male rats - Mary K. Estes; Vishnu Guda; Emei Thompson; Daniela Rodrigues de Oliveira; David B. Nowak; Cecilia J. Hillard; John R. Mantsch (Psychopharmacology, 2026)

Reply to Discussion by R. A. Henderson of ‘Kinematics of the Clarke River Shear Zone (northeastern Australia) and implications for the tectonic evolution of the Tasmanides’ - R. T. Rodrigues; G. Rosenbaum (Australian Journal of Earth Sciences, 2026)

Application of a Liquid Chromatography: Tandem Mass Spectrometry Based Method to Determine Plasma Cycloserine Concentrations in Indian MDR-TB Patients—A Pilot Study - Rohan V. Lokhande; Prerna R. Arora; Camilla Rodrigues; Ganesh R. Bhagure; Zarir F. Udwadia; Amita Gupta; Jeffrey A. Tornheim; Tester F. Ashavaid; Lancelot M. Pinto; Jai B. Mullerpattan; Ayesha Sunavala; Jigneshkumar Patel; et al. (Indian Journal of Clinical Biochemistry, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Advancing eutrophication mitigation through nature-based and hybrid solutions: A systematic review - Rafaela R. Morelato; Fernando Rodrigues-Silva; Guenther Carlos C. Viana; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Two decades of flood-pulse-driven chlorophyll-a dynamics in an Amazon floodplain lake - Ana Clara de Lara Maia; Anna Beatriz Silva Alves; Hulair Braga Carneiro; Lucas de Oliveira Arice; Nathalia Moraes Desani; Raiane Helena da Silva Santos; José Roberto Mantovani; Yasmim Carvalho Guimarães; Thanan Rodrigues; Deepak R. Mishra; Edward Park; Enner Alcântara (Science of The Total Environment, 2026)

Harnessing waste materials and tidal flow in constructed wetlands: High-Performance treatment of dye and surfactant-contaminated wastewater - J. Maciel; K. Rodrigues; R. Araújo; L. Pereira; G. Marinho (Journal of Environmental Management, 2026)

Hemocyte Apoptosis as a Biomarker of Environmental Stress in Aeglid Species (Decapoda: Anomura) - Renan A. P. dos Santos; Graziela G. Romagnoli; George S. Yasui; Isabela R. R. Moraes; Mariana V. Capparelli; Gabriel F. B. Rodrigues; Larissa R. C. de Oliveira; Antonio L. Castilho (Bulletin of Environmental Contamination and Toxicology, 2026)

Taxonomic update for the giant algal chloroviruses of the family Phycodnaviridae - Rodrigo A. L. Rodrigues; João Victor R. P. Carvalho; Lethícia R. Henriques; David D. Dunigan; James L. Van Etten (Archives of Virology, 2026)

New insights into the putative XX / XY sex chromosomal system in blue‐eyed red‐fin pleco Hypostomus soniae (Siluriformes, Loricariidae) - Luan Aércio Melo Maciel; Renata Coelho Rodrigues Noronha; Bruno Rafael Ribeiro de Almeida; Manoella Gemaque Cavalcante; Cleusa Yoshiko Nagamachi; Julio Cesar Pieczarka; Luís Reginaldo R. Rodrigues (Journal of Fish Biology, 2026)
Blue‐eyed red‐fin pleco Hypostomus soniae (family Loricariidae) presented a putative sex system XX/XY in early stage. Aiming to explore the inter‐populational karyotypic variation and proposed emergence of the XX/XY system, we studied 13 H. soniae individuals (6 males, 7 females) from the Tapajós River. Mitotic karyotypes and meiotic cells were analysed using C‐banding, site verification Ag‐NOR (nucleolar organizing region), chromomycin A 3 (CMA3) and fluorescent in situ hybridization with repetitive DNA probes (DNAr 18s, 5S, histone H1, H3, telomere). The synaptonemal complex on meiocytes was studied using immunodetection with anti‐structural maintenance of chromosomes protein 3, anti‐γH2AX and anti‐H3K9ac. The karyotype presented was 2 n = 64, with clear size heteromorphism varying between male and female. The species presented multiple NORs colocalized with 18S and CMA3‐positive marks in two pairs of acrocentric chromosomes. The centromeric region of pairs 25 and 26 carries the repeats of histones H1 and H3. All the bivalents at pachytene exhibited tip‐to‐tip pairing, revealing the absence of an XY pair with partial synapsis. The synaptic behaviour of the putative sexual pair failed to corroborate the XX/XY system hypothesis in H. soniae . Further cytogenetic and molecular investigations are necessary to determine the proposed emergence of an XX/XY sexual system in H. soniae and the regulatory mechanisms underlying its atypical meiotic behaviour.

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Interaction between diagenesis and faulting in sandstone reservoirs: Inferences from the Groningen gas field - Job P.B. Arts; Dallyn Rodrigues; Fadi H. Nader; Martyn R. Drury; Liviu C. Matenco; Ernst Willingshofer; André R. Niemeijer (Journal of Structural Geology, 2025)

Development of fluids containing silicon dioxide extracted from Agro-Industry waste and tamarind gum for wettability alteration of carbonate rocks - Maria Eduarda R. Vaz; Priscila F. Oliveira; Carolina R.A. Cruz; Letícia Cristina A. Sanches; Raissa T. Rodrigues; Luiz Carlos M. Palermo; Claudia R.E. Mansur (Fuel, 2025)

Valorisation of olive oil by-products into pectic- and glucuronoxylo-oligosaccharides via one-step fermentation - Ana Cordeiro; Andreia Fernandes; Andreia S. Ferreira; Elisabete Coelho; Manuel A. Coimbra; Sara C. Silvério; Vasco Cadavez; António M. Peres; Lígia R. Rodrigues; Cláudia Amorim (Food Chemistry, 2025)

Cryopreservation of fish ovarian tissue post-mortem: Solution for emergency genetic preservation - Thaiza R. de Freitas; Lis S. Marques; Raquel S. dos Santos; Renata V. Dantas; Thales S. França; Rômulo B. Rodrigues; Karel G. Torres Lozano; Eduardo Albuquerque; Diógenes H. Siqueira-Silva; Tiantian Zhang; Danilo P. Streit (Cryobiology, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Microencapsulation of Fridericia chica extract: stability, anthocyanin retention, and antioxidant properties for food and therapeutic applications - Vitória Ribeiro Garcia de Figueiredo Muniz; Ailane Souza de Freitas; Luan da Silva Dias Rabelo; Luís Felipe Perdigão Rodrigues; Karina Rodrigues Honorato; Ana Carolina Rorato; Ana Lúcia Tasca Gois Ruiz; Ilza Maria de Oliveira Sousa; Luciana Igarashi-Mafra; Mary Ann Foglio; Alvaro Luiz Mathias; Marcos R. Mafra (Bioactive Carbohydrates and Dietary Fibre, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Komagataella pastoris KM71H Attenuates Cognitive Deficits and Depressive-Like Behavior by the TLR4/NF-κB Signaling Pathway in an Aβ1-40-Induced AD-Like Mouse Model - Paloma T. Birmann; Giuliana Petiz Zugno; Airton Sinott; Rafael R. Rodrigues; Fabricio R. Conceição; Fernanda Severo Sabedra Sousa; Tiago Collares; Fabiana K. Seixas; Lucielli Savegnago (Molecular Neurobiology, 2025)

Partial attenuation of coral bleaching by turbidity along the Brazilian coast - Tainá Luchese Gaspar; Ronaldo Francini-Filho; Miguel Mies; Regina R. Rodrigues; Afonso Gonçalves Neto; Carlos Alberto da Silva Junior; Thomás Banha; Guilherme Ortigara Longo; Bárbara Segal (Coral Reefs, 2025)

Sugarcane radiation use efficiency: varietal differences, temperature dependence, and implications for modeling biomass across environments - Mathias Christina; David Clark; Fabio Ricardo Marin; Rafael Vasconcelos Ribeiro; Julio Victor Saez; Tendai Polite Chibarabada; Murilo dos Santos Vianna; Matthew R. Jones; Santiago Vianna Cuadra; Osvaldo Machado Rodrigues Cabral; Martin Moises Acreche; Henrique Boriolo Dias (Agricultural and Forest Meteorology, 2025)

SpiderATLAS : A Database of Spider Traits and Distributions in the Brazilian Atlantic Forest - Gabriel X. Boldorini; Paulo M. Martins; Antonio D. Brescovit; Adalberto J. Santos; Leonardo S. Carvalho; Ubirajara Oliveira; Philip Russo; Joyce C. B. Brito; Aparecida P. Barbosa; André Celso Bezerra Rodrigues; Aníbal Silva Cantalice; Arthur A. B. Rodrigues; et al. (Journal of Biogeography, 2025)
Aim Biodiversity shortfalls related to limited knowledge about geographic distribution (Wallacean) and species traits (Raunkiæran) are extremely common in many animal groups and perhaps more evident in invertebrate groups such as spiders. This lack of knowledge could present challenges for researchers investigating the response and effects of spiders along large spatial scales, particularly in the Global South. The aim of the SpiderATLAS is to facilitate research that links macroecology, biogeography, trait‐based ecology and global change biology. Location Brazilian Atlantic Forest, spanning virtually the entire eastern coastline of Brazil, encompassing 1,620,000 km 2 , 30 degrees of latitude (3° 42′ S to 33° 31′ S), and 22 degrees of longitude (34° 50′ W to 56° 45′ W). Taxon Spiders (Class Araneae), including 1648 species from 63 families. Methods We compiled the spatial distribution (i.e., occurrence data) and data on morphological characteristics and derived traits for spider species from species descriptions, taxonomic revisions and personal collection. Species occurrences were extracted from several data sources spanning from the 1880s to 2023. Data on the morphological traits of species were compiled from taxonomic and diversity inventory papers published between 1833 and 2024. Results We provide 9369 georeferenced point locations and six morphological traits (body length, prosoma length, prosoma width, prosoma height, femur I length, and patella I length) for 1648 spider species. Most data are available for females and males. The dataset and code are available to download from Dryad, World Spider Trait database, and the ZooTraits app. Main Conclusions The SpiderATLAS can be useful to access information on the distribution and traits of spiders, contributing to the development of macroecological, biogeographical and trait‐based ecology. This dataset can also facilitate the biodiversity conservation of one of the most abundant and important arthropod predators on the planet, in a biodiversity hotspot.

Evolution in Response to an Abiotic Stress Shapes Species Coexistence - Inês Fragata; Diogo P. Godinho; Leonor R. Rodrigues; Miguel A. Cruz; Flore Zélé; Oscar Godoy; Sara Magalhães (Ecology Letters, 2025)
Adaptation to abiotic stresses generally relies on traits that are not independent from those affecting species interactions. Still, the impact of such evolutionary processes on coexistence remains elusive. Here, we studied two spider mite species evolving separately on tomato plants that hyper‐accumulated cadmium, a stressful environment for herbivores, or on plants without cadmium. Through experimental evolution and structural stability theory, we found that both species coexist in the cadmium environment, but the evolution of a single species in cadmium leads to exclusion. However, when both species evolve in cadmium they can coexist. This shift occurred due to a simultaneous increase in intra and a decrease in interspecific competition in that environment. These predictions were further confirmed with complementary experiments of population dynamics. Therefore, population shifts to novel environments, even in the absence of interspecific competitors, may have unforeseen evolutionary consequences for community composition and the maintenance of species diversity.

Amino Acid Complexed Minerals Zn, Mn, and Cu Improve Bone and Intestinal Characteristics in Laying Pullets - Marcos José Batista dos Santos; Carlos Bôa-Viagem Rabello; Andresa de Gusmão Faria; Waleska R. L. Medeiros-Ventura; Rogério Ventura Silva Junior; Heraldo Bezerra de Oliveira; Fabiano Sellos Costa; Mércia Rodrigues Barros; Alba K. Fireman (Biological Trace Element Research, 2025)
The present study investigates the effect of partially supplemented trace minerals zinc (Zn), manganese (Mn), and copper (Cu) using 2 different sources: inorganic mineral (IM) or amino acid-complexed minerals (AACM), in pullet diets during 6 to 14 weeks. A total of 1120 Lohmann Brown Lite pullets were distributed into 40 experimental cages with 2 dietary treatments. Two dietary treatments were established: a IM supplemented with 70 mg kg⁻ 1 Zn (as oxide), 70 mg kg⁻ 1 Mn (as oxide), and 8 mg kg⁻ 1 Cu (as sulfate), and a test diet (IM + AACM) providing the same total elemental concentrations of Zn, Mn, and Cu, but with 40, 40, and 2.75 mg kg⁻ 1 from IM sources (oxides/sulfate) and 30, 30, and 5.25 mg kg⁻ 1 from AACM, respectively. Data were compared by Student's t-test ( P < 0.05). Zootechnical performance was not affected by mineral source ( P > 0.05). However, AACM increased relative intestinal weight ( P = 0.01) and small intestine length ( P = 0.05) and decreased cecum length ( P < 0.01). Tibia calcium and phosphorus contents were 8.5% and 6.9%, respectively, higher ( P < 0.05) in the AACM group. Birds fed AACM diets showed enhanced tibia bone density ( P < 0.01). Serum analysis showed elevated ( P < 0.05) red blood cells, hemoglobin, hematocrit, white blood cells, alkaline phosphatase, albumin, creatinine, and thyroxine levels in birds supplemented with AACM. Supplementation with AACM trace minerals enhance bone, intestine, and blood measurements in laying pullets without impacting growth or organ weights.

Patterns of pharmaceutical contamination in streams of European cities across urbanisation gradients: Potential impacts on One Health - Fernanda Rodrigues; Ana R. Calapez; André M.P.T. Pereira; Liliana J.G. Silva; Andreia Freitas; Rayan Bouchali; Andree De Cock; Marie Anne Eurie Forio; Peter Goethals; Silje H. Henni; Adeline Loyau; Anne Moen; et al. (Journal of Hazardous Materials, 2025)

Bisphenol AF (BPAF) jeopardizes male fertility and triggers intergenerational defects in zebrafish (Danio rerio) - Daniel Fernandes da Costa; Luciana Marino Borali; Maya Zanardini; Eduardo Antonio Sanches; Ana Regina Seabra de Souza; Maira da Silva Rodrigues; Adriana Carvalho Natal de Moraes; Hamid R. Habibi; Rafael Henrique Nóbrega (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Metabolomic profiles and antioxidant intake in female soccer players: a cross-sectional study - M. M. S. Gouveia; M. B. A. Nascimento; A. C. Crispim; E. R. da Rocha; M. P. P. Santos; E. S. Bento; T. M. Aquino; P. Balikian; N. A. Rodrigues; T. Ataide-Silva; G. G. de Araujo; F. A. B. Sousa (European Journal of Applied Physiology, 2025)

Tides of rebirth: A stratigraphic perspective on the Lazarus effect in freshwater bivalves in the Aptian-Albian Romualdo Formation, Araripe Basin, Brazil - Marcello G. Simões; Vitor B. Guerrini; Victor R. Silva; Filipe G. Varejão; Suzana A. Matos; Mariza G. Rodrigues; Lucas V. Warren; Mario L. Assine; Franz T. Fürsich (Cretaceous Research, 2025)

Ancient Introgression Explains Mitochondrial Genome Capture and Mitonuclear Discordance Among South American Collared Tropidurus Lizards - Matheus M. A. Salles; André L. G. Carvalho; Adam D. Leaché; Nicolas Martinez; Frederick Bauer; Martha Motte; Viviana Espínola; Miguel T. Rodrigues; Carla Piantoni; Marcio R. Pie; André Olivotto; Guarino R. Colli; et al. (Molecular Ecology, 2025)
Mitonuclear discordance—evolutionary discrepancies between mitochondrial and nuclear DNA phylogenies—can arise from various factors, including introgression, incomplete lineage sorting, recent or ancient demographic fluctuations, sex‐biased dispersal asymmetries, among others. Understanding this phenomenon is crucial for accurately reconstructing evolutionary histories, as failing to account for discordance can lead to misinterpretations of species boundaries, phylogenetic relationships, and historical biogeographic patterns. We investigate the evolutionary drivers of mitonuclear discordance in the Tropidurus spinulosus species group, which contains nine species of lizards inhabiting open tropical and subtropical environments in South America. Using a combination of population genetic and phylogenomic approaches applied to mitochondrial and nuclear data, we identified different instances of gene flow that occurred in ancestral lineages of extant species. Our results point to a complex evolutionary history marked by prolonged isolation between species, demographic fluctuations, and potential episodes of secondary contact with genetic admixture. These conditions likely facilitated mitochondrial genome capture while diluting signals of nuclear introgression. Furthermore, we found no strong evidence supporting incomplete lineage sorting or natural selection as primary drivers of the observed mitonuclear discordance. Therefore, the unveiled patterns are most consistent with neutral demographic processes, coupled with ancient mitochondrial introgression, as the main factors underlying the mismatch between nuclear and mitochondrial phylogenies in this system. Future research could further explore the role of other demographic processes, such as asymmetric sex‐biased dispersal, in shaping these complex evolutionary patterns.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

Twelve-year residual effect of sewage sludge on the biogeochemical cycling of potentially toxic elements in tropical Eucalyptus plantation - Antonio L. Florentino; Alexandre V. Ferraz; Adam C. Rodrigues; Nikolas S. Mateus; Paulo H.S. Cardoso; Timothy R. Filley; Eduardo Mariano; José Lavres; José L.M. Gonçalves; Cassio H. Abreu-Junior (Forest Ecology and Management, 2025)

Amazonian trees functional adjustments to long term experimental drought are limited and species dependent - Vanessa Negrão-Rodrigues; Paulo Bittencourt; Pablo Sanchez-Martinez; Lucy Rowland; Lion R. Martius; Patrick Meir; Manolo T. Quintilhan; José Roberto V. Aragão; Victor Brigatto; Vinicius D. Oliveira; Peter Groenendijk; Arlete A. Soares; et al. (Flora, 2025)

Luteal features and serum concentrations of progesterone and hCG in dairy goats submitted to estrus induction followed by intrauterine or intramuscular hCG administration - Alice L. Martins; Luana R. Côrtes; Juliana N.D. Rodrigues; Paulo Sergio C. Rangel; Ana Lucia R. e S. Maia; Felipe Z. Brandão; Luiz Gustavo B. Siqueira; Bruna W. de Freitas; Jeferson F. Fonseca (Domestic Animal Endocrinology, 2025)

Exploring In Vitro Mesenchymal Stem Cell Osteodifferentiation via Vibrational Microspectroscopy: A Review - Daniela S. Bispo; Inês C. R. Graça; João A. Rodrigues; João T. S. Martins; Mariela M. Nolasco; Maria P. M. Marques; Helena I. S. Nogueira; João F. Mano; Mariana B. Oliveira; Paulo J. A. Ribeiro-Claro; Ana M. Gil (Stem Cell Reviews and Reports, 2025)
The application of vibrational microspectroscopy to the study of in vitro mesenchymal stem cells (MSC) osteogenic differentiation is a promising approach towards the understanding of the molecular processes involved in bone fabrication. Both infrared (IR) and Raman microspectroscopies have been applied, with a clear predominance of the latter. Bone marrow MSC have been the target of most studies, followed by those originating from dental/oral and adipose tissues. Interests have increasingly addressed single cell and extracellular matrix characterization at the molecular level. Most studies have focused on the characteristics and maturity of time-course mineralization, attempting to localize mineral aggregates formed onto the evolving collagen strands. Some reports have focused on time-dependent changes in protein structure and other components of extracellular matrix components. Besides spectral band examination through position, linewidth and shape, selected band ratios have proved largely informative to assess mineral species evolution and mineral-to-organic matrix interactions over time. The increasing use of multivariate analysis (or chemometrics) and machine learning strategies to detect finer spectral variations is evident, as is the promise of more recent IR and Raman variations to provide higher sensitivity and spatial resolution conditions. The label-free non-invasive nature of vibrational microspectroscopy makes it particularly promising for rapid and effective selection of suitable MSC donors, to support scale-up procedures for translation to the clinic. Some of the challenges to be faced are briefly discussed. Graphical Abstract

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Turning up the heat on skeletal muscle adaptations and neuromuscular function: key considerations for passive heating prescription and best practices - Patrick Rodrigues; Geoffrey M. Minett; Lucas B. R. Orssatto (European Journal of Applied Physiology, 2025)
Despite compelling evidence supporting the benefits of passive heat therapy in promoting skeletal muscle adaptation and enhancing neuromuscular function, the topic remains debated. Some recent studies report no significant effects on muscle protein synthesis, muscle mass, recovery, strength, or power. This raises critical questions: is passive heat therapy not actually effective? Or do these discrepancies reflect inconsistencies in study protocols and an overgeneralisation of the term passive heating ? Despite its growing recognition as a health treatment, exercise mimetic, and tool for sport performance and recovery, the interpretation of outcomes is often simplistic or misinformed. In this opinion article, we discuss the disparities in the literature and highlight the risks of oversimplification, such as the binary view that passive heat therapy either “works” or “does not work.” We also propose incorporating the FITT (Frequency, Intensity, Time, and Type) principles from exercise science into thermal therapy research to enhance methodological consistency and clarity. By adopting a more structured and rigorous approach, the field can better realise the potential of passive heat therapy as a scientifically grounded intervention for both health and sport performance applications.

The role of nest-site interference competition with Cape Verde Shearwater in explaining breeding success of Red-billed Tropicbird on Raso Islet, Cape Verde archipelago - Jaime A. Ramos; Catelene Monteiro; Isabel Rodrigues; Diana M. Matos; Vitor H. Paiva; Filipe R. Ceia; Jorge M. Pereira; Kenny Delgado; Stefan Antunes (Journal of Ornithology, 2025)

Are fish larvae contaminated before they start eating? First evidence of microplastic contamination in the yolk-sac of wild fish larvae - Sabrina M. Rodrigues; Francisca Espincho; Michael Elliott; C. Marisa R. Almeida; Sandra Ramos (Frontiers in Marine Science, 2025)
Microplastics (MPs) ingestion in wild fish during the early stages remains a field with scarce information and contradictory findings in laboratory studies. This study evaluated whether MPs contamination of larval fish stages begins at the commencement of the exogenous feeding phase and whether different species and ontogenetic development stages exhibit different profiles of MPs contamination. We assessed, for the first time, the presence of MPs in the larval stages of two species: the European sardine ( Sardina pilchardus ), a marine migrant species, and the common goby ( Pomatoschistus microps) , an estuarine resident species, inhabiting the Douro Estuary (NW Portugal). In both species, MPs were found even in the yolk-sac stage, when fish larvae still have endogenous feeding and do not actively prey on other organisms. This illustrates that fish larvae are already contaminated at a stage where the mouth is still not fully open, further indicating that MPs were not actively ingested. MPs contamination did not vary between species or throughout the ontogenetic development stages, showing similar levels of contamination and MPs contamination profiles. This novel study provides relevant insights into MPs contamination processes, showing that MPs contamination can occur early in the life cycle of fishes, from hatching onwards. Furthermore, the presence of MPs in fish larvae appears to be more dependent on the MPs that are in higher abundance in the surrounding water than fish larvae preferences or ecological guild, physical characteristics, or even the ontogenetic developmental stage.

Functional recovery of tropical forests: The role of restoration methods and environmental conditions - Rens Brouwer; Marielos Peña-Claros; Frans Bongers; Lourens Poorter; Joannès Guillemot; Danilo R.A. Almeida; Catherine Torres de Almeida; Angélica F. Resende; Laura H.P. Simões; Natália M. Ivanauskas; Renato A. Ferreira de Lima; Vinicius Castro Souza; et al. (Biological Conservation, 2025)

Enteric methane emissions and thermal comfort indexes of Nellore steers in a livestock-forestry system in the Amazon biome - Alyce Monteiro; Flabiele S. Silva; Adibe L. Abdalla; Maguy Eugène; Luciano Barreto-Mendes; Renato A. R. Rodrigues; Ciro A. Magalhães; Bruno C. Pedreira (Tropical Animal Health and Production, 2025)

Application of graphene oxide incorporated into biopolymer microfibers as a novel adsorbent for removing pharmaceuticals from water - L. Pellenz; A. H. da Silva Júnior; C. R. S. de Oliveira; L. P. Mazur; L. H. I. Mei; N. M. Medeiros Rodrigues; A. A. U. de Souza; A. da Silva (International Journal of Environmental Science and Technology, 2025)

Inheritance and fitness costs of Cry1Ab and Cry1Ac resistance in Brazilian populations of Diatraea saccharalis (Lepidoptera: Crambidae) - Juliana G. Rodrigues; Caroline Izabel R. Sakuno; Fabricio José B. Francischini; Karen Missy A. Komada; Fangneng Huang (Crop Protection, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

ESTIMET: Enhanced and Spatial-Temporal Improvement of MODIS EvapoTranspiration algorithm for all sky conditions in tropical biomes - Cinthia M.A. Claudino; Guillaume F. Bertrand; Rodolfo L.B. Nóbrega; Cristiano das N. Almeida; Ana Cláudia V. Gusmão; Suzana M.G.L. Montenegro; Bernardo B. Silva; Eduardo G. Patriota; Filipe C. Lemos; Jaqueline V. Coutinho; José Welton Gonçalo de Sousa; João M. Andrade; et al. (Remote Sensing of Environment, 2025)

Effects of bisphenol A alternatives (BPS and BPAF) on zebrafish (Danio rerio) spermatogenesis ex vivo: meiosis damage and transcriptional deregulation of genes related to spermatogenic processes and epigenetic regulation - Daniel Fernandes da Costa; Maira da Silva Rodrigues; Luciana Marino Borali; Beatriz Marques de Souza; Hamid R. Habibi; Rafael Henrique Nóbrega (Environmental Toxicology and Pharmacology, 2025)

Typologies for ecosystem accounting for the Brazilian Pantanal - Fernando Rodrigues Teixeira Dias; Catia Urbanetz; Pedro R. Andrade (Wetlands Ecology and Management, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Relationship between estrus and reactivity on the reproductive performance of beef cows - Francisco A.R. Catalano; Luiz E. Kozicki; Isis V. Rodrigues; Ruan R. Daros (Applied Animal Behaviour Science, 2025)

Unlocking biochemical profile of Chaetoceros calcitrans, Cylindrotheca fusiformis, and Nannofrustulum shiloi (Bacillariophyta) for nutritional and added-value applications - Ana S.P. Moreira; Helena R. Rocha; Susana Aveiro; Andreia S. Ferreira; Kayane Oliveira; Alexandra Conde; Marta Coelho; Alexandre M.C. Rodrigues; Natacha Coelho; Hugo Pereira; Ana Gomes; Manuela Pintado; et al. (Algal Research, 2025)

Evaluation and calibration of MERRA-2 and CAMS reanalysis for PM2.5 in a semi-urbanized area in the south of the Amazon - Danielle Nassarden; Jorge Menezes; Carlos Barbosa Pessoa; Anderson Carneiro; Luiz O. F. dos Santos; Glauber Cirino; Breno Imbiriba; Fernando Sallo; Leone F. A. Curado; Thiago R. Rodrigues; João Basso; Marco A. Franco; et al. (Air Quality, Atmosphere & Health, 2025)

Total nutrient digestibility and small intestine starch digestion in Nellore and Nellore × Angus steers fed whole shelled corn-based diet with or without roughage - Priscilla D. Teixeira; Aline C. Rodrigues; Daniel R. Casagrande; Erick D. Batista; José M. Oliveira; Ana C.O. Santos; Pedro V.R. Paulino; Marcio M. Ladeira (Livestock Science, 2025)

Understanding the impact of different post-digestion enzymatic inhibition methods and storage conditions on standardized gastrointestinal model (INFOGEST): A case study of Pleurotus ostreatus mushroom biomass - Helena Araújo-Rodrigues; Ana Sofia Salsinha; Ezequiel R. Coscueta; João Bettencourt Relvas; Freni K. Tavaria; Manuela E. Pintado (Food Research International, 2025)

Distinctness Between Taxonomic and Functional Diversity Indexes of Bryozoan-Associated Decapods in Southeastern Brazil - G. F. B. Rodrigues; L. Zacari; M. R. R. Trevisan; I. R. R. Moraes; A. L. Castilho (Thalassas: An International Journal of Marine Sciences, 2025)

The role of the P2X7 receptor in inactivated SARS-CoV-2-induced lung injury - N. C. Carvalho-Barbosa; Fabiana Cristina-Rodrigues; Jairo R. Temerozo; Thiago M. L. Souza; Andre L. Gouvêa; Claudio A. Canetti; Eleonora Kurtenbach; Dumith Chequer Bou-Habib; Claudia F. Benjamim; Christina M. Takiya; Luiz E. B. Savio; Robson Coutinho-Silva (Purinergic Signalling, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Multivariate analysis to evaluate the storage time of cocoa honey (Theobroma cacao L.) processed by pasteurization and high intensity ultrasound - Manuela B. Nascimento; Bruno N. Paulino; Suzana B. Silva; Kathleen R. Deegan; Joseane C.G. Alencar; Adriana C.R. Ferreira; Frederico M. Rodrigues; Paulo R.R. Mesquita; Sergio E. Soares (Food Chemistry, 2025)

Estimation of diurnal and nocturnal radiation balance in tropical ecosystems - D. O. Maionchi; I. J. C. de Paulo; S. R. de Paulo; J. B. Marques; A. L. P. Junior; H. J. A. da Silva; R. S. Palácios; T. R. Rodrigues; T. A. dos Santos; A. M. S. Lima; M. S. Biudes; L. Sanches; et al. (Theoretical and Applied Climatology, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

A Cryptococcus neoformans polysaccharide conjugate vaccine made with filtered polysaccharide elicits protective immunity in mice - Piotr R. Stempinski; Paola Ramos Irizarry; Scott A. McConnell; Livia C. Liporagi Lopes; Samuel Rodrigues Dos Santos Júnior; Maggie P. Wear; Arturo Casadevall (Fungal Biology, 2025)

Neuroinflammation in Severe COVID-19: The Dynamics of Inflammatory and Brain Injury Markers During Hospitalization - Carla Andretta Moreira Neves; Gilson P. Dorneles; Paula C. Teixeira; Paulo C. Santana Filho; Alessandra Peres; Carina Rodrigues Boeck; Liane N. Rotta; Claudia E. Thompson; Pedro R. T. Romão (Molecular Neurobiology, 2025)

Simulation of the natural fractures influence on hydraulic fractures propagation using high aspect ratio interface elements - Lucas G. Barbosa; Pedro R. Cleto; Michael A. Maedo; Murilo Camargo; Eduardo A. Rodrigues; Osvaldo L. Manzoli (Computers and Geotechnics, 2025)

Meal delivery and the local restaurant industry - Carlos R. Azzoni; Rodrigo M.S. Moita; Mateus Rodrigues (Applied Geography, 2025)

The invasion of Pagurus longicarpus Say, 1817 in the Wadden Sea: Ecological niche modeling to predict its further expansion to the North and Baltic Sea - Leonardo Cirillo; Gabriel F. B. Rodrigues; Alexandre R. da Silva (Biologia, 2025)

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Distribution of microplastics in the tidal flats of La Parguera, Puerto Rico - Brenna R. Bruffey; Lisa J. Rodrigues (Marine Pollution Bulletin, 2025)

Impact of cigarette butts elutriates on Artemia franciscana in a climate change context - S. Couto; S. Rodrigues; R. Patrão; M. Vieira; S.C. Antunes; C. Pinheiro (Marine Pollution Bulletin, 2025)

Evaluation of Scalibor® deltamethrin collar chronic exposure in dogs - Larissa T.P. Rodrigues; Andriele F. Qualhato; Carolle V.M. Sprícigo; Kelly C.A. Arantes; Rayanne H.S. da Silva; Alexandre C.M. Barros; Monica C. Vicente; Murilo R. Souza; Luiza G.F. de Paula; Danilo Roman-Campos; Artur S. Miranda; Danieli B. Martins; et al. (Research in Veterinary Science, 2025)

An engineered, biocide-grafted TiO2-based nanohybrid material with enhanced photocatalytic and antimicrobial activity - Olga Ferreira; Mafalda Gil; Ana Carapeto; Andreia Barreto; Manuela Pereira; Mário S. Rodrigues; Lucas Habib; Luciana C. Gomes; Rita Teixeira-Santos; Filipe J.M. Mergulhão; Elisabete R. Silva (Journal of Cleaner Production, 2025)

Impact of Drilling Fluids on Borehole Hydraulic Conductivity in Geotechnical Investigations - F. Schnaid; B. A. Rodrigues; D. E. Lourenço; G. M. A. do Patrocínio; S. Maghous; J. L. dos Santos; M. L. P. Alves; R. Fonseca; V. B. de Araújo (Geotechnical and Geological Engineering, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Modeling different modes of failure in reinforced concrete beams combining tensile and shear-frictional damage models and bond–slip coupling for non-matching reinforcement and fragmented concrete meshes - Andrei F. Villa dos Santos; Marcela Gimenes; Eduardo Alexandre Rodrigues; Pedro R. Cleto; Osvaldo Luís Manzoli (Engineering Structures, 2025)

Improving survival and growth of caprine preantral follicles cultured in medium commonly used for MSC: Role of oxidative stress regulation and epigenetic changes - Ana F.B. Silva; Laritza F. Lima; Anna C.A. Ferreira; Ariclécio C. Oliveira; Napoleão M.A. Neto; Benner G. Alves; Ana P.R. Rodrigues; Eduardo L. Gastal; Vilceu Bordignon; José R. Figueiredo (Domestic Animal Endocrinology, 2025)

Integrative species delimitation and biogeography of the Rhinella margaritifera species group (Amphibia, Anura, Bufonidae) suggest an intense diversification throughout Amazonia during the last 10 million years - Antoine Fouquet; Miqueias Ferrão; Miguel T. Rodrigues; Fernanda P. Werneck; Ivan Prates; Leandro J.C.L. Moraes; Tomas Hrbek; Juan C. Chaparro; Albertina P. Lima; Renata Perez; Andre Pansonato; Vinicius T. Carvalho; et al. (Systematics and Biodiversity, 2024)

Airborne DNA: State of the art – Established methods and missing pieces in the molecular genetic detection of airborne microorganisms, viruses and plant particles - C.-E. Pogner; C. Antunes; G.P. Apangu; N. Bruffaerts; S. Celenk; A. Cristofori; N. González Roldán; A. Grinn-Gofroń; B. Lara; M. Lika; D. Magyar; M. Martinez-Bracero; et al. (Science of The Total Environment, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Impact of climatic seasons on the dynamics of carbon, nitrogen and mercury in soils of Brazilian biomes affected by gold mining - Matheus B. Soares; Rebeca R. Rodrigues; Laura O. Péres; Carlos Eduardo P. Cerri; Luís Reynaldo F. Alleoni (Science of The Total Environment, 2024)

Microbiota diversity of three Brazilian native fishes during ice and frozen storage - Rafaela C. Baptista; Ilario Ferrocino; Matheus Pavani; Tatiane M. Guerreiro; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Rodrigo R. Catharino; Elenilson G. Alves Filho; Sueli Rodrigues; Edy S. de Brito; Magdevis Y.R. Caturla; et al. (Food Microbiology, 2024)

Effect of connection elements on shear strength of wooden pieces for structural use - Hellen M. A. C. Rodrigues; Evelize A. Amaral; Rodrigo A Pereira; José Benedito Guimarães Junior; Paulo R. G. Hein (Journal of the Indian Academy of Wood Science, 2024)

Bullseye: shotgun metagenomics taking aim at the microbial diversity associated with tubes of Ceriantharia - Hellen Ceriello; Gustavo R. Brito; Bruno Francesco Rodrigues de Oliveira; Marielton dos Passos Cunha; Sérgio N. Stampar (Aquatic Ecology, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Deciphering Permian wetland deposits of the Parnaíba Basin through an integrated study of lithofacies and palynofacies in Western Gondwana - Edvaldo José Oliveira; Paulo A. Souza; Ana Maria Góes; Cristina M. Félix; Daiana R. Boardman; Luiz Saturnino de Andrade; Eduardo Premaor; Gelson Luís Fambrini; Afonso César Rodrigues Nogueira; Ana Karina Scomazzon (Journal of South American Earth Sciences, 2024)

Has unsustainable groundwater use induced low flow regimes in the Urucuia Aquifer System? An urgent call for integrated water management - André F. Rodrigues; Bruno M. Brentan; Marta V. Ottoni; Jhones S. Amorim; Maria A.A. Mourão; Nilton Curi; Junior C. Avanzi; Carlos R. de Mello (Journal of Environmental Management, 2024)

Nanoencapsulation of quinoa oil enhanced the antioxidant potential and inhibited digestive enzymes - Bruna Lorena Meneses Marques; Thaís Souza Passos; Alyne Ingrydid Dantas; Malu Andrade Alves de Lima; Susana Margarida Gomes Moreira; Victor M. Rodrigues; Marina R. do Nascimento Dantas; Patrícia Santos Lopes; Ana Paula Barreto Gomes; Rafael da Silva Fernandes; Francisco Humberto Xavier Júnior; Francisco Canindé de Sousa Júnior; et al. (Food Research International, 2024)

Juvenile-related tolerance to papaya sticky disease (PSD): proteomic, ultrastructural, and physiological events - Silas P. Rodrigues; Eduardo de A. Soares; Tathiana F. Sá Antunes; Marlonni Maurastoni; Leidy J. Madroñero; Sabrina G. Broetto; Lucas E. C. Nunes; Brunno R. F. Verçoza; David S. Buss; Diolina M. Silva; Juliany C. F. Rodrigues; José A. Ventura; et al. (Plant Cell Reports, 2024)

Evaluation of antioxidant, anti-inflammatory and cytotoxic potential of phytochemicals from Gymnostachyum febrifugum -an in vitro study - K. J. Spandana; K. P. Fathimathul Lubaba; A. Sujina; Wilson Joel Rodrigues; K. R. Chandrashekar; N. Bhagya (Plant Biosystems, 2024)

Contribution to the Iberian thermomediterranean oak woods (Spain, Portugal): the importance of their teaching for the training of experts in environmental management - Cano E.; Piñar Fuentes J.C.; Cano Ortiz A.; Quinto Canas R.; Rodrigues Meireles C.; Mauro R.; Pinto Gomes C.J.; Spampinato G.; Musarella C. M. (Plant Biosystems, 2024)

Multi‐Taxa Responses to Climate Change in the Amazon Forest - Carlos A. S. Rodrigues‐Filho; Flávia R. C. Costa; Juliana Schietti; Anselmo Nogueira; Rafael Pereira Leitão; Juliana Menger; Gabriel Borba; Caian Souza Gerolamo; Stefano S. Avilla; Thaise Emilio; Carolina Volkmer de Castilho; Douglas Aviz Bastos; et al. (Global Change Biology, 2024)
Tropical biodiversity is undergoing unprecedented changes due to the hydrological cycle intensification, characterized by more intense droughts and wet seasons. This raises concerns about the resilience of animal and plant communities to such extremes and the existence of potential refugia—areas theorized to safeguard biological communities from adverse climate impacts. Over 20 years of monitoring in Central Amazonia, we investigated the short‐term and long‐term effects of hydrological cycle intensification on bird, fish, ant, and palm communities. We explored whether the ‘insurance effect’ of climate trends (droughts buffered by preceded wet seasons) or ‘environmental refugia’ (droughts or floods buffered by topographic features) could lessen the impact of climate events on community composition, richness, evenness, and species rank. Pronounced abundance changes were observed among animal species, whereas palm species showed relative temporal stability. Birds and fish were more affected by the immediate and long‐term severity of droughts and wet periods, while ants responded primarily to short‐term drought impacts. Conversely, palm communities exhibited delayed responses to climate extremes, primarily in long‐term comparisons. As expected, the proposed ‘insurance effect’ mitigates the long‐term impacts of extreme climate events on animal and plant community trends. However, less extreme hydrological conditions linked to topographic features did not provide effective ‘environmental refugia’ for animals or plants during adverse climate conditions. These outcomes underscore the complex and varied biological responses to ongoing climate change, challenging the prevailing assumptions about the efficacy of environmental refugia and highlighting the nuanced resilience of biodiversity in Central Amazonia.

Holistic evaluation of the environmental impacts of shipping in the sensitive region of Ria de Aveiro - A. Monteiro; V. Rodrigues; A. Picado; J.M. Dias; N. Abrantes; A. Ré; M. Rosa; M. Russo; A. Barreirinha; M. Potiris; M. Aghito; R. Hänninen; et al. (Science of The Total Environment, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evaluation of operational parameters and technology readiness for enhanced management of oilfield produced water treated by ozonation - Sabryna Isabelly Giordani da Costa; Silvio Edegar Weschenfelder; Maria Alice Prado Cechinel; João Vítor R. Fuck; Daniela Gier Della Rocca; Belisa Alcantara Marinho; Sálvio Lima de Carvalho Neto; Maria de Fatima Rodrigues da Cunha; Luciana Prazeres Mazur; Regina F.P.M. Moreira; Adriano da Silva; Selene M.A. Guelli. U. de Souza; et al. (Chemical Engineering Journal, 2024)

Gut colonization by extended-spectrum β-lactamase-producing Escherichia coli in dairy herd in Brazil: successful dissemination of a One Health clone - Luciana Sartori; Fábio P. Sellera; Taiana T. Silva-Pereira; Bruna Fuga; Danny Fuentes-Castillo; Milena Dropa; Quézia Moura; Miriam R. Fernandes; Larissa Rodrigues; Fernanda Esposito; Elder Sano; Mario A. R. Aleman; et al. (Veterinary Research Communications, 2024)

Silicon-mediated resistance in maize against infection by Colletotrichum graminicola - Ana C. R. Mochko; Bruno N. Silva; Lillian M. Oliveira; Leandro C. Silva; Fabrício A. Rodrigues (Plant and Soil, 2024)

P02-28 Microfluidics technology as a tool to improve maturation and drug metabolism capacity of stem cell-derived hepatocytes in vitro - J.S. Rodrigues; S. Relvas; P.G. Condelipes; B. Silva; R. Bozzo; P. Guedes de Pinho; V. Chu; F. Remião; J.P. Conde; J.P. Miranda (Toxicology Letters, 2024)

Three picorna-like viruses found associated with the spider mite, Tetranychus truncatus (Acari: Tetranychidae) - Thaís Danielle Duarte Santana; Thiago Magalhães Rodrigues; Lucas de Araujo Andrade; Ethiane R. Santos; Daniel M.P. Ardisson-Araújo (Journal of Invertebrate Pathology, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

Assessing interpreter’s disagreements in land cover reference data collection from historical Landsat time series in Amazon - Mariane S. Reis; Lucélia S. de Barros; Manoel R. Rodrigues Neto; Dayane Rafaela V. de Moraes; Noeli Aline P. Moreira; Gabriel Mikael R. Alves; Bruno V. Adorno; Cassiano Gustavo Messias; Luciano V. Dutra; Camilo D. Rennó; Sidnei João S. Sant’Anna; Maria Isabel S. Escada (International Journal of Remote Sensing, 2024)

Uncovering microplastics contamination in canned seafood - Diogo M. Silva; C. Marisa R. Almeida; Francisco A. Guardiola; Rúben Pereira; Sabrina M. Rodrigues; Sandra Ramos (Food Chemistry, 2024)

Effects of post-exercise cold-water immersion on performance and perceptive outcomes of competitive adolescent swimmers - Natanael P. Batista; Flávia A. de Carvalho; Caio R. D. Rodrigues; Jéssica K. Micheletti; Aryane F. Machado; Carlos M. Pastre (European Journal of Applied Physiology, 2024)
Purpose To evaluate the effects of repeated use of cold-water immersion (CWI) during a training week on performance and perceptive outcomes in competitive adolescent swimmers. Methods This randomized-crossover study included 20 athletes, who received each intervention [CWI (14 ± 1 °C), thermoneutral water immersion (TWI) (27 ± 1 °C) as placebo, and passive recovery (PAS)] three times a week between the land-based resistance training and swim training. The interventions were performed in a randomized order with a 1-week wash-out period. We tested athletes before and after each intervention week regarding swim (100 m freestyle sprints) and functional performance (flexibility, upper and lower body power, and shoulder proprioception). We monitored athlete’s perceptions (well-being, heaviness, tiredness, discomfort and pain) during testing sessions using a 5-item questionnaire. Athlete preferences regarding the interventions were assessed at the end of the study. We used generalized linear mixed models and generalized estimating equations for continuous and categorical variables, respectively (intervention x time). Results We found a time effect for swim performance ( p = .01) in which, regardless the intervention, all athletes improved sprint time at post-intervention compared to baseline. There was an intervention effect for pain ( p = .04) and tiredness ( p = .04), but with no significant post-hoc comparisons. We found no significant effects for other outcomes. All athletes reported a preference for CWI or TWI in relation to PAS. Conclusion The repeated use of CWI throughout a training week did not impact functional or swim performance outcomes of competitive adolescent swimmers. Perceptive outcomes were also similar across interventions; however, athletes indicated a preference for both CWI and TWI.

Depth, hard coral, and turf cover as predictors of micro-scale spatial distribution of fishes in a subtropical rocky reef - Thiago E. Rodrigues; Vinícius J. Giglio; Fernando Z. Gibran; Fernanda A. Rolim; Leonardo M. Neves; Guilherme Henrique Pereira-Filho; Gustavo Shintate; Gabriel R. S. Souza; Domingos Garrone-Neto; Fabio S. Motta (Environmental Biology of Fishes, 2024)

The role of microRNAs in NBS-LRR gene expression and its implications for plant immunity and crop development - J. C. M. Rodrigues; J. Carrijo; R. M. Anjos; N. B. Cunha; P. Grynberg; F. J. L. Aragão; G. R. Vianna (Transgenic Research, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Cytotoxic screening of plants from the Brazilian Atlantic Forest has led to the identification of Casearia arborea and Sorocea hilarii as sources of antitumor compounds - L. A. Rodrigues; A. A. Almeida; A. P. Agrizii; N. Pacheco; B. C. R. Carvalho; A. C. Zanatta; M. Kohlhoff; C. M. M. E. Torres; G. C. Bressan; J. P. V. Leite (Natural Product Research, 2024)

The role of health and wellbeing in shaping local park experiences during the COVID-19 pandemic - Lauren A. Ferguson; Michael D. Ferguson; Krista Rodrigues; Darrick Evensen; Alexander R. Caraynoff; Kimberly Persson; Josephine B. Porter; Stephen Eisenhaure (Journal of Outdoor Recreation and Tourism, 2024)

Blown film of PLA for packaging with green tea and fish industrial residues: An insight on their properties - Pedro V. Rodrigues; Ana B. Cunha; Mariana A. Andrade; Fernanda Vilarinho; Ana Vera Machado; M. Cidália R. Castro (Food Packaging and Shelf Life, 2024)

Protein-assisted synthesis of chitosan-coated minicells enhance dendritic cell recruitment for therapeutic immunomodulation within pulmonary tumors - Jing Feng; Yiting Liu; Xiaoran Zheng; Min Gao; Li Wang; Lígia R. Rodrigues; Yuting Wen; Hangcheng Pan; Gege Li; Longjiang Zhang; Bing Wan; Yunlei Zhang (Carbohydrate Polymers, 2024)

Diminishing benefits of thermal mass in Iranian climate: Present and future scenarios - Eugénio Rodrigues; Nazanin Azimi Fereidani; Marco S. Fernandes; Adélio R. Gaspar (Building and Environment, 2024)

Ambush strategy enhances organisms’ performance in rock–paper–scissors games - R. Barbalho; S. Rodrigues; M. Tenorio; J. Menezes (BioSystems, 2024)

Do hurricanes or freezing events regulate the sustainability of subtropical mangroves on the Gulf of Mexico coast? - Marcelo C. L. Cohen; Qiang Yao; Adriana V. de Souza; Kam-biu Liu; Sergio Nunes; Erika Rodrigues; Luiz C. R. Pessenda; Nicholas Culligan (Regional Environmental Change, 2024)

A densely sampled molecular phylogeny of Tachigali (Leguminosae), an evolutionarily successful lineage of neotropical ant-housing canopy trees - Isau Huamantupa-Chuquimaco; Vitor Hugo Maia; Haroldo Cavalcante de Lima; Maristerra Rodrigues Lemes; Cristiane Snak; Bernarda Gregório; Sérgio Ricardo S. Cardoso; Luciano Paganucci de Queiroz; Charles E. Zartman; Gwilym P. Lewis; Euan K. James; Kyle G. Dexter; et al. (Brazilian Journal of Botany, 2024)

Kinematics of the Clarke River Shear Zone (northeastern Australia) and implications for the tectonic evolution of the Tasmanides - R. T. Rodrigues; G. Rosenbaum; R. Abdullah (Australian Journal of Earth Sciences, 2024)

Improving coffee capsules recyclability - A combined assessment of circularity and environmental performance of a novel design - Sara M. Pinto; Joana R. Gouveia; Marcelo Sousa; Bruno Rodrigues; José Oliveira; Carlos Pinto; A.J. Baptista (Sustainable Production and Consumption, 2024)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Provenance of volcano-sedimentary features using tourmaline and REE compositional analysis, in the Paraná Basin, southern Brazil - Isaque C. Rodrigues; Ana M.P. Mizusaki; Glaucia N. Queiroga; Cassiana R.L. Michelin; Fernando R. Rios (Journal of South American Earth Sciences, 2024)

Deciphering global patterns of forest canopy rainfall interception (FCRI): A synthesis of geographical, forest species, and methodological influences - Carlos R. de Mello; Li Guo; Chuan Yuan; André F. Rodrigues; Renato R. Lima; Marcela C.N.S. Terra (Journal of Environmental Management, 2024)

Biodegradable PBAT/PLA blend films incorporated with turmeric and cinnamomum powder: A potential alternative for active food packaging - Layara L.R.L. de Castro; Lauriene G.L. Silva; Iago R. Abreu; Cristiano J.F. Braz; Samara C.S. Rodrigues; Regilda S. dos R. Moreira-Araújo; Rudy Folkersma; Laura H. de Carvalho; Renata Barbosa; Tatianny S. Alves (Food Chemistry, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Landscape Ecology Meets Disease Ecology in the Tropical America: Patterns, Trends, and Future Directions - Matheus C. S. Mancini; Julia Rodrigues Barreto; Raquel L. Carvalho; Renata L. Muylaert; Ricardo Corasa Arrais; Paula R. Prist (Current Landscape Ecology Reports, 2024)

Evaluation of blastocyst re-expansion, quality in relation to storage temperature, and sexing using blastocoel fluid after manual perforation with a hand-held needle involving in vivo produced equine embryos - Giovana Siqueira Camargo; Luiz Daniel de Barros; José Paes Oliveira-Filho; Cristiana Raach Bromberger; Luciane Alarcao Dias-Melicio; Leandro Alves dos Santos; Don R. Bergfelt; Erica Rodrigues Ferraz de Andrade; Heloisa Siqueira Canesin; Cezinande de Meira; Fernanda Saules Ignácio (Theriogenology, 2024)

Chilled Pacu (Piaractus mesopotamicus) fillets: Modeling Pseudomonas spp. and psychrotrophic bacteria growth and monitoring spoilage indicators by 1H NMR and GC–MS during storage - Rafaela C. Baptista; Rodrigo B.A. Oliveira; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Matheus Pavani; Tatiane M. Guerreiro; Rodrigo R. Catharino; Elenilson G.A. Filho; Sueli Rodrigues; Edy S. de Brito; Verônica O. Alvarenga; et al. (International Journal of Food Microbiology, 2024)

Assessment of the impact of conservation measures by modeling soil loss in Minas Gerais, Brazil - A. K. M. Soares; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2024)

On the estimation of scintillation severity using background F-region peak densities: description and example results using GOLD observations - J. Sousasantos; F. S. Rodrigues; A. O. Moraes; R. W. Eastes; J. F. G. Monico (GPS Solutions, 2024)

Consistent Symbiodiniaceae community assemblage in a mesophotic-specialist coral along the Saudi Arabian Red Sea - Silvia Vimercati; Tullia I. Terraneo; Carolina Bocanegra Castano; Federica Barreca; Benjamin C. C. Hume; Fabio Marchese; Mustapha Ouhssain; Alexandra Steckbauer; Giovanni Chimienti; Ameer A. Eweida; Christian R. Voolstra; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Introduction The Red Sea is a narrow rift basin characterized by latitudinal environmental gradients which shape the diversity and distribution of reef-dwelling organisms. Studies on Symbiodiniaceae associated with select hard coral taxa present species- specific assemblages and concordant variation patterns from the North to southeast Red Sea coast at depths shallower than 30 m. At mesophotic depths, however, algal diversity studies are rare. Here, we characterize for the first-time host-associated algal communities of a mesophotic specialist coral species, Leptoseris cf. striatus , along the Saudi Arabian Red Sea coast. Methods We sampled 56 coral colonies spanning the eastern Red Sea coastline from the Northern Red Sea to the Farasan Banks in the South, and across two sampling periods, Fall 2020 and Spring 2022. We used Next Generation Sequencing of the ITS2 marker region in conjunction with SymPortal to denote algal assemblages. Results and discussion Our results show a relatively stable coral species-specific interaction with algae from the genus Cladocopium along the examined latitudinal gradient, with the appearance, in a smaller proportion, of presumed thermally tolerant algal taxa in the genera Symbiodinium and Durusdinium during the warmer season (Fall 2020). Contrary to shallow water corals, our results do not show a change in Symbiodiniaceae community composition from North to South in this mesophotic specialist species. However, our study highlights for the first time that symbiont communities are subject to change over time at mesophotic depth, which could represent an important phenomenon to address in future studies.

Anti-inflammatory and antiproliferative activity of Helichrysum odoratissimum Sweet. against lung cancer - Tenille Esmear; Danielle Twilley; Velaphi Clement Thipe; Kattesh V. Katti; Vusani Mandiwana; Michel Lonji Kalombo; Suprakas Sinha Ray; Rirhandzu Rikhotso-Mbungela; Venugopal Reddy Bovilla; SubbaRao Madhunapantula; Lenka Langhanshova; Catarina Roma-Rodrigues; et al. (South African Journal of Botany, 2024)

Pyrogenic carbon stocks are controlled by hydro-edaphic conditions in different forest types of the Northern Brazilian Amazon - Libério Junio da Silva; Lidiany Camila da Silva Oliveira; Gabriel Nuto Nóbrega; Dener Márcio S. Oliveira; Cleber Cunha Figueredo; Gabriel Rocha; Gabriel Souza Martins; Renato de Aragão R. Rodrigues; Reinaldo Imbrózio Barbosa; Renato Campello Cordeiro (CATENA, 2024)

Fluoxetine alters rat's milk properties causing impact on offspring's development - Gabriel R. Abreu; Julia Zaccarelli-Magalhães; Laís S. Féba; Emily Y. Penna; Julia P. Silva; Mariana V. Teixeira; Marianna Manes; Guilherme A. Vergara; Leonardo M.A. Rodrigues; André R. Fukushima; Esther L. Ricci; Helenice S. Spinosa (Toxicology and Applied Pharmacology, 2024)

Eucalyptus plantation reduces diversity and disrupts predator-prey correlations of soil invertebrates within Atlantic Forest - Felipe Martello; Wesley Dáttilo; Débora Rodrigues Souza-Campana; Hugo Reis Medeiros; Rogério R. Silva; Milton Cezar Ribeiro; Maria Santina C. Morini (Forest Ecology and Management, 2024)

Microrheological characterisation of Cyanoflan in human blood plasma - T. Rodrigues; R. Mota; L. Gales; P. Tamagnini; L. Campo-Deaño (Carbohydrate Polymers, 2024)

Effect of biomass burning emission on carbon assimilation over Brazilian Pantanal - Leone F. A. Curado; Sérgio R. de Paulo; Haline J. Araújo da Silva; Rafael S. Palácios; João B. Marques; Iramaia Jorge Cabral de Paulo; Higo José Dalmagro; Thiago Rangel Rodrigues (Theoretical and Applied Climatology, 2024)

Rainfall and rain pulse role on energy, water vapor and CO2 exchanges in a tropical semiarid environment - Cláudio M. Santos e Silva; Bergson G. Bezerra; Keila R. Mendes; Pedro R. Mutti; Daniele Tôrres Rodrigues; Gabriel Brito Costa; Pablo Eli Soares de Oliveira; Jean Reis; Thiago V. Marques; Rosaria Rodrigues Ferreira; Suany Campos; Tarsila M. Ramos; et al. (Agricultural and Forest Meteorology, 2024)

Detrimental impact of a heatwave on male reproductive behaviour and fertility - Afonso Grandela; Marta A. Antunes; Marta A. Santos; Margarida Matos; Leonor R. Rodrigues; Pedro Simões (acta ethologica, 2024)
Understanding how heatwaves impact on different aspects of mating behaviour and fertility is getting increasingly important. In this context, laboratory fertility and mating experiments involving manipulation and exposure of insects to different thermal conditions are common procedures. To conduct such experiments practical methods such as dyes are needed for an easy, non-invasive discrimination of individuals. We report here a study measuring the effect of an extended heat stress applied to males on several parameters of mating behaviour and fertility of laboratory populations of Drosophila subobscura derived from two distinct European locations. We found highly detrimental effects of heatwave on mating behaviour—with longer (courtship and copulation) latencies and lower mating occurrence but no changes in mating duration—and fertility, with reduced fecundity and reproductive success. Furthermore, we also tested the efficacy of food dye as a marker for individual discrimination and mating occurrence. While food dye did not allow to infer the occurrence of a mating based on a transfer of coloration from male to female, it did not affect mating and fertility, attesting its utility has a method for discriminating individuals within mating experiments in the context of thermal studies. Importantly, despite the fact that the heatwave was only applied in males, we observed an impact on behaviour of females that mated with stressed males, by often refusing their nuptial feeding. This opens possibilities for further integrated research on the changes of female and male mating behaviour and fertility under different thermal scenarios.

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Pest termite Cryptotermes havilandi (Sjöstedt, 1900) (Blattodea: Isoptera: Kalotermitidae) as an invasive species of natural ecosystems in northeastern Brazil - Renan Rodrigues Ferreira; Ricardo Koroiva; Flávia Maria S. Moura; Sara Rikeley Paulino Monteiro; Rozzanna Esther C. R. Figueirêdo; Matilde Vasconcelos Ernesto; Alexandre Vasconcellos (International Journal of Tropical Insect Science, 2024)

Experimental and Theoretical Investigation of the Effect of Cellulose Nanowhiskers on the Pb(II) Adsorption by Superabsorbent Hydrogel Nanocomposites - André R. Fajardo; Robson S. Oliboni; Carlos E. C. de Magalhães; Maria G. M. Chaves; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2024)

Enantioselectivity of pinene against Leishmania amazonensis - Ingrid S. Adão; Andreza R. Garcia; Kamila M. Sette; Camila M. Adade; Jefferson R. de Andrade Silva; Ana Claudia F. Amaral; Anderson S. Pinheiro; Igor A. Rodrigues (Medicinal Chemistry Research, 2024)

Effects of feeding mycotoxin-contaminated diets and the use of an adsorbent on the intake, digestibility, rumen fermentation, nitrogen balance and physiological parameters in the blood of Nellore steers - Luis Henrique C. Batista; Gustavo R. Siqueira; Luiz F. Costa e Silva; Anne Koontz; Yury T. Granja-Salcedo; Igor M. Ferreira; Iorrano A. Cidrini; Karla A. Oliveira; Amanda Caroliny M. de Queiroz; Aline N. Rodrigues; Flávio D. de Resende (Animal Feed Science and Technology, 2024)

Combined effects of Limonene and Ivermectin on P-glycoprotein-9 gene expression of lambs Infected with Haemonchus contortus - L.M. Katiki; R. Giglioti; J.F.S. Ferreira; P.A. Pacheco; H.Z. Barbosa; L. Rodrigues; C.J. Veríssimo; P.A.C. Braga; A.F.T. Amarante; H. Louvandini (Veterinary Parasitology, 2023)

Multivariate combined optimization strategy and comparative life-cycle assessment of biomass and plastic residues via microwave co-pyrolysis approach towards a sustainable synthesis of renewable hydrocarbon fuel - Dineshkumar Muniyappan; Guilherme Rodrigues Lima; Amaro Olimpio Pereira; R. Gopi; Anand Ramanathan (Journal of Environmental Chemical Engineering, 2023)

Solar photocatalysis using post-consumer alkaline batteries for degrading contaminants of emerging concern in surface water - Guenther Carlos C. Viana; Elisângela Maria R. Rocha; Elisandra Scapin; Arthur Cahino; Iris Rebeca D. Leite; Daniel A. Bertuol; José D. Ardisson; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Indole-3-carbinol and chlorogenic acid combination modulates gut microbiome and attenuates nonalcoholic steatohepatitis in a murine model - Gabriel P. Bacil; Guilherme R. Romualdo; Josias Rodrigues; Luís F. Barbisan (Food Research International, 2023)

Protocols for the seminal cryopreservation of South American catfishes – current status - Danilo P. Streit; Rômulo B. Rodrigues; Eduardo A. Sanches; Jayme A. Povh; Diógenes H. Siqueira-Silva; Thaíza R. de Freitas; Nathalia T. Santos; Jhony B. Lisboa; Thales S. França; Eduardo Nicoleti; Larise O.C. Lima; Tiantian Zhang (Cryobiology, 2023)

A meta-analytical review of turbidity effects on fish mobility - Jean N. Rodrigues; Jean C. G. Ortega; Danielle K. Petsch; Andre A. Padial; Dieison A. Moi; Bruno R. S. Figueiredo (Reviews in Fish Biology and Fisheries, 2023)

Chitosan with modified porosity and crosslinked with genipin: A dynamic system structurally characterized - Elí Emanuel Esparza-Flores; Larissa Bertoldo Siquiera; Fernanda Dias Cardoso; Tania Haas Costa; Edilson Valmir Benvenutti; Iliana E. Medina-Ramírez; Mercedes Perullini; Patricio R. Santagapita; Rafael C. Rodrigues; Plinho F. Hertz (Food Hydrocolloids, 2023)

Long-term memory in Staphylococcus aureus α-hemolysin ion channel kinetics - M. P. Silva; C. G. Rodrigues; D. C. Machado; R. A. Nogueira (European Biophysics Journal, 2023)

Metallothionein expression in the central nervous system in response to chronic heavy metal exposure: possible neuroprotective mechanism - A. Navarro-Sempere; P. Martínez-Peinado; A. S. Rodrigues; P. V. Garcia; R. Camarinho; G. Grindlay; L. Gras; M. García; Y. Segovia (Environmental Geochemistry and Health, 2023)
It has been reported that volcanoes release several tonnes of mercury per year among other heavy metals through eruptions, fumaroles, or diffuse soil degassing. Since a high percentage of the world's population lives in the vicinity of an active volcano, the aim of this study is to evaluate the accumulation of these metals in the central nervous system and the presence of cellular mechanisms of heavy metal detoxification such as metallothioneins. To carry out this study, wild mice (Mus musculus) chronically exposed to an active volcanic environment were captured in Furnas village (Azores, Portugal) and compared with those trapped in a reference area (Rabo de Peixe, Azores, Portugal). On the one hand, the heavy metal load has been evaluated by analyzing brain and cerebellum using ICP-MS and a mercury analyzer and on the other hand, the presence of metallothionein 2A has been studied by immunofluorescence assays. Our results show a higher load of metals such as mercury, cadmium and lead in the central nervous system of exposed mice compared to non-exposed individuals and, in addition, a higher immunoreactivity for metallothionein 2A in different areas of the cerebrum and cerebellum indicating a possible neuroprotection process.

How do intrinsic and extrinsic causes interact in the extinction vulnerability of South American savanna shrub and tree species? - Everton A. Maciel; Valéria Forni Martins; Roger Rodrigues Torres; Fernando R. Martins (Journal of Environmental Management, 2023)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

Fixed and volatile constituents of Acritopappus micropappus and their chemophenetics significance - Vanessa Rodrigues Guedes; Floricéa Magalhães Araújo; Hortensia Pousada Bautista; Paulo R. Ribeiro; Dirceu Martins (Biochemical Systematics and Ecology, 2023)

Effects of cyclic adenosine monophosphate modulating agents during oocyte pre-maturation and the role of melatonin on in vitro maturation of bovine cumulus-oocyte complexes - Bianca R. Silva; Laryssa G. Barrozo; Danisvânia R. Nascimento; Francisco C. Costa; Venância A.N. Azevedo; Laís R.F.M. Paulino; Everton P.F. Lopes; Ana L.P.S. Batista; Francisco L.N. Aguiar; Christina A. Peixoto; Mariana A.M. Donato; Ana P.R. Rodrigues; et al. (Animal Reproduction Science, 2023)

Effect of the combined use of monensin with virginiamycin or bacitracin on beef cattle performance, liver gluconeogenesis, lipid metabolism and intramuscular fat content - José M. Oliveira Júnior; Bruno G.C. Homem; Daniel Cunha; Ítalo B.G. Lima; Aline C. Rodrigues; Felipe C. Maciel; Edmilson H.R. Domingues; German D. Ramírez-Zamudio; Priscilla D. Teixeira; Tathyane R.S. Gionbelli; Matheus H. Moretti; Daniel R. Casagrande; et al. (Animal Feed Science and Technology, 2023)

Interactive effects of palladium (Pd) and microplastics (MPs) on metal bioaccumulation and biological responses in the Mediterranean mussel, Mytilus galloprovincialis - Joana Patrício Rodrigues; Juan Santos-Echeandía; Elena Chaves-Pozo; Juan Antonio Campillo; Teresa Rocha-Santos; Armando C. Duarte; José R. Rivera-Hernández; Juliana Valdés; Marina Albentosa (Marine Pollution Bulletin, 2023)

P26-16: Exosomes derived from mesenchymal stem cells exposed to hepatic injury signals reveal a distinct protein signature associated to pro-regenerative effects - A.S. Serras; S.P. Camões; J.S. Rodrigues; J.M. Vej-Nielsen; R. Vitorino; J.P. Miranda (Toxicology Letters, 2023)

P23-05: Urinary monohydroxyl-polycyclic aromatic hydrocarbons and metals in firefighters with active participation in controlled structure fires - J. Teixeira; R. Azevedo; A. Almeida; F. Rodrigues; A. Santos-Silva; C. Delerue-Matos; M. Oliveira (Toxicology Letters, 2023)

P06-04: Development of the TOXIN Knowledge Graph for assisting animal-free risk assessment of cosmetic ingredients - S. Sepehri; J. Maushagen; G. Vrijens; C. Debruyne; R. Marcelino Rodrigues; A. Sanctorum; O. De Troyer; T. Vanhaecke (Toxicology Letters, 2023)

P01-02: An updated adverse outcome pathway network on chemical-induced liver steatosis - A. Verhoeven; J. van Ertvelde; J. Boeckmans; A. Gatzios; R. Jover; B. Lindeman; G. Lopez Soop; R. Marcelino Rodrigues; A. Rapisarda; M. Stinckens; S. Sepehri; M. Vinken; et al. (Toxicology Letters, 2023)

Detection of Equus caballus Papillomavirus in Equine Aural Plaque Samples - Cristiana R. Bromberger; Julia Rodrigues Costa; Mariana Herman; Juliana Mira Hernandez; Lukas Garrido Albertino; Carlos Eduardo Fonseca Alves; Alexandre S. Borges; Jose P. Oliveira-Filho (Journal of Equine Veterinary Science, 2023)

On the quiet-time occurrence rates, severity and origin of L-band ionospheric scintillations observed from low-to-mid latitude sites located in Puerto Rico - J. Gomez Socola; J. Sousasantos; F.S. Rodrigues; C.G.M. Brum; P. Terra; A.O. Moraes; R. Eastes (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Influence of loading rates and feeding conditions on hybrid constructed wetlands integrated with microbial fuel cells - Gustavo S. Colares; Naira Dell'Osbel; Igor Conrad; Gabriele Paranhos; Sabrina B. Vaz; Gislayne Oliveira; Letícia Mesacasa; Deison Fochi; Odorico Konrad; Lucia R. Rodrigues; Carlos A. Lutterbeck; Adriane Lawisch Rodriguez; et al. (Ecological Engineering, 2023)

Different patterns of maize hybrids responses under variable phosphorus availability - R. E. Rodrigues; A. R. Neto; L. S. Jesus; L. T. M. Guedes; L. S. Santos; M. N. Xavier; L. A. Souza (Acta Physiologiae Plantarum, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Volcano-sedimentary interactions – A key to understand Cretaceous paleoenvironments in the Paraná basin (southern Brazil) - Fernando R. Rios; Ana M.P. Mizusaki; Cassiana R.L. Michelin; Isaque C. Rodrigues (Journal of South American Earth Sciences, 2023)

Zeolite associated with silicification in a volcano-sedimentary context, southern Brazil - Isaque C. Rodrigues; Ana M.P. Mizusaki; Glaucia N. Queiroga; Cassiana R.L. Michelin; Fernando R. Rios (Journal of South American Earth Sciences, 2023)

Volcanoclastic and epiclastic diagenesis of sandstones associated with volcano-sedimentary deposits from the upper Jurassic, Lower cretaceous, Paraná Basin, southern Brazil - Fernando R. Rios; Ana M.P. Mizusaki; Cassiana R.L. Michelin; Isaque C. Rodrigues (Journal of South American Earth Sciences, 2023)

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10 - Francisco C. S. Ferreira; Marco Clementino; Francisco A. P. Rodrigues; Herlice N. Veras; Dainesy S. Martins; Marcus L. Queiroga; Mikael A. Lima; Dayara O. Silva; Thiago M. de Freitas; Samilly A. Ribeiro; Mario R. L. Mota; James A. da Silva; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Body size and its correlates in fruit-feeding butterflies in a seasonal environment - Geraldo de Brito Freire; Danielle Salcido; Hernani F. M. Oliveira; Danilo B. Ribeiro; Diogo B. Provete; Thayane Silva; Joao Paulo Dias; Hanna P. Rodrigues; Jessie P. Santos; Ivone R. Diniz (Journal of Insect Conservation, 2023)

Removal of Reactive Dyes from a Real Bichromatic Textile Effluent Employing Bio-Based Nanomagnetic Adsorbents - Kátia C. H. Bezerra; Jacqueline R. Nascimento; Tiago D. Martins; Sherlan G. Lemos; Elma N. V. M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Water, Air, & Soil Pollution, 2023)

An exonuclease V homologue is expressed predominantly during early megasporogenesis in apomictic Brachiaria brizantha - Diva M. A. Dusi; Elizângela R. Alves; Gláucia B. Cabral; Luciane V. Mello; Daniel J. Rigden; Érica D. Silveira; Márcio Alves-Ferreira; Larissa A. Guimarães; Ana Cristina M. M. Gomes; Júlio C. M. Rodrigues; Vera T. C. Carneiro (Planta, 2023)

Komagataella pastoris KM71H Mitigates Depressive-Like Phenotype, Preserving Intestinal Barrier Integrity and Modulating the Gut Microbiota in Mice - Paloma T. Birmann; Angela M. Casaril; Ana Paula Pesarico; Rafael R. Rodrigues; Fabricio R. Conceição; Fernanda Severo Sabedra Sousa; Tiago Collares; Fabiana K. Seixas; Lucielli Savegnago (Molecular Neurobiology, 2023)

From ecological functions to ecosystem services: linking coastal lagoons biodiversity with human well-being - Jorge L. Rodrigues-Filho; Rafael L. Macêdo; Hugo Sarmento; Victor R. A. Pimenta; Cecilia Alonso; Clarissa R. Teixeira; Paulo R. Pagliosa; Sérgio A. Netto; Natália C. L. Santos; Fábio G. Daura-Jorge; Odete Rocha; Paulo Horta; et al. (Hydrobiologia, 2023)

Characterization of the organic micropollutants behavior during electrochemical ammonia recovery - Mariana Rodrigues; Malgorzata Roman; Annemiek ter Heijne; Tom Sleutels; Emile R. Cornelissen; Arne Verliefde; Cees J.N. Buisman; Philipp Kuntke (Journal of Environmental Chemical Engineering, 2023)

Correction to: Characterization of Portuguese sown rainfed grasslands using remote sensing and machine learning - Tiago G. Morais; Marjan Jongen; Camila Tufik; Nuno R. Rodrigues; Ivo Gama; David Fangueiro; João Serrano; Susana Vieira; Tiago Domingos; Ricardo F. M. Teixeira (Precision Agriculture, 2023)

A multi-dimensional non-homogeneous Markov chain of order K to jointly study multi-pollutant exceedances - Marco A. Gallegos-Herrada; Eliane R. Rodrigues; Mario H. Tarumoto; Guadalupe Tzintzun (Environmental and Ecological Statistics, 2023)
In this work we consider a multivariate non-homogeneous Markov chain of order $$K \ge 0$$ K ≥ 0 to study the occurrences of exceedances of environmental thresholds. In the model, $$d \ge 1$$ d ≥ 1 pollutants may be observed and, according to their respective environmental thresholds, a pollutant’s concentration measurement may be considered an exceedance or not. The parameters of the model are the order of the chain, and its initial and transition distributions. These parameters are estimated under the Bayesian point of view with the maximum a posteriori and leave-one-out cross validation methods used to estimate the order. In the case of the initial and transition probabilities, the estimation is made through samples generated using their respective posterior distributions. Once these parameters are obtained, we may estimate the probability of having no, one or more pollutants exceeding the associated environmental thresholds. This is made using the Markov property as well as a recurrence formula. Results are applied to the case where $$d = 2$$ d = 2 which will correspond to ozone and particulate matter with diameter smaller than 10 microns (PM $$_{10}$$ 10 ) measurements obtained from the Mexico City monitoring network.

Coexistence of two sympatric hermit crab species from South Brazil: the effect of the shell adequacy index and circadian movement patterns - Alexandre R. da Silva; Renan A. P. Santos; Gabriel F. B. Rodrigues; Neida R. Vieira; Bruna K. Baroni; Rafael A. Gregati (Aquatic Ecology, 2023)

Estimation of soluble solids content and fruit temperature in 'Rocha' pear using Vis-NIR spectroscopy and the SpectraNet–32 deep learning architecture - J.A. Martins; D. Rodrigues; A.M. Cavaco; M.D. Antunes; R. Guerra (Postharvest Biology and Technology, 2023)

Customized tissue microarray molds suitable for different histological workflows - J. De-Carvalho; J. Rodrigues-Lóios; A. Mindouro; R. Leite; P. Faísca (Journal of Comparative Pathology, 2023)

Monitoring the impacts of a mega-dam on Amazonian understorey herbs - Marcelo B. Medeiros; Washington L. Oliveira; Flávio R.O. Rodrigues; Renata D. Silva; Íris J.K. Ferreira; Wellyngton E. Ayala; Suelma R. Silva; Rafaela T. Souza; Marcelo F. Simon (Forest Ecology and Management, 2023)

Controlled lipid self-assembly for scalable manufacturing of next-generation immune stimulating complexes - Ivan S. Pires; Kaiyuan Ni; Mariane Bandeira Melo; Na Li; Elana Ben-Akiva; Laura Maiorino; Jonathan Dye; Kristen A. Rodrigues; DongSoo Yun; Byungji Kim; Ryan R. Hosn; Paula T. Hammond; et al. (Chemical Engineering Journal, 2023)

Interaction between sulfur and selenium in agronomic biofortification of cowpea plants under field conditions - Vinícius Martins Silva; Lolita Wilson; Scott D. Young; Martin R. Broadley; Philip J. White; André Rodrigues dos Reis (Plant and Soil, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

From the shallow to the mesophotic: a characterization of Symbiodiniaceae diversity in the Red Sea NEOM region - Tullia I. Terraneo; Mustapha Ouhssain; Carolina Bocanegra Castano; Manuel Aranda; Benjamin C. C. Hume; Fabio Marchese; Silvia Vimercati; Giovanni Chimienti; Ameer A. Eweida; Christian R. Voolstra; Burton H. Jones; Sam J. Purkis; et al. (Frontiers in Marine Science, 2023)
Introduction The northern Red Sea has been coined a refuge for reef corals due to the exceptional thermal tolerance of these organisms. With ocean warming threatening coral reefs worldwide, a panoptic characterization of corals living in extreme conditions may provide insights into future responses of corals to environmental change. Among other factors, the genotype of the endosymbiotic algae in the family Symbiodiniaceae has been shown to have major implications on the distribution and resilience of their coral hosts. In this study, we aim at genotyping the Symbiodiniaceae communities associated with three depth generalist and one depth specialist coral species, characterized by the ability to withstand environmental conditions that are apparently limiting for other corals and occurring in a unique geographical region. Methods We sampled 50 corals from the northern Saudi Arabian Red Sea and the Gulf of Aqaba, covering a 97 m bathymetric gradient. We used high-throughput ITS2 gene sequencing and recovered different patterns of host–algal associations. Results and discussion The majority of the recovered algal genotypes appeared host- and environment-specific, while others were more widely distributed. At large, coral specimens were overwhelmingly associated with symbionts from the genus Cladocopium and specifically with many previously undescribed genotypes. This suggests the selection of specific genotypes, which might confer resistance and/or resilience to their host counterparts. Interestingly, we found a limited association with Durusdinium spp. and other known tolerant taxa in mesophotic corals in the northern Red Sea, but not in the Gulf of Aqaba. The broad absence of Durusdinium spp., typically ascribed to be stress tolerant, warrants further investigation into Symbiodiniaceae species that convey environmental resilience. Our data will serve as a baseline to explore the occurrence of specific symbionts that might be contributing to coral acclimation and adaptation and to assay how biodiversity might be impacted if subjected to increasing stressors.

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

The inverted forest: Aboveground and notably large belowground carbon stocks and their drivers in Brazilian savannas - Marcela C.N.S. Terra; Matheus Henrique Nunes; Cleber R. Souza; Gabriel W.D. Ferreira; Jamir A. do Prado-Junior; Vanessa L. Rezende; Rafaella Maciel; Vanessa Mantovani; André Rodrigues; Vinícius Augusto Morais; José Roberto Soares Scolforo; José Marcio de Mello (Science of The Total Environment, 2023)

Limited impacts of the fungus Syncephalastrum on nests of leaf-cutting ants - Keminy R. Bautz; Marcela C.S. Caixeta; Nathalia P. Del Puppo; André Rodrigues; Thiago G. Kloss; Simon L. Elliot (Fungal Ecology, 2023)

Disinformation permeates Castro's reply to Rajão et al. (2022) - Raoni Rajão; Antonio Donato Nobre; Evandro L.T.P. Cunha; Tiago Ribeiro Duarte; Camilla Marcolino; Britaldo S. Soares-Filho; Gerd Sparovek; Ricardo R. Rodrigues; Carlos Valera; Mercedes Bustamante; Carlos Nobre; Letícia Santos de Lima (Biological Conservation, 2023)

The effects of exogenously applied antioxidants on plant growth and resilience - Aline Rodrigues de Queiroz; Connor Hines; Jeremy Brown; Seema Sahay; Jithesh Vijayan; Julie M. Stone; Nate Bickford; Melissa Wuellner; Katarzyna Glowacka; Nicole R. Buan; Rebecca L. Roston (Phytochemistry Reviews, 2023)
Plant growth and resilience require balancing an inherently oxidative metabolism with powerful antioxidant systems that help maintain homeostasis. When the environment changes, reactive oxygen species are potent indicators of that change, allowing adaptation through re-balancing metabolism and antioxidant systems. A large body of evidence supports the use of exogenously applied antioxidants to improve both plant growth and their resilience to stress. Notably, some phenotypic effects are similar upon the application of chemically diverse antioxidants, while others are distinct. In this review, we analyze research from antioxidant treatment experiments and highlight the similarities in their practical applications and their effects on plant stress tolerance, photosynthesis, native antioxidant systems, and phytohormones. We also briefly cover the specific effects of individually applied antioxidants and what is known about their potential modes of action. Given the strong potential of antioxidant applications, we discuss research needed to promote their agricultural use. Finally, we identify outstanding questions about how the exogenous application of antioxidants mechanistically affects plant growth.

Nitrogen fate during agricultural managed aquifer recharge: Linking plant response, hydrologic, and geochemical processes - Elad Levintal; Laibin Huang; Cristina Prieto García; Adolfo Coyotl; Matthew W. Fidelibus; William R. Horwath; Jorge L. Mazza Rodrigues; Helen E. Dahlke (Science of The Total Environment, 2023)

Increased ATP Release and Higher Impact of Adenosine A2A Receptors on Corticostriatal Plasticity in a Rat Model of Presymptomatic Parkinson’s Disease - Francisco Q. Gonçalves; Filipe C. Matheus; Henrique B. Silva; Joana I. Real; Daniel Rial; Ricardo J. Rodrigues; Jean-Pierre Oses; António C. Silva; Nélio Gonçalves; Rui D. Prediger; Ângelo R. Tomé; Rodrigo A. Cunha (Molecular Neurobiology, 2023)
Extracellular ATP can be a danger signal, but its role in striatal circuits afflicted in Parkinson’s disease (PD) is unclear and was now investigated. ATP was particularly released at high stimulation intensities from purified striatal nerve terminals of mice, which were endowed with different ATP-P2 receptors (P2R), although P2R antagonists did not alter corticostriatal transmission or plasticity. Instead, ATP was extracellularly catabolized into adenosine through CD73 to activate adenosine A 2A receptors (A 2A R) modulating corticostriatal long-term potentiation (LTP) in mice. In the presymptomatic phase of a 6-hydroxydopamine rat model of PD, ATP release from striatal nerve terminals was increased and was responsible for a greater impact of CD73 and A 2A R on corticostriatal LTP. These observations identify increased ATP release and ATP-derived formation of extracellular adenosine bolstering A 2A R activation as a key pathway responsible for abnormal synaptic plasticity in circuits involved in the onset of PD motor symptoms. The translation of these findings to humans prompts extending the use of A 2A R antagonists from only co-adjuvants of motor control in Parkinsonian patients to neuroprotective drugs delaying the onset of motor symptoms.

Neuroinflammation in Alzheimer’s disease: potential beneficial effects of vitamin D - Bruna R. Kouba; Anderson Camargo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2023)

Methyl benzoate and nerolidol attract the cyclocephaline beetle Cyclocephala paraguayensis to trumpet flowers - Arodí P. Favaris; Amanda C. Túler; Weliton D. Silva; Marvin Pec; Sérgio R. Rodrigues; Artur C. D. Maia; José Maurício S. Bento (The Science of Nature, 2023)

Characterization of portuguese sown rainfed grasslands using remote sensing and machine learning - Tiago G. Morais; Marjan Jongen; Camila Tufik; Nuno R. Rodrigues; Ivo Gama; David Fangueiro; João Serrano; Susana Vieira; Tiago Domingos; Ricardo F.M. Teixeira (Precision Agriculture, 2023)

Trichoderma as a powerful fungal disease control agent for a more sustainable and healthy agriculture: recent studies and molecular insights - Amanda O. Rodrigues; Louise L. May De Mio; Carlos R. Soccol (Planta, 2023)

The antidepressant-like effect elicited by vitamin D3 is associated with BDNF/TrkB-related synaptic protein synthesis - Bruna R. Kouba; Ana Clara N. C. Torrá; Anderson Camargo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2023)

Endotoxin tolerance and low activation of TLR-4/NF-κB axis in monocytes of COVID-19 patients - Gilson P. Dorneles; Paula C. Teixeira; Alessandra Peres; Luiz Carlos Rodrigues Júnior; Simone Gonçalves da Fonseca; Marta Chagas Monteiro; Sarah Eller; Tiago F. Oliveira; Eliana M. Wendland; Pedro R. T. Romão (Journal of Molecular Medicine, 2023)

Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - João L. Guilherme; Victoria R. Jones; Inês Catry; Martin Beal; Maria P. Dias; Steffen Oppel; Juliet A. Vickery; Chris M. Hewson; Stuart H. M. Butchart; Ana S. L. Rodrigues (Conservation Biology, 2023)
The conservation of long‐distance migratory birds requires coordination between the multiple countries connected by the movements of these species. The recent expansion of tracking studies is shedding new light on these movements, but much of this information is fragmented and inaccessible to conservation practitioners and policy makers. We synthesized current knowledge on the connectivity established between countries by landbirds and raptors migrating along the African–Eurasian flyway. We reviewed tracking studies to compile migration records for 1229 individual birds, from which we derived 544 migratory links, each link corresponding to a species’ connection between a breeding country in Europe and a nonbreeding country in sub‐Saharan Africa. We used these migratory links to analyze trends in knowledge over time and spatial patterns of connectivity per country (across species), per species (across countries), and at the flyway scale (across all countries and all species). The number of tracking studies available increased steadily since 2010 (particularly for landbirds), but the coverage of existing tracking data was highly incomplete. An average of 7.5% of migratory landbird species and 14.6% of raptor species were tracked per country. More data existed from central and western European countries, and it was biased toward larger bodied species. We provide species‐ and country‐level syntheses of the migratory links we identified from the reviewed studies, involving 123 populations of 43 species, migrating between 28 European and 43 African countries. Several countries (e.g., Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for future tracking studies to complement existing data, particularly on landbirds. Despite the limitations in existing tracking data, our data and results can inform discussions under 2 key policy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia.

Microplastic contamination in large migratory fishes collected in the open Atlantic Ocean - Rúben Pereira; Sabrina M. Rodrigues; Diogo Silva; Vânia Freitas; C. Marisa R. Almeida; Sandra Ramos (Marine Pollution Bulletin, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Impacts of the use of biological pest control on the technical efficiency of the Brazilian agricultural sector - L. C. C. Rodrigues; R. M. Fortini; M. C. R. Neves (International Journal of Environmental Science and Technology, 2023)

Post-earthquake damage classification and assessment: case study of the residential buildings after the Mw = 5 earthquake in Mila city, Northeast Algeria on August 7, 2020 - Hamidatou Mouloud; Amar Chaker; Hallal Nassim; Saad Lebdioui; Hugo Rodrigues; Matthew R. Agius (Bulletin of Earthquake Engineering, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Diversification of the Pristimantis conspicillatus group (Anura: Craugastoridae) within distinct neotropical areas throughout the Neogene - Antoine Fouquet; Alexandre Réjaud; Miguel T. Rodrigues; Santiago R. Ron; Juan C. Chaparro; Mariela Osorno; Fernanda P. Werneck; Tomas Hrbek; Albertina P. Lima; Teresa Camacho-Badani; Andres F. Jaramillo-Martinez; Jérôme Chave (Systematics and Biodiversity, 2022)

Species diversity and systematics of the Leptodactylus melanonotus group (Anura, Leptodactylidae): review of diagnostic traits and a new species from the Eastern Guiana Shield - Thiago R. Carvalho; Antoine Fouquet; Mariana L. Lyra; Ariovaldo A. Giaretta; C. Eduardo Costa-Campos; Miguel T. Rodrigues; Célio F. B. Haddad; Santiago R. Ron (Systematics and Biodiversity, 2022)

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Narratives of Positionality in Primatology: Foreign/Range–Country Collaborator Perspectives from Africa and South America - Michelle A. Rodrigues; Vicent Kiiza; Matthew R. McLennan; Sérgio L. Mendes; Karen B. Strier (International Journal of Primatology, 2022)

Response of benthic dinoflagellates Amphidinium carterae and Bysmatrum gregarium to salinity changes and prolonged darkness: elucidation through laboratory experiments - R. V. Rodrigues; J. S. Patil (Aquatic Ecology, 2022)

Sexual segregation in the foraging distribution, behaviour, and trophic niche of the endemic Boyd’s shearwater (Puffinus lherminieri boydi) - Ivo dos Santos; Jaime A. Ramos; Filipe R. Ceia; Isabel Rodrigues; Nathalie Almeida; Stefan Antunes; Ana R. Carreiro; Diana M. Matos; Ricardo J. Lopes; Pedro Geraldes; Vítor H. Paiva (Marine Biology, 2022)

Behavioural responses of a cold-water benthivore to loss of oxythermal habitat - Tazi H. Rodrigues; Andrew J. Chapelsky; Lee E. Hrenchuk; Graham R. Mushet; Lauren J. Chapman; Paul J. Blanchfield (Environmental Biology of Fishes, 2022)
Climate-driven declines in oxythermal habitat in freshwater lakes can impose prolonged constraints on cold-water fishes sensitive to hypoxia. How fish cope with severe habitat limitations is not well understood, yet has implications for their persistence. Here, we use acoustic-positioning telemetry to assess seasonal habitat occupancy and activity patterns of lake whitefish ( Coregonus clupeaformis ), a cold-water benthivore, in a small boreal lake that regularly faces severe oxythermal constraints during summer stratification. During this stratified period, they rarely (< 15% of detections) occupied depths with water temperatures > 10 °C (interquartile range = 5.3–7.9 °C), which resulted in extensive use (> 90% of detections) of water with < 4 mg L −1 dissolved oxygen (DO; interquartile range = 0.3–5.3 mg L −1 ). Lake whitefish were least active in winter and spring, but much more active in summer, when only a small portion of the lake (1–10%) contained optimal oxythermal habitat (< 10 °C and > 4 mg L −1 DO), showing frequent vertical forays into low DO environments concurrent with extensive lateral movement (7649 m d −1 ). High rates of lateral movement (8392 m d −1 ) persisted in the complete absence of optimal oxythermal habitat, but without high rates of vertical forays. We found evidence that lake whitefish are more tolerant of hypoxia (< 2 mg L −1 ) than previously understood, with some individuals routinely occupying hypoxic habitat in winter (up to 93% of detections) despite the availability of higher DO habitat. The changes in movement patterns across the gradient of habitat availability indicate that the behavioural responses of lake whitefish to unfavourable conditions may lead to changes in foraging efficiency and exposure to physiological stress, with detrimental effects on their persistence.

Hyperglycemia alters N-glycans on colon cancer cells through increased production of activated monosaccharides - H. F. Loponte; I. A. Oliveira; B. C. Rodrigues; R. Nunes-da-Fonseca; R. Mohana-Borges; F. Alisson-Silva; W. B. Dias; A. R. Todeschini (Glycoconjugate Journal, 2022)

Small mammal diversity of a poorly known and threatened Amazon region, the Tapajós Area of Endemism - Joyce Rodrigues do Prado; Rita G. Rocha; Heitor Bissoli-Silva; Ana Cristina Mendes-Oliveira; Regeane C. L. Pontes; Paula Cristina R. de A Maués; Leonora Pires Costa (Biodiversity and Conservation, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Seasonal approach to forecast the suitability of spawning habitats of a temperate small pelagic fish under a high-emission climate change scenario - André R. A. Lima; Susana Garrido; Isabel Riveiro; Diana Rodrigues; Maria M. P. Angélico; Emanuel J. Gonçalves; Myron A. Peck; Gonçalo Silva (Frontiers in Marine Science, 2022)
Spawning habitats of cold-water, European small pelagic fishes have shifted poleward in the last three decades coincident with gradual ocean warming. We predicted present-day, season-specific habitat suitability for spawning by European sardine Sardina pichardus in the Atlantic Ocean and Mediterranean and Black Seas, and projected climate-driven changes in suitable areas from 2050-2099 under the IPCC – RCP 8.5 scenario. Sea surface temperature and distance to the coast had the greater influences in spawning habitats, reflecting the temperature- and coastal-dependent spawning of sardines. Chlorophyll- a was the third most important explanatory variable for spawning in winter to summer. Winds were predominantly important during autumn, whilst sea surface salinity was an important driver during spring and summer. Present-day, “hotspots” for spawning were identified in regions of highly productive, salty waters, where SST was between 6 and 18°C from autumn to spring or 16 and 25°C during summer and favourable winds occurred that would retain eggs and larvae closer to the coast (< 250 km). For future scenarios, forecasts indicate that environmental optima for spawning is projected to be in regions where SST varies between 11°C and 18°C from autumn to spring; and between 18°C and 24°C during summer. However, a negative relationship between phytoplankton productivity and habitat suitability induced by warming is likely to occur in the future. Projections suggest that suitable spawning habitats in all seasons will shift to higher latitudes, with a prominent range expansion along the coast of Norway during winter and autumn (> 83%). The total spawning area, however, was projected to contract in the future during spring (-10.5%) and autumn (-4.1%) due to losses of currently suitable areas along the Atlantic African Coast and Mediterranean Sea. Such regions currently support the greatest sardine stocks but climate-driven warming and decreased plankton productivity are projected to make these areas unsuitable for spawning and likely also for sardine fisheries in future.

Sugarcane: A Promising Source of Green Carbon in the Circular Bioeconomy - Susan G. Karp; Walter J. M. Burgos; Luciana P. S. Vandenberghe; Kim V. Diestra; Luis A. Z. Torres; Adenise L. Woiciechowski; Luiz A. J. Letti; Gilberto V. M. Pereira; Vanete Thomaz-Soccol; Cristine Rodrigues; Júlio C. de Carvalho; Carlos R. Soccol (Sugar Tech, 2022)

Epithelial morphometric alterations and mucosecretory responses in the nasal cavity of mice chronically exposed to hydrothermal emissions - R. Camarinho; A. Madrero Pardo; P. V. Garcia; A. S. Rodrigues (Environmental Geochemistry and Health, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

A systematic analysis of climate model precipitation in southern Brazil - Maria Fernanda R. Pereima; Pedro L. B. Chaffe; Pablo Borges de Amorim; Regina R. Rodrigues (International Journal of Climatology, 2022)
Climate model precipitation is the foremost input for hydrological models in climate change risk assessment. However, some aspects of precipitation (e.g., frequency, seasonality, and extremes) are usually not well represented by climate models, especially at the regional scale and in the tropics. In this study, we use a set of well‐established metrics to evaluate the marginal, temporal, and spatial aspects of CMIP5 and CMIP6 precipitation in Southern Brazil. This region is in the transition between tropical and subtropical climates with diverse rainfall generation mechanisms and complex topography. We compare the multi‐model‐ensemble mean (MME) and a constrained ensemble (CE) of CMIP5 and CMIP6 against a high‐resolution precipitation data grid. The constrained ensemble is obtained using a weighting approach that minimizes the difference between the simulated and observed cumulative distribution functions. We find that CMIP6 outperforms CMIP5 for most metrics, especially in the simulation of the seasonal cycle and the spatial distribution of precipitation. Simulated precipitation is more seasonal and more spatially dependent than the observations, with a dry bias characterized by lower precipitation amounts and higher consecutive dry days. Our analysis suggests that the models are not able to reproduce the transition between tropical and subtropical climates in this region as well as the passage of frontal systems. Future studies using CMIP6 should focus on those regional mechanisms of precipitation variability.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Occurrence of Volcanogenic Inorganic Mercury in Wild Mice Spinal Cord: Potential Health Implications - A. Navarro-Sempere; M. García; A. S. Rodrigues; P. V. Garcia; R. Camarinho; Y. Segovia (Biological Trace Element Research, 2022)
Mercury accumulation has been proposed as a toxic factor that causes neurodegenerative diseases. However, the hazardous health effects of gaseous elemental mercury exposure on the spinal cord in volcanic areas have not been reported previously in the literature. To evaluate the presence of volcanogenic inorganic mercury in the spinal cord, a study was carried out in São Miguel island (Azores, Portugal) by comparing the spinal cord of mice exposed chronically to an active volcanic environment (Furnas village) with individuals not exposed (Rabo de Peixe village), through the autometallographic silver enhancement histochemical method. Moreover, a morphometric and quantification analysis of the axons was carried out. Results exhibited mercury deposits at the lumbar level of the spinal cord in the specimens captured at the site with volcanic activity (Furnas village). A decrease in axon calibre and axonal atrophy was also observed in these specimens. Given that these are relevant hallmarks in the neurodegenerative pathologies, our results highlight the importance of the surveillance of the health of populations chronically exposed to active volcanic environments.

Optical time series for the separation of land cover types with similar spectral signatures: cocoa agroforest and forest - João E. Batista; Nuno M. Rodrigues; Ana I. R. Cabral; Maria J. P. Vasconcelos; Adriano Venturieri; Luiz G. T. Silva; Sara Silva (International Journal of Remote Sensing, 2022)

Foraging costs drive within-colony spatial segregation in shearwaters from two contrasting environments in the North Atlantic Ocean - Jorge M. Pereira; Jaime A. Ramos; Nathalie Almeida; Pedro M. Araújo; Filipe R. Ceia; Pedro Geraldes; Ana M. Marques; Diana M. Matos; Isabel Rodrigues; Ivo dos Santos; Vitor H. Paiva (Oecologia, 2022)

Attraction of whitefly Aleurodicus cocois mediated by cashew volatiles - Wenner V. A. Saraiva; Nívia S. Dias-Pini; Elenilson G. Alves Filho; José W. S. Melo; Marilene Fancelli; Cristiane R. Coutinho; Guilherme J. Zocolo; Tigressa H. S. Rodrigues; Poliana M. Duarte; Vitor H. M. Macedo; Elaine S. S. Goiana (Phytoparasitica, 2022)

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Economic potential comparative of reusing different industrial solid wastes in cementitious composites: a case study in Brazil - Afonso R. G. de Azevedo; Alan Marinho Costa; Daiane Cecchin; Carlos Rodrigues Pereira; Markssuel Teixeira Marvila; Adeyemi Adesina (Environment, Development and Sustainability, 2022)

Light and thermal niches of ground‐foraging A mazonian insectivorous birds - Vitek Jirinec; Patricia F. Rodrigues; Bruna R. Amaral; Philip C Stouffer (Ecology, 2022)
Insectivores of the tropical rainforest floor are consistently among the most vulnerable birds to forest clearing and fragmentation. Several hypotheses attempt to explain this pattern, including sensitivity to extreme microclimates found near forest borders, particularly brighter and warmer conditions. Importantly, this “microclimate hypothesis” has additional implications for intact forest under global climate change that could be evaluated through direct assessment of the light and temperature environment of terrestrial insectivores. In this study, we harness novel technology to directly quantify the light and thermal niches of 10 species of terrestrial insectivores in undisturbed Amazonian rainforest. Loggers placed on birds ( N = 33) and their environment ( N = 9) recorded nearly continuous microclimate data from 2017 to 2019, amassing >5 million measurements. We found that midday light intensity in tree fall gaps (~39,000 lux) was >40 times higher than at the ground level of forest interior (950 lux). Light intensity registered by sensors placed on birds averaged 17.4 (range 3.9–41.5) lux, with species using only 4.3% (0.9%–10.4%) of available light on the forest floor. Birds therefore selected very dark microhabitats—the light environment was >2200 times brighter in tree fall gaps. Bird thermal niche was a function of ambient temperature as well as body temperature, which averaged >40.5°C but varied among species. Forest floor temperature peaked daily at 27.0°C, whereas bird loggers averaged 35.1°C (34.5–35.7°C) at midday. The antpitta Myrmothera campanisona and the antthrush Formicarius colma used thermal conditions closest to their body temperatures, whereas leaftossers ( Sclerurus spp.) and Myrmornis torquata occupied relatively cool microclimates. We found no general link between abundance trends and variation in species‐specific light and thermal niches. However, all species occupied markedly dim and cool microclimates. Because such conditions are rare outside the interior of primary forest, these results support the microclimate hypothesis in disturbed landscapes. Moreover, strong avoidance of conditions that are becoming more common under climate change highlights the vulnerability of terrestrial insectivores even in the absence of disturbance and may be the reason for enigmatic declines in Amazonia and elsewhere.

NeoBat Interactions: A data set of bat–plant interactions in the Neotropics - Guillermo L. Florez‐Montero; Renata L. Muylaert; Marcelo R. Nogueira; Cullen Geiselman; Sharlene E. Santana; Richard D. Stevens; Marco Tschapka; Francisco A. Rodrigues; Marco A. R. Mello (Ecology, 2022)
Data papers and open databases have revolutionized contemporary science, as they provide the long‐needed incentive to collaborate in large international teams and make natural history information widely available. Nevertheless, most data papers have focused on species occurrence or abundance, whereas interactions have received much less attention. To help fill this gap, we have compiled a georeferenced data set of interactions between 93 bat species of the family Phyllostomidae (Chiroptera) and 501 plant species of 68 families. Data came from 169 studies published between 1957 and 2007 covering the entire Neotropical Region, with most records from Brazil (34.5% of all study sites), Costa Rica (16%), and Mexico (14%). Our data set includes 2571 records of frugivory (75.1% of all records) and nectarivory (24.9%). The best represented bat genera are Artibeus (28% of all records), Carollia (24%), Sturnira (10.1%), and Glossophaga (8.8%). Carollia perspicillata (187), Artibeus lituratus (125), Artibeus jamaicensis (94), Glossophaga soricina (86), and Artibeus planirostris (74) were the bat species with the broadest diets recorded based on the number of plant species. Among the plants, the best represented families were Moraceae (17%), Piperaceae (15.4%), Urticaceae (9.2%), and Solanaceae (9%). Plants of the genera Cecropia (46), Ficus (42), Piper (40), Solanum (31), and Vismia (27) exhibited the largest number of interactions. These data are stored as arrays (records, sites, and studies) organized by logical keys and rich metadata, which helped to compile the information on different ecological and geographic scales, according to how they should be used. Our data set on bat–plant interactions is by far the most extensive, both in geographic and taxonomic terms, and includes abiotic information of study sites, as well as ecological information of plants and bats. It has already facilitated several studies and we hope it will stimulate novel analyses and syntheses, in addition to pointing out important gaps in knowledge. Data are provided under the Creative Commons Attribution 4.0 International License. Please cite this paper when the data are used in any kind of publication related to research, outreach, and teaching activities.

Onset and demise dates of the rainy season in the South American monsoon region: A cluster analysis result - Maria A. M. Rodrigues; Sâmia R. Garcia; Mary T. Kayano; Alan J. P. Calheiros; Rita V. Andreoli (International Journal of Climatology, 2022)
This work proposes an adaptation of the method developed in previous papers to determine the onset and demise of the rainy season (ONR and DER) dates in the areas of the South American monsoon system (SAMS) based on the pentad antisymmetric outgoing long‐wave radiation (AOLR). In those papers, the sign change of the mean AOLR in the central Amazon Basin (CAM) and western central Brazil (WCB) from positive to negative defined the ONR, from negative to positive, the DER dates. Since the monsoon convection presents a northwest–southeast oriented progression, the antisymmetric area to the WCB was selected subjectively. Thus, here we propose to use the Ward hierarchical clustering method to select areas in the SAMS and in the northern tropical America (NTA) for the regionalized AOLR calculation. The significant (at the 95% confidence level) negative correlations with the largest magnitude among the clusters in the SAMS and NTA and the outgoing long‐wave radiation (OLR) and precipitation annual cycles in each group define the pairs to calculate the AOLR. Then, the AOLR time series is calculated and subjected to a 5‐pentad running mean filter. This method keeps the climatological features of the convection annual cycle such that the closer (farther) the pair is to the equator the longer (shorter) the rainy season. The ONR and DER dates found with this new method are remarkably close to those found previously. Therefore, the new method proposed here highlights regional aspects of rainy season and can easily be automatized for its routine application at the operational climate monitoring centres, for instance at INPE. This is the most important advantage of the method and might be relevant to the SAMS rainy season monitoring.

Hybrid constructed wetlands integrated with microbial fuel cells and reactive bed filter for wastewater treatment and bioelectricity generation - Gustavo Stolzenberg Colares; Naira Dell’Osbel; Gabriele Paranhos; Patrícia Cerentini; Gislayne A. Oliveira; Elizandro Silveira; Lúcia R. Rodrigues; Jocelene Soares; Carlos A. Lutterbeck; Adriane Lawisch Rodriguez; Jan Vymazal; Ênio L. Machado (Environmental Science and Pollution Research, 2022)

Pharmacological blockage of the AHR-CYP1A1 axis: a call for in vivo evidence - N. R. Coelho; A. B. Pimpão; M. J. Correia; T. C. Rodrigues; E. C. Monteiro; J. Morello; S. A. Pereira (Journal of Molecular Medicine, 2022)

Manganese(I) tricarbonyl complexes as potential anticancer agents - Oscar A. Lenis-Rojas; Beatriz Carvalho; Rui Cabral; Margarida Silva; Sofia Friães; Catarina Roma-Rodrigues; Marta S. H. Meireles; Clara S. B. Gomes; Jhonathan A. A. Fernández; Sabela F. Vila; Juan A. Rubiolo; Laura Sanchez; et al. (JBIC Journal of Biological Inorganic Chemistry, 2022)

Metformin effect in models of inflammation is associated with activation of ATP-dependent potassium channels and inhibition of tumor necrosis factor-α production - Paulo S. A. Augusto; Tamires C. Matsui; Alysson V. Braga; Felipe F. Rodrigues; Marcela I. Morais; Marcela M. G. B. Dutra; Carla R. A. Batista; Ivo S. F. Melo; Sarah O. A. M. Costa; Caryne M. Bertollo; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2022)

Climate and management effects on the herbaceous layer productivity of a cork oak woodland - M. C. Bicho; A. C. Correia; A. R. Rodrigues; J. Soares David; F. Costa-e-Silva (Agroforestry Systems, 2022)

A new species of Hoplias malabaricus species complex ( Characiformes: Erythrinidae ) from the Crepori River , Amazon basin, Brazil - Karen L. A. Guimarães; Juan J. Rosso; Mariano González‐Castro; Mendelsohn F. B. Souza; Juan M. Díaz de Astarloa; Luís R. R. Rodrigues (Journal of Fish Biology, 2022)
A new species belonging to the Hoplias malabaricus complex from the Amazon basin, Brazil, is described. The new species is characterized by 15–16 predorsal scales, 37–39 lateral‐line scales, 5 scales from dorsal fin to lateral line, 38–39 vertebrae, iii‐iv, 7–8 anal‐fin rays, ii‐iv, 12–15 caudal‐fin rays, last vertical series of scales on the base of caudal‐fin rays forming a straight line, 6–7 dark bands in anal fin and no distinctive dark bands or blotches on flanks. The new species is also distinguished from other congeners of the H. malabaricus species‐group by means of landmark‐based morphometrics and DNA Barcoding ( Cytochrome c Oxidase I gene ). An identification key to species of the H. malabaricus species complex is provided.

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

The 2019 Benguela Niño - Rodrigue Anicet Imbol Koungue; Peter Brandt; Joke Lübbecke; Arthur Prigent; Meike Sena Martins; Regina R. Rodrigues (Frontiers in Marine Science, 2021)
High interannual sea surface temperature anomalies of more than 2°C were recorded along the coasts of Angola and Namibia between October 2019 and January 2020. This extreme coastal warm event that has been classified as a Benguela Niño, reached its peak amplitude in November 2019 in the Angola Benguela front region. In contrast to classical Benguela Niños, the 2019 Benguela Niño was generated by a combination of local and remote forcing. In September 2019, a local warming was triggered by positive anomalies of near coastal wind-stress curl leading to downwelling anomalies through Ekman dynamics off Southern Angola and by anomalously weak winds reducing the latent heat loss by the ocean south of 15°S. In addition, downwelling coastal trapped waves were observed along the African coast between mid-October 2019 and early January 2020. Those coastal trapped waves might have partly emanated from the equatorial Atlantic as westerly wind anomalies were observed in the central and eastern equatorial Atlantic between end of September to early December 2019. Additional forcing for the downwelling coastal trapped waves likely resulted from an observed weakening of the prevailing coastal southerly winds along the Angolan coast north of 15°S between October 2019 and mid-February 2020. During the peak of the event, latent heat flux damped the sea surface temperature anomalies mostly in the Angola Benguela front region. In the eastern equatorial Atlantic, relaxation of cross-equatorial southerly winds might have contributed to the equatorial warming in November 2019 during the peak of the 2019 Benguela Niño. Moreover, for the first time, moored velocities off Angola (11°S) revealed a coherent poleward flow in the upper 100 m in October and November 2019 suggesting a contribution of meridional heat advection to the near-surface warming during the early stages of the Benguela Niño. During the Benguela Niño, a reduction of net primary production in the Southern Angola and Angola Benguela front regions was observed.

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Production and bioaccessibility of Emiliania huxleyi biomass and bioactivity of its aqueous and ethanolic extracts - B. Vicente; J. Matos; R. Gomes; M. Sapatinha; Cláudia Afonso; T. Rodrigues; A. Amorim; N. M. Bandarra; Carlos Cardoso (Journal of Applied Phycology, 2021)

Floating treatment wetland for nutrient removal and acute ecotoxicity improvement of untreated urban wastewater - L. H. Bauer; A. Arenzon; N. D. Molle; J. A. Rigotti; A. C. A. Borges; N. R. Machado; L. H. R. Rodrigues (International Journal of Environmental Science and Technology, 2021)

Correction to: Seismic fragility functions for Portuguese RC precast buildings - R. Sousa; N. Batalha; V. Silva; H. Rodrigues (Bulletin of Earthquake Engineering, 2021)

Seismic fragility functions for Portuguese RC precast buildings - R. Sousa; N. Batalha; V. Silva; H. Rodrigues (Bulletin of Earthquake Engineering, 2021)

In vitro enzyme inhibitory and anti-oxidant properties, cytotoxicity and chemical composition of the halophyte Malcolmia littorea (L.) R.Br. (Brassicaceae) - Viana Castañeda-Loaiza; Chloé Placines; Maria João Rodrigues; Catarina G. Pereira; Gokhan Zengin; Nuno R. Neng; José M. F. Nogueira; Luísa Custódio (Natural Product Research, 2021)

Whiptail lizard lineage delimitation and population expansion as windows into the history of Amazonian open ecosystems - Lidia F. Martins; Erik L. Choueri; Alan F. S. Oliveira; Fabrícius M. C. B. Domingos; Gabriel H. O. Caetano; Vitor H. G. L. Cavalcante; Rafael N. Leite; Antoine Fouquet; Miguel T. Rodrigues; Ana C. Carnaval; Guarino R. Colli; Fernanda P. Werneck (Systematics and Biodiversity, 2021)

Dopaminergic Receptors as Neuroimmune Mediators in Experimental Autoimmune Encephalomyelitis - E. C. D. Gonçalves; V. Lieberknecht; V. V. Horewicz; B. D. Rabelo; F. A. Felipetti; A. L. S. Rodrigues; D. F. Martins; R. C. Dutra (Molecular Neurobiology, 2021)

Chronic exposure to volcanic gaseous elemental mercury: using wild Mus musculus to unveil its uptake and fate - R. Camarinho; A. Navarro-Sempere; P. V. Garcia; M. García; Y. Segovia; A. S. Rodrigues (Environmental Geochemistry and Health, 2021)

Microencapsulated Lemongrass ( Cymbopogon flexuosus ) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage - Cristine Rampelotto; Caroline S. Speroni; Lisiane Conte; Dirleise Pianesso; Isadora S. Machado; Renata F. Rodrigues; Natália M. Minuzzi; Taida J. Adorian; Bruna Klein; Roger Wagner; Bernardo Baldisserotto; Leila P. da Silva; et al. (Journal of Aquatic Food Product Technology, 2021)

Tropical grass and legume pastures may alter lamb meat physical and chemical characteristics - V. S. Hampel; C. H. E. C. Poli; M. Joy; J. F. Tontini; T. Devincenzi; J. R. B. Pardos; R. E. F. Macedo; E. N. Nalério; A. G. F. Saccol; E. Rodrigues; V. Manfroi; N. M. Fajardo (Tropical Animal Health and Production, 2021)

Combining regional to local restoration goals in the Brazilian Atlantic forest - Cassia M.G. Lemos; Pedro R. Andrade; Ricardo R. Rodrigues; Leticia Hissa; Ana P. D. Aguiar (Regional Environmental Change, 2021)
To achieve regional and international large-scale restoration goals with minimum costs, several restoration commitments rely on natural regeneration, a passive and inexpensive strategy. However, natural regeneration potential may vary within the landscape, mainly due to its historical context. In this work, we use spatially explicit restoration scenarios to explore how and where, within a given region, multiple restoration commitments could be combined to achieve cost-effectiveness outcomes. Our goal is to facilitate the elaboration of forest restoration plans at the regional level, taking into consideration the costs for active and passive restoration methods. The approach includes (1) a statistical analysis to estimate the natural regeneration potential for a given area based on alternative sets of biophysical, land cover, and/or socioeconomic factors and (2) the use of a land change allocation model to explore the cost-effectiveness of combining multiple restoration commitments in a given area through alternative scenarios. We test our approach in a strategic region in the Brazilian Atlantic Forest Biome, the Paraiba Valley in São Paulo State. Using the available data for 2011, calibrated for 2015, we build alternative scenarios for allocating natural regeneration until 2025. Our models indicate that the natural regeneration potential of the region is actually very low, and the cost-effectiveness outcomes are similar for all scenarios. We believe our approach can be used to support the regional-level decision-making about the implementation of multiple commitments aiming at the same target area. It can also be combined with other approaches for more refined analysis (e.g., optimization models).

Floral glands in myophilous and sapromyophilous species of Pleurothallidinae (Epidendroideae, Orchidaceae)—osmophores, nectaries, and a unique sticky gland - Gustavo Arévalo-Rodrigues; Fábio de Barros; Arthur R. Davis; Poliana Cardoso-Gustavson (Protoplasma, 2021)

Impact of growing seasons and pesticides used on the occurrence and severity of the gummy stem blight in melon cultivation in Brazil - Gil Rodrigues dos Santos; P. H. Tschoeke; R. A. Sarmento; E. E. Oliveira; N. Rodrigues-Silva; M. S. Dalcin; K. Haddi; R. S. Silva (European Journal of Plant Pathology, 2021)

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

Vibrotactile biofeedback devices in Parkinson’s disease: a narrative review - Helena R. Gonçalves; Ana Margarida Rodrigues; Cristina P. Santos (Medical & Biological Engineering & Computing, 2021)

Textile effluent treatment employing yeast biomass and a new nanomagnetic biocomposite - Jacqueline R. Nascimento; Kátia C.H. Bezerra; Tiago D. Martins; Elma N.V.M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Environmental Science and Pollution Research, 2021)

Bioaccumulation of metals by edible bivalve Saccostrea cucullata and its application as a bioindicator of metal pollution, tropical (Zuari) estuary, Goa, India - Racheal J. Rodrigues; Maheshwar R. Nasnodkar; Ganapati N. Nayak; Anoop Kumar Tiwari (Arabian Journal of Geosciences, 2021)

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Using richness of native and non-native aquatic species along a climatic gradient to test the intermediate disturbance hypothesis - Luciano N. Santos; Ana Clara S. Franco; Joice S. de Souza; Igor C. Miyahira; Antonio Jailson S. Rodrigues; Isabela Cristina B. Gonçalves; Natascha Krepsky; Helga A. B. Monte; Clarissa Naveira; Tatiana M. B. Cabrini; Rayane R. S. Abude; Matheus Augusto; et al. (Hydrobiologia, 2021)

(3,3’-Methylene)bis-2-hydroxy-1,4-naphthoquinones induce cytotoxicity against DU145 and PC3 cancer cells by inhibiting cell viability and promoting cell cycle arrest - Paula Priscilla de Freitas; Ruan Carlos Busquet Ribeiro; Isabella dos Santos Guimarães; Caroline S. Moreira; David R. Rocha; Fernando de Carvalho da Silva; Vitor Francisco Ferreira; Etel Rodrigues Pereira Gimba (Molecular Biology Reports, 2021)

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Feeding behavior of feedlot-finished crossbred bulls fed palm kernel cake - Mateus de M. Lisboa; Robério R. Silva; Fabiano F. da Silva; Maria M. S. Pereira; Gabriel D. Costa; Fabrício B. L. Mendes; Sinvaldo O. de Souza; Marceliana da C. Santos; Laoan B. O. Rodrigues; Henry D. R. Alba; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2021)

Ursolic acid abrogates depressive-like behavior and hippocampal pro-apoptotic imbalance induced by chronic unpredictable stress - André R. S. Colla; Francis L. Pazini; Vicente Lieberknecht; Anderson Camargo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2021)

The CORDEX Flagship Pilot Study in southeastern South America: a comparative study of statistical and dynamical downscaling models in simulating daily extreme precipitation events - M. L. Bettolli; S. A. Solman; R. P. da Rocha; M. Llopart; J. M. Gutierrez; J. Fernández; M. E. Olmo; A. Lavin-Gullon; S. C. Chou; D. Carneiro Rodrigues; E. Coppola; R. Balmaceda Huarte; et al. (Climate Dynamics, 2021)

Herbaceous-shrub species composition, diversity and soil attributes in moist grassland, shrub grassland and savanna in Central Brazil - Gabriella Ferreira de Souza; Raphael Ferreira Almeida; Natália Rodrigues Bijos; Christopher William Fagg; Cássia Beatriz R. Munhoz (Brazilian Journal of Botany, 2021)

Association between exposure to air pollution during intrauterine life and cephalic circumference of the newborn - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R. D. M. Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Environmental Science and Pollution Research, 2021)

Seasonal variation in photosynthetic rates and satellite-based GPP estimation over mangrove forest - N. Lele; M. K. Kripa; M. Panda; S. K. Das; A. Hari Nivas; N. Divakaran; S. Naik-Gaonkar; A. Sawant; A. K. Pattnaik; R. N. Samal; T. Thangaradjou; A. Saravanakumar; et al. (Environmental Monitoring and Assessment, 2021)

Reliability of evidence‐review methods in restoration ecology - João P. Romanelli; Paula Meli; Rafaela P. Naves; Marcelo C. Alves; Ricardo R. Rodrigues (Conservation Biology, 2021)
In restoration science, evidence reviews play a crucial role in summarizing research findings in practice and policy. However, if unreliable or inappropriate methods are used to review evidence, decisions based on these reviews may not accurately reflect the available evidence base. To assess the current value of restoration reviews, we examined a sample of meta‐analyses and narrative syntheses (n = 91) with the Collaboration for Environmental Evidence Synthesis Assessment Tool (CEESAT), which uses detailed criteria to assesses the method of policy‐relevant evidence synthesis according to elements important for objectivity, transparency, and comprehensiveness. Overall, reviews scored low based on this standard: median score 16 out of 39, modal score 15, and mean 16.6. Meta‐analyses scored higher than narrative syntheses (median 17 vs. 5, respectively), although there were some outlier narrative syntheses that had high scores, suggesting that quantitative synthesis does not solely reflect the reliability of a review. In general, criteria spanning the more fundamental review stages (i.e., searching for studies and including studies) received low scores for both synthesis types. Conversely, criteria comprising the later stages of the review (i.e., critical appraisal, data extraction, and data synthesis) were generally well described in meta‐analyses; thus, these criteria achieved the highest individual CEESAT scores. We argue that restoration ecology is well positioned to advance so‐called evidence‐based restoration, but review authors should elucidate their conceptual understanding of evidence syntheses and recognize that conducting reliable reviews demands the same methodological rigor and reporting standards used in primary research. Given the potential of evidence reviews to inform management, policy, and research, it is of vital importance that the overall methodological reliability of restoration reviews be improved.

First record on mercury accumulation in mice brain living in active volcanic environments: a cytochemical approach - A. Navarro-Sempere; Y. Segovia; A. S. Rodrigues; P. V. Garcia; R. Camarinho; M. García (Environmental Geochemistry and Health, 2021)

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

In vitro bioassay guided anti-dermatophyte and cytotoxic activities from Piper umbellatum L. Miq. led to 4-nerolidylcatechol - Jolindo A. Freitas; Rodrigo Sorrechia; Flávio A. S. Politi; André G. Santos; Edvânio R. Rodrigues; Lourdes C. Santos; Ana M. Fusco-Almeida; Andrew A. Oliveira; Rafael V. C. Guido; Rosemeire C. L. R. Pietro (Natural Product Research, 2020)

Violacein antimicrobial activity on Staphylococcus epidermidis biofilm - H. V. Dodou; A. H. M. Batista; S. C. Medeiros; G. W. P. Sales; M. L. Rodrigues; P. I. O. Pereira; P. C. N. Nogueira; E. R. Silveira; T. B. Grangeiro; N. A. P. Nogueira (Natural Product Research, 2020)

Mitoxantrone impairs proteasome activity and prompts early energetic and proteomic changes in HL-1 cardiomyocytes at clinically relevant concentrations - Vera Marisa Costa; João Paulo Capela; Joana R. Sousa; Rute P. Eleutério; Patrícia R. S. Rodrigues; José Luís Dores-Sousa; Rui A. Carvalho; Maria Lourdes Bastos; José Alberto Duarte; Fernando Remião; M. Gabriela Almeida; Kurt J. Varner; et al. (Archives of Toxicology, 2020)

Characterization, antibacterial activity and antibiotic modifying action of the Caryocar coriaceum Wittm. pulp and almond fixed oil - Fladson F.G. Pereira; Maria K. S. B. Feitosa; Maria do S. Costa; Saulo R. Tintino; Fábio F.G. Rodrigues; Irwin R. A. Menezes; Henrique D. M. Coutinho; José G.M. da Costa; Erlânio O. de Sousa (Natural Product Research, 2020)

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Metal mixtures in pregnant women and umbilical cord blood at urban populations—Rio de Janeiro, Brazil - Nataly Damasceno de Figueiredo; Monica Seefelder Araújo; Ronir R Luiz; Volney de Magalhaes Câmara; Silvana do Couto Jacob; Lisia Maria Gobbo dos Santos; Santos Alves Vicentini; Carmen Ildes Rodrigues Froes Asmus (Environmental Science and Pollution Research, 2020)

Sulfate removal from mine-impacted water by electrocoagulation: statistical study, factorial design, and kinetics - Caroline Rodrigues; Hioná V. Dal Magro Follmann; Dámaris Núñez-Gómez; Maria Eliza Nagel-Hassemer; Flávio R. Lapolli; María Ángeles Lobo-Recio (Environmental Science and Pollution Research, 2020)

Formaldehyde effects on kanamycin resistance gene of inactivated recombinant Escherichia coli vaccines - Rafael A. Donassolo; Marcos Roberto A. Ferreira; Clóvis Moreira Jr; Lucas M. dos Santos; Emili Griep; Gustavo M. S. G. Moreira; Rafael R. Rodrigues; Ângela N. Moreira; Fabricio R. Conceição (Biotechnology Letters, 2020)

Costus stripe mosaic virus, a tentative new member of the genus Potyvirus - M. Amelia V. Alexandre; Ligia M. L. Duarte; Pedro L. Ramos-González; Alexandre L. R. Chaves; Ricardo Harakava; Leilane K. Rodrigues; Camila Chabi-Jesus; E. W. Kitajima (Archives of Virology, 2020)

Historical biogeography identifies a possible role of Miocene wetlands in the diversification of the Amazonian rocket frogs (Aromobatidae: Allobates ) - Alexandre Réjaud; Miguel T. Rodrigues; Andrew J. Crawford; Santiago Castroviejo‐Fisher; Andrés F. Jaramillo; Juan C. Chaparro; Frank Glaw; Giussepe Gagliardi‐Urrutia; Jiří Moravec; Ignacio J. De la Riva; Pedro Perez; Albertina P. Lima; et al. (Journal of Biogeography, 2020)
Aim We investigate the spatiotemporal context of the diversification of Allobates , a widespread genus of Amazonian frogs with high species diversity particularly in western Amazonia. We tested if that diversity originated in situ or through repeated dispersals from other Amazonian areas and if this diversification took place during or after the Pebas system, a vast lacustrine system occupying most western Amazonia between 23 and 10 million years ago (Mya). Location Amazonia. Taxon Allobates (Anura: Aromobatidae). Methods We gathered a spatially and taxonomically extensive sampling of mitochondrial DNA sequences from 932 Allobates specimens to delimit Operational Taxonomic Units (OTUs). Complete mitogenomes of these OTUs were assembled to reconstruct a time‐calibrated phylogeny used to infer the historical and spatial origin of the Amazonian Allobates lineages. Results Phylogenetic analyses and ancestral area reconstruction suggested that most of the western Amazonian lineages resulted from in situ diversification and that these events occurred between the inferred origin of the genus (25 Mya) and 10 Mya, with a possible peak between 14 and 10 Mya. Dispersal among areas mostly occurred from western Amazonia towards the Brazilian and the Guiana Shields. Closely related Allobates OTUs display an allopatric pattern of distribution, matching interfluves delimited by modern Amazonian rivers. Main Conclusions In western Amazonia, diversification of Allobates appears to have been simultaneous with the last stages of the Pebas system (14–10 Mya). Subsequently (within the last 10 Mya), modern Amazonian river courses shaped the distribution pattern of Allobates species and possibly promoted allopatric speciation.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Biodiversity of caridean shrimps on rocky bottoms of two preserved islands on the southeastern Brazilian coast - Isabela R. R. Moraes; Alexandre Oliveira Almeida; Valter José Cobo; Douglas Fernandes Rodrigues Alves; Thiago Maia Davanso; Antonio Leão Castilho (Marine Biology Research, 2020)

Damming reduced the functional richness and caused the shift to a new functional state of the phytoplankton in a subtropical region - Alfonso Pineda; Patrícia Iatskiu; Susicley Jati; Aline C. M. Paula; Bárbara F. Zanco; Claudia C. Bonecker; Geovani A. Moresco; Laura A. Ortega; Yasmin R. Souza; Luzia C. Rodrigues (Hydrobiologia, 2020)

Gonadal remodeling and hormonal regulation during sex change of juvenile dusky grouper Epinephelus marginatus (Teleostei, Serranidae), an endangered protogynous hermaphrodite fish - J. A. Rodrigues-Filho; C. E. O. Garcia; C. G. Chehade; E. G. Sanches; M. I. Borella; F. L. Lo Nostro; B. C. Araújo; G. S. Branco; R. G. Moreira (Fish Physiology and Biochemistry, 2020)

Association between maternal exposure to air pollution before conception and sex determination in the city of São Paulo - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R D M Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Air Quality, Atmosphere & Health, 2020)

Stimulation of isoprene emissions and electron transport rates as key mechanisms of thermal tolerance in the tropical species Vismia guianensis - Tayana B. Rodrigues; Christopher R. Baker; Anthony P. Walker; Nate McDowell; Alistair Rogers; Niro Higuchi; Jeffrey Q. Chambers; Kolby J. Jardine (Global Change Biology, 2020)
Tropical forests absorb large amounts of atmospheric CO 2 through photosynthesis, but high surface temperatures suppress this absorption while promoting isoprene emissions. While mechanistic isoprene emission models predict a tight coupling to photosynthetic electron transport (ETR) as a function of temperature, direct field observations of this phenomenon are lacking in the tropics and are necessary to assess the impact of a warming climate on global isoprene emissions. Here we demonstrate that in the early successional species Vismia guianensis in the central Amazon, ETR rates increased with temperature in concert with isoprene emissions, even as stomatal conductance ( g s ) and net photosynthetic carbon fixation ( P n ) declined. We observed the highest temperatures of continually increasing isoprene emissions yet reported (50°C). While P n showed an optimum value of 32.6 ± 0.4°C, isoprene emissions, ETR, and the oxidation state of PSII reaction centers (q L ) increased with leaf temperature with strong linear correlations for ETR (ƿ = 0.98) and q L (ƿ = 0.99) with leaf isoprene emissions. In contrast, other photoprotective mechanisms, such as non‐photochemical quenching, were not activated at elevated temperatures. Inhibition of isoprenoid biosynthesis repressed P n at high temperatures through a mechanism that was independent of stomatal closure. While extreme warming will decrease g s and P n in tropical species, our observations support a thermal tolerance mechanism where the maintenance of high photosynthetic capacity under extreme warming is assisted by the simultaneous stimulation of ETR and metabolic pathways that consume the direct products of ETR including photorespiration and the biosynthesis of thermoprotective isoprenoids. Our results confirm that models which link isoprene emissions to the rate of ETR hold true in tropical species and provide necessary “ground‐truthing” for simulations of the large predicted increases in tropical isoprene emissions with climate warming.

Melaleuca leucadendra Essential Oil Promotes Loss of Cell Membrane and Wall Integrity and Inhibits Bacterial Growth: An In Silico and In Vitro Approach - Jessica P. Bautista-Silva; Janaína B. Seibert; Tatiane R. Amparo; Ivanildes V. Rodrigues; Luiz Fernando M. Teixeira; Gustavo Henrique B. Souza; Orlando D. H. dos Santos (Current Microbiology, 2020)

Retrospective study of porcine circovirus 3 (PCV3) in swine tissue from Brazil (1967–2018) - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; R. L. Silveira; T. X. Castro (Brazilian Journal of Microbiology, 2020)

How do wheat plants cope with Pyricularia oryzae infection? A physiological and metabolic approach - Carlos Eduardo Aucique-Pérez; Renata Sousa Resende; Auxiliadora Oliveira Martins; Patricia Ricardino Silveira; João Henrique Frota Cavalcanti; Nívea Moreira Vieira; Alisdair R. Fernie; Wagner Luiz Araújo; Fábio Murilo DaMatta; Fabrício Ávila Rodrigues (Planta, 2020)

An update on potential links between type 2 diabetes mellitus and Alzheimer’s disease - Ricardo Augusto Leoni De Sousa; Alison R. Harmer; Daniel Almeida Freitas; Vanessa Amaral Mendonça; Ana Cristina Rodrigues Lacerda; Hércules Ribeiro Leite (Molecular Biology Reports, 2020)

Large‐scale DNA‐based survey of frogs in Amazonia suggests a vast underestimation of species richness and endemism - Jean‐Pierre Vacher; Jérôme Chave; Francesco Gentile Ficetola; Guilhem Sommeria‐Klein; Shengli Tao; Christophe Thébaud; Michel Blanc; Agustín Camacho; José Cassimiro; Timothy J. Colston; Maël Dewynter; Raffael Ernst; et al. (Journal of Biogeography, 2020)
Aim Mapping Amazonian biodiversity accurately is a major challenge for integrated conservation strategies and to study its origins. However, species boundaries and their respective distribution are notoriously inaccurate in this region. Here, we generated a georeferenced database of short mtDNA sequences from Amazonian frogs, revised the species richness and the delimitation of bioregions of the Eastern Guiana Shield and estimated endemism within these bioregions. Location Amazonia, with a focus on the Eastern Guiana Shield. Taxon studied Amphibia: Anura. Methods We used an extensive DNA‐based sampling of anuran amphibians of Amazonia using next‐generation sequencing to delimit Operational Taxonomic Units (OTU) and their distribution. We analysed this database to infer bioregions using Latent Dirichlet Allocation modelling. We then compared endemism within these bioregions based on our results and the current IUCN database, and inferred environmental variables that contributed the most to the biogeographic pattern. Results The recognized anuran species richness within the focal area increased from 440 species currently listed by the IUCN Red List to as much as 876 OTUs with our dataset. We recovered eight bioregions, among which three lie within the Eastern Guiana Shield. We estimated that up to 82% of the OTUs found in this area are endemic, a figure three times higher than the previous estimate (28%). Environmental features related to seasonal precipitations are identified as playing an important role in shaping Amazonian amphibian bioregions. Main conclusions Our results have major implications for defining future conservation priorities of this vast area given that endemism in most Amazonian bioregions is vastly underestimated, and might therefore hide a large portion of threatened species. Moreover, these findings raise concern about meta‐analyses based on public databases within Amazonia dealing with poorly known groups.

Evaluation of gully development over several years using GIS and fractal analysis: a case study of the Palmital watershed, Minas Gerais (Brazil) - L. S. C. Real; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2020)

PAH Profiles in Suspended Particulate Matter from an Urbanized River Within the Brazilian Amazon - L. C. Sousa; C. C. S. Rodrigues; R. A. Mendes; J. A. M. Corrêa (Bulletin of Environmental Contamination and Toxicology, 2020)

Cellular oxidative damage and impairment on the photosynthetic apparatus caused by Asian Soybean Rust on soybeans are alleviated by nickel - Andersom M. Einhardt; Sandro Ferreira; Gabriel M. F. Souza; Ana C. R. Mochko; Fabrício A. Rodrigues (Acta Physiologiae Plantarum, 2020)

P2X7 siRNA targeted to the kidneys increases klotho and delays the progression of experimental diabetic nephropathy - A. M. Rodrigues; R. S. Serralha; D. Y. Lima; G. R. Punaro; I. Visona; M. J. S. Fernandes; E. M. S. Higa (Purinergic Signalling, 2020)

Entomopathogenic Viruses in the Neotropics: Current Status and Recently Discovered Species - D R Sosa-Gómez; F S Morgado; R F T Corrêa; L A Silva; D M P Ardisson-Araújo; B M P Rodrigues; E E Oliveira; R W S Aguiar; B M Ribeiro (Neotropical Entomology, 2020)

Exploring the potential of polyethylene terephthalate in the design of antibacterial surfaces - Tugçe Çaykara; Maria G. Sande; Nuno Azoia; Ligia R. Rodrigues; Carla Joana Silva (Medical Microbiology and Immunology, 2020)
Polyethylene terephthalate (PET) is one of the most used polymeric materials in the health care sector mainly due to its advantages that include biocompatibility, high uniformity, mechanical strength and resistance against chemicals and/or abrasion. However, avoiding bacterial contamination on PET is still an unsolved challenge and two main strategies are being explored to overcome this drawback: the anti-adhesive and biocidal modification of PET surface. While bacterial adhesion depends on several surface properties namely surface charge and energy, hydrophilicity and surface roughness, a biocidal effect can be obtained by antimicrobial compounds attached to the surface to inhibit the growth of bacteria (bacteriostatic) or kill bacteria (bactericidal). Therefore, it is well known that granting antibacterial properties to PET surface would be beneficial in the prevention of infectious diseases. Different modification methods have been reported for such purpose. This review addresses some of the strategies that have been attempted to prevent or reduce the bacterial contamination on PET surfaces, including functionalisation, grafting, topographical surface modification and coating. Those strategies, particularly the grafting method seems to be very promising for healthcare applications to prevent infectious diseases and the emergence of bacteria resistance.

New solutions to capture and enrich bacteria from complex samples - Maria G. Sande; Tugçe Çaykara; Carla Joana Silva; Ligia R. Rodrigues (Medical Microbiology and Immunology, 2020)
Current solutions to diagnose bacterial infections though reliable are often time-consuming, laborious and need a specific laboratory setting. There is an unmet need for bedside accurate diagnosis of infectious diseases with a short turnaround time. Moreover, low-cost diagnostics will greatly benefit regions with poor resources. Immunoassays and molecular techniques have been used to develop highly sensitive diagnosis solutions but retaining many of the abovementioned limitations. The detection of bacteria in a biological sample can be enhanced by a previous step of capture and enrichment. This will ease the following process enabling a more sensitive detection and increasing the possibility of a conclusive identification in the downstream diagnosis. This review explores the latest developments regarding the initial steps of capture and enrichment of bacteria from complex samples with the ultimate goal of designing low cost and reliable diagnostics for bacterial infections. Some solutions use specific ligands tethered to magnetic constructs for separation under magnetic fields, microfluidic platforms and engineered nano-patterned surfaces to trap bacteria. Bulk acoustics, advection and nano-filters comprise some of the most innovative solutions for bacteria enrichment.

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Antimicrobial and Disinfectant Susceptibility of Salmonella Serotypes Isolated from Swine Slaughterhouses - Caroline L. de Quadros; Luciane Manto; Enzo Mistura; Bruna Webber; Giseli A. Ritterbusch; Karen A. Borges; Thales Q. Furian; Laura B. Rodrigues; Luciana R. dos Santos (Current Microbiology, 2020)

Clindamycin inhibits nociceptive response by reducing tumor necrosis factor-α and CXCL-1 production and activating opioidergic mechanisms - Felipe F. Rodrigues; Marcela I. Morais; Ivo S. F. Melo; Paulo S. A. Augusto; Marcela M. G. B. Dutra; Sarah O. A. M. Costa; Fábio C. Costa; Franciele A. Goulart; Alysson V. Braga; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2020)

Evidence of strong population bottleneck in genetics of endangered Brazilian Merganser (Mergus octosetaceus) - T. A. Maia; D. P. Campos; L. R. Silva; L. V. Lins; F. Ribeiro; F. Sebaio; F. R. Rodrigues; G. P. M. Dantas (Journal of Ornithology, 2020)

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Climate change impacts under representative concentration pathway scenarios on streamflow and droughts of basins in the Brazilian Cerrado biome - Jéssica A. M. Rodrigues; Marcelo R. Viola; Lívia A. Alvarenga; Carlos R. de Mello; Sin C. Chou; Vinícius A. de Oliveira; Venkatesh Uddameri; Marco A. V. Morais (International Journal of Climatology, 2020)
Brazilian Cerrado biome is the largest and richest tropical savanna in the world. In order to understand the effects of climate changes on the hydrology of the Cerrado basins, this paper investigates the hydrological impacts of climate change throughout the 21st century under different emissions scenarios on the streamflow and on the droughts in the Sono, Manuel Alves da Natividade and Palma basins, located in the Brazilian Cerrado. For this purpose, the SWAT hydrological model driven by the downscaling of the HadGEM2‐ES and MIROC5 global climate models associated with RCP4.5 and RCP8.5 scenarios were used in three time slices (2011–2040, 2041–2070 and 2071–2099). The Standardized Precipitation Index (SPI) and the Standardized Streamflow Index (SSFI) were used to characterize droughts. In general, the results showed that the duration, intensity and frequency of the meteorological and hydrological droughts are expected to increase during the future periods. However, the hydrological droughts are projected to be larger than the meteorological droughts. Reductions in the streamflow are indicated in all future time slices and under both RCPs, especially, during dry periods, which may cause negative impacts in the ecological functions of the Cerrado biome, risk for reduction of the recharge of aquifers and risk for the electric energy production in northern Brazil.

The Galactose-Binding Lectin Isolated from Vatairea macrocarpa Seeds Enhances the Effect of Antibiotics Against Staphylococcus aureus–Resistant Strain - Valdenice F. Santos; Maria S. Costa; Fábia F. Campina; Renato R. Rodrigues; Ana L. E. Santos; Felipe M. Pereira; Karla L. R. Batista; Rafael C. Silva; Raquel O. Pereira; Bruno A. M. Rocha; Henrique D. M. Coutinho; Claudener S. Teixeira (Probiotics and Antimicrobial Proteins, 2020)

Brazil's vegetation ravage may be encouraged by law - Gustavo H. Zaia Alves; Raffael M. Tófoli; Jorge L. Rodrigues-Filho; Patricia A. Sacramento; Vivian M. Cionek; Bruno R. S. Figueiredo; Edivando Vitor do Couto (Biodiversity and Conservation, 2020)

Thiamine, riboflavin, and nicotinamide inhibit paclitaxel-induced allodynia by reducing TNF-α and CXCL-1 in dorsal root ganglia and thalamus and activating ATP-sensitive potassium channels - Alysson V. Braga; Sarah O. A. M. Costa; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela I. Morais; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2020)

Do improved pastures enhance soil quality of cork oak woodlands in the Alentejo region (Portugal)? - A. R. Rodrigues; F. Costa e Silva; A. C. Correia; M. C. Bicho; M. Madeira; J. Coutinho (Agroforestry Systems, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Calibration and combination of monthly near-surface temperature and precipitation predictions over Europe - Luis R. L. Rodrigues; Francisco J. Doblas-Reyes; Caio A. S. Coelho (Climate Dynamics, 2019)

Antibacterial activity of silver/reduced graphene oxide nanocomposite synthesized by sustainable process - Raynara M. S. Jacovone; Jaqueline J. S. Soares; Thainá S. Sousa; Flávia R. O. Silva; Rafael H. L. Garcia; Hang N. Nguyen; Debora F. Rodrigues; Solange K. Sakata (Energy, Ecology and Environment, 2019)

Physiological and biochemical responses of soybean to white mold affected by manganese phosphite and fluazinam - M. I. C. Novaes; D. Debona; I. R. F. Fagundes-Nacarath; V. V. Brás; F. A. Rodrigues (Acta Physiologiae Plantarum, 2019)

Synthesis, structural characterization, and cytotoxic evaluation of chalcone derivatives - Paulo N. Bandeira; Telma L. G. Lemos; Hélcio S. Santos; Mylena C. S. de Carvalho; Daniel P. Pinheiro; Manoel O. de Moraes Filho; Cláudia Pessoa; Francisco W. A. Barros-Nepomuceno; Tigressa H. S. Rodrigues; Paulo R. V. Ribeiro; Herbert S. Magalhães; Alexandre M. R. Teixeira (Medicinal Chemistry Research, 2019)

Flavonoids from Plinia cauliflora (Mart.) Kausel (Myrtaceae) with antifungal activity - Tatiana M. Souza-Moreira; Juliana A. Severi; Edvânio Ramos Rodrigues; Mayara Ivani de Paula; Jolindo A. Freitas; Wagner Vilegas; Rosemeire C. L. R. Pietro (Natural Product Research, 2019)

Ecophysiology of mesophotic reef‐building corals in Hawai‘i is influenced by symbiont–host associations, photoacclimatization, trophic plasticity, and adaptation - Jacqueline L. Padilla‐Gamiño; Melissa S. Roth; Lisa J. Rodrigues; Christina J. Bradley; Robert R. Bidigare; Ruth D. Gates; Celia M. Smith; Heather L. Spalding (Limnology and Oceanography, 2019)
Mesophotic reef corals remain largely unexplored in terms of the genetic adaptations and physiological mechanisms to acquire, allocate, and use energy for survival and reproduction. In the Hawaiian Archipelago, the Leptoseris species complex form the most spatially extensive mesophotic coral ecosystem known and provide habitat for a unique community. To study how the ecophysiology of Leptoseris species relates to symbiont–host specialization and understand the mechanisms responsible for coral energy acquisition in extreme low light environments, we examined Symbiodinium (endosymbiotic dinoflagellate) photobiological characteristics and the lipids and isotopic signatures from Symbiodinium and coral hosts over a depth‐dependent light gradient (55–7 μ mol photons m −2 s −1 , 60–132 m). Clear performance differences demonstrate different photoadaptation and photoacclimatization across this genus. Our results also show that flexibility in photoacclimatization depends primarily on Symbiodinium type. Colonies harboring Symbiodinium sp. COI‐2 showed significant increases in photosynthetic pigment content with increasing depth, whereas colonies harboring Symbiodinium spp. COI‐1 and COI‐3 showed variability in pigment composition, yield measurements for photosystem II, as well as size and density of Symbiodinium cells. Despite remarkable differences in photosynthetic adaptive strategies, there were no significant differences among lipids of Leptoseris species with depth. Finally, isotopic signatures of both host and Symbiodinium changed with depth, indicating that coral colonies acquired energy from different sources depending on depth. This study highlights the complexity in physiological adaptations within this symbiosis and the different strategies used by closely related mesophotic species to diversify energy acquisition and to successfully establish and compete in extreme light‐limited environments.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Autophagy and vacuolar biogenesis during the nectary development - Silvia R. Machado; Tatiane M. Rodrigues (Planta, 2019)

First indication of deleterious impacts in white-seabream larvae (Diplodus sargus) survival and behaviour following acute venlafaxine exposure - Ana Rodrigues; Francisco O. Borges; Vasco Pissarra; Ana Luísa Maulvault; José R. Paula; Regina Bispo; Rui Rosa (Ecotoxicology, 2019)

Occurrence and Environmental Distribution of 5 UV Filters During the Summer Season in Different Water Bodies - S. K. Fagervold; A. S. Rodrigues; C. Rohée; R. Roe; M. Bourrain; D. Stien; P. Lebaron (Water, Air, & Soil Pollution, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Photochemistry and hydric responses of congeneric Croton species at restoration sites under dry season: implications for species selection - Angélica L. Rodrigues; Angelo A. S. Bertholdi; Luís Paulo B. Mantoan; Gabriela M. Vasconcellos; Luiz Fernando R. Almeida (Theoretical and Experimental Plant Physiology, 2019)

Chemical Characterization and Biotechnological Applicability of Pigments Isolated from Antarctic Bacteria - Tiago R. Silva; Renata S. N. Tavares; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Iramaia A. Neri-Numa; Glaucia M. Pastore; Luiz H. Rosa; José A. A. Schultz; Hosana M. Debonsi; Lorena R. G. Cordeiro; Valeria M. Oliveira (Marine Biotechnology, 2019)

Using a non-homogeneous Poisson model with spatial anisotropy and change-points to study air pollution data - Eliane R. Rodrigues; Geoff Nicholls; Mario H. Tarumoto; Guadalupe Tzintzun (Environmental and Ecological Statistics, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Comparative social grooming networks in captive chimpanzees and bonobos - Michelle A. Rodrigues; Emily R. Boeving (Primates, 2019)

Secretomic analysis of Beauveria bassiana related to cattle tick, Rhipicephalus microplus, infection - Lucélia Santi; Caio J. B. Coutinho-Rodrigues; Markus Berger; Lisete A. S. Klein; Eduardo M. De Souza; Rafael L. Rosa; Jorge A. Guimarães; John R. Yates; Wendell M. S. Perinotto; Vânia R. E. P. Bittencourt; Walter O. Beys-da-Silva (Folia Microbiologica, 2019)

Pyrene degradation by marine-derived ascomycete: process optimization, toxicity, and metabolic analyses - Maria R. S. Vasconcelos; Gabriela A. L. Vieira; Igor V. R. Otero; Rafaella C. Bonugli-Santos; Marili V. N. Rodrigues; Vera L. G. Rehder; Milene Ferro; Sinésio Boaventura; Maurício Bacci; Lara D. Sette (Environmental Science and Pollution Research, 2019)

Isolation by instability: Historical climate change shapes population structure and genomic divergence of treefrogs in the Neotropical Cerrado savanna - Mariana M. Vasconcellos; Guarino R. Colli; Jesse N. Weber; Edgardo M. Ortiz; Miguel T. Rodrigues; David C. Cannatella (Molecular Ecology, 2019)
Although the impact of Pleistocene glacial cycles on the diversification of the tropical biota was once dismissed, increasing evidence suggests that Pleistocene climatic fluctuations greatly affected the distribution and population divergence of tropical organisms. Landscape genomic analyses coupled with paleoclimatic distribution models provide a powerful way to understand the consequences of past climate changes on the present‐day tropical biota. Using genome‐wide SNP data and mitochondrial DNA, combined with projections of the species distribution across the late Quaternary until the present, we evaluate the effect of paleoclimatic shifts on the genetic structure and population differentiation of Hypsiboas lundii , a treefrog endemic to the South American Cerrado savanna. Our results show a recent and strong genetic divergence in H. lundii across the Cerrado landscape, yielding four genetic clusters that do not seem congruent with any current physical barrier to gene flow. Isolation by distance (IBD) explains some of the population differentiation, but we also find strong support for past climate changes promoting range shifts and structuring populations even in the presence of IBD. Post‐Pleistocene population persistence in four main areas of historical stable climate in the Cerrado seems to have played a major role establishing the present genetic structure of this treefrog. This pattern is consistent with a model of reduced gene flow in areas with high climatic instability promoting isolation of populations, defined here as “isolation by instability,” highlighting the effects of Pleistocene climatic fluctuations structuring populations in tropical savannas.

Allochthonous versus autochthonous organic matter sustaining macroconsumers in a subtropical sandy beach revealed by stable isotopes - A. M. Garcia; M. C. L. M. Oliveira; C. Odebrecht; J. L. A. Colling; J. P. Vieira; F. L. Rodrigues; R. F. Bastos (Marine Biology Research, 2019)

Effect of temperature on the thermal conductivity of a granite with high heat production from Central Portugal - M. M. Miranda; C. R. Matos; N. V. Rodrigues; A. J. S. C. Pereira; J. J. Costa (Journal of Iberian Geology, 2019)

Can Luminol Be a Fluorophore? - M. Fátima Barroso; Rui J. A. Silva; Sérgio F. Moreira; Sofia S. Rodrigues; Helena M. R. Gonçalves; Abel J. Duarte (Journal of Fluorescence, 2019)

Fourier transform infrared spectroscopy: unlocking fundamentals and prospects for bacterial strain typing - Ângela Novais; Ana R. Freitas; Carla Rodrigues; Luísa Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Glyphosate detection: methods, needs and challenges - A. L. Valle; F. C. C. Mello; R. P. Alves-Balvedi; L. P. Rodrigues; L. R. Goulart (Environmental Chemistry Letters, 2019)

Eucalyptus rust climatic risk as affected by topography and ENSO phenomenon - R. S. Nóia Júnior; F. Schwerz; J. L. Safanelli; J. C. Rodrigues; P. C. Sentelhas (Australasian Plant Pathology, 2019)

Pigments in an iridescent bacterium, Cellulophaga fucicola, isolated from Antarctica - Tiago R. Silva; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Fábio N. dos Santos; Marcos N. Eberlin; Iramaia A. Neri-Numa; Glaucia M. Pastore; Renata S. N. Tavares; Hosana M. Debonsi; Lorena R. G. Cordeiro; Luiz H. Rosa; et al. (Antonie van Leeuwenhoek, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Crispoic acid, a new compound from Laelia marginata (Orchidaceae), and biological evaluations against parasites, human cancer cell lines and Zika virus - Andrezza C. Belloto; Gredson K. Souza; Paula C. Perin; Ivania T. A. Schuquel; Silvana M. O. Santin; Lucas U. R. Chiavelli; Francielle P. Garcia; Vanessa Kaplum; Jean H. S. Rodrigues; Débora B. Scariot; Rodrigo Delvecchio; Erik Machado-Ferreira; et al. (Natural Product Research, 2018)

Biotransformation of (-)-cubebin by Aspergillus spp. into (-)-hinokinin and (-)-parabenzlactone, and their evaluation against oral pathogenic bacteria - Caroline Arruda; Daniele de Souza Eugênio; Monique Rodrigues Moreira; Guilherme Venâncio Símaro; Jairo Kenupp Bastos; Carlos Henrique Gomes Martins; Márcio Luís Andrade Silva; Rodrigo Cássio Sola Veneziani; Paula Bruzadelle Vieira; Sérgio R. Ambrósio (Natural Product Research, 2018)

Risk Assessment of the Drinking Water Samples in the Rural Area from MG, Brazil - Mayra S. Santos; Maria C. R. M. Metzker; Guilherme L. Rodrigues; Luis R. S. Corrêa; Mayne L. V. Silva; Ana L. G. Barbosa; Márcia C. S. Faria; Jairo L. Rodrigues (International Journal of Environmental Research, 2018)

Computing derivative information of sequentially coupled subsurface models - Rafael J. de Moraes; José R. P. Rodrigues; Hadi Hajibeygi; Jan Dirk Jansen (Computational Geosciences, 2018)

Current advances in gibberellic acid (GA3) production, patented technologies and potential applications - Marcela C. Camara; Luciana P. S. Vandenberghe; Cristine Rodrigues; Juliana de Oliveira; Craig Faulds; Emmanuel Bertrand; Carlos R. Soccol (Planta, 2018)

Phosphites attenuate Sclerotinia sclerotiorum-induced physiological impairments in common bean - I. R. F. Fagundes-Nacarath; D. Debona; V. V. Brás; P. R. Silveira; F. A. Rodrigues (Acta Physiologiae Plantarum, 2018)

Phylogeography of Muller's termite frog suggests the vicariant role of the Central Brazilian Plateau - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Gabriel C. Costa; Frank T. Burbrink; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To test three different scenarios to account for the geographic distribution of genetic variation in Dermatonotus muelleri , a fossorial frog endemic of the South American diagonal of open formations ( DOF ) formed by Chaco, Cerrado, and Caatinga biomes: (a) The pan‐ DOF hypothesis, where these biomes behave as a single biogeographical unit and DOF species lack population structure; (b) the southwest‐northeast ( SW ‐ NE ) hypothesis, where structured populations along the DOF have either asymmetric or unidirectional gene flow in the northeast direction; (c) the vicariance hypothesis, where a pattern of population structure with no or reduced gene flow is observed. Location Caatinga, Cerrado, and Chaco in South America. Methods We sampled 179 individuals across the species distribution and sequenced one mitochondrial and two nuclear markers. We evaluated population structure, the presence, direction, and asymmetry of gene flow, and demographic changes to test three different phylogeographic hypotheses for D. muelleri using a model‐based simulation approach. Results We found two geographically structured lineages with no gene flow, refuting pan‐ DOF hypothesis. The Southwest lineage occurs in Chaco and western Cerrado and the Northeast lineage in eastern Cerrado and Caatinga. Our results support the model with demographic change for the Northeast lineage and constant size for Southwest lineage. The vicariance model with divergence time estimated around 4 Ma was preferred. Main conclusions Vicariance was the best explanation for the geographic distribution of genetic variation in Dermatonotus . Divergence time supports the role of Neogene orogeny in central Brazil for the splitting of Dermatonotus lineages. The influence of Pleistocene climatic fluctuations seems restricted to changes in one lineage's population size. Therefore, both ancient and recent events shaped the phylogeography of Dermatonotus . Genetic divergence, lack of gene flow, and the presence of a geographic barrier between lineages indicate the existence of a cryptic, undescribed species in northeastern Brazil.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Quantifying individual specialization using tracking data: a case study on two species of albatrosses - A.-S. Bonnet-Lebrun; R. A. Phillips; A. Manica; A. S. L. Rodrigues (Marine Biology, 2018)

A facile method to prepare translucent anatase thin films in monolithic structures for gas stream purification - Caio Rodrigues-Silva; Ricardo A. R. Monteiro; Márcia Dezotti; Adrián M. T. Silva; Eugénia Pinto; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2018)

Brain-Derived Neurotrophic Factor Prevents Depressive-Like Behaviors in Early-Symptomatic YAC128 Huntington’s Disease Mice - Victor Silva da Fonsêca; André R. da Silva Colla; Cristine de Paula Nascimento-Castro; Evelini Plácido; Julia Macedo Rosa; Marcelo Farina; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues; Patricia S. Brocardo (Molecular Neurobiology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Nanoparticle vaccines against viral infections - Fernando B. Sulczewski; Raquel B. Liszbinski; Pedro R. T. Romão; Luiz Carlos Rodrigues Junior (Archives of Virology, 2018)

Mitochondrial genome analysis in penile carcinoma - L. F. Araujo; A. T. Terra; C. T. G. Sares; C. F. R. Sobreira; E. F. Faria; R. D. Machado; A. A. Rodrigues; V. F. Muglia; W. A. Silva; R. B. Reis (Molecular Biology Reports, 2018)

Targeting the mitochondrial VDAC in hepatocellular carcinoma using a polyclonal antibody-conjugated to a nitrosyl ruthenium complex - Loyanne C. B. Ramos; Fernando P. Rodrigues; Juliana C. Biazzotto; Sergio de Paula Machado; Leonardo D. Slep; Michael R. Hamblin; Roberto S. da Silva (JBIC Journal of Biological Inorganic Chemistry, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Publisher Correction to: Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Transcriptome analysis provides insights into the delayed sticky disease symptoms in Carica papaya - Johana Madroñero; Silas P. Rodrigues; Tathiana F. S. Antunes; Paolla M. V. Abreu; José A. Ventura; A. Alberto R. Fernandes; Patricia Machado Bueno Fernandes (Plant Cell Reports, 2018)

Diversification with gene flow and niche divergence in a lizard species along the South American “diagonal of open formations” - Emanuel M. Fonseca; Marcelo Gehara; Fernanda P. Werneck; Flávia M. Lanna; Guarino R. Colli; Jack W. Sites; Miguel T. Rodrigues; Adrian A. Garda (Journal of Biogeography, 2018)
Aim To assess the effects of historical events on the tempo and mode of diversification of the lizard Polychrus acutirostris along the South American diagonal of open formations ( DOF ). Location Caatinga and Cerrado biomes in Brazil. Methods We sequenced fragments of one mt DNA and three nu DNA genes of 68 individuals from 33 localities. We used population assignment methods to access genetic structure and estimate lineage boundaries. Next, we estimated lineage relationships, intraspecific diversity, environmental niche similarity and demographic history. Finally, we tested 12 diversification scenarios using an approximate Bayesian computation ( ABC ) approach. Results We recovered three non‐overlapping, geographically structured lineages corresponding to Caatinga, north‐east Cerrado and south‐west Cerrado, with the major divergence event dating to the Late Neogene. We also recovered a complex scenario of divergence associated with gene flow and niche divergence. Main conclusions We show a complex history of diversification along the South American DOF . Our findings support the role of environmental features as the likely drivers of P. acutirostris intraspecific diversification during the Late Neogene.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

P2X7 receptor and klotho expressions in diabetic nephropathy progression - A. M. Rodrigues; R. S. Serralha; C. Farias; G. R. Punaro; M. J. S. Fernandes; Elisa Mieko Suemitsu Higa (Purinergic Signalling, 2018)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Contribution to the understanding of biologic concentrations of arsenic in children living in an urban area from Rio de Janeiro, Brazil - Thatiana Verônica Rodrigues de Barcellos Fernandes; Volney M. Camara; Paulo Rubens Guimarães Barrocas; Armando Mayer; Carmen I. R. Froes Asmus (Environmental Science and Pollution Research, 2018)

Treatment with pentylenetetrazole (PTZ) and 4-aminopyridine (4-AP) differently affects survival, locomotor activity, and biochemical markers in Drosophila melanogaster - Deividi C. S. Soares; José L. R. Portela; Daniel H. Roos; Nathane R. Rodrigues; Karen K. Gomes; Giulianna E. Macedo; Thais Posser; Jeferson L. Franco; Waseem Hassan; Robson L. Puntel (Molecular and Cellular Biochemistry, 2018)

Pedotransfer functions of potentially toxic elements in tropical soils cultivated with vegetable crops - Alexys G. F. Boim; Sónia M. Rodrigues; Sabrina N. dos Santos-Araújo; Eduarda Pereira; Luís R. F. Alleoni (Environmental Science and Pollution Research, 2018)

Transgenerational Effects of Toxicants: An Extension of the Daphnia 21-day Chronic Assay? - B. B. Castro; A. R. Freches; M. Rodrigues; B. Nunes; S. C. Antunes (Archives of Environmental Contamination and Toxicology, 2018)

Reconquering the water: Evolution and systematics of South and Central American aquatic lizards (Gymnophthalmidae) - Sergio Marques‐Souza; Ivan Prates; Antoine Fouquet; Agustín Camacho; Philippe J. R. Kok; Pedro M. S. Nunes; Francisco Dal Vechio; Renato Sousa Recoder; Nathalia Mejia; Mauro Teixeira Junior; Cesar Barrio‐Amorós; José Cassimiro; et al. (Zoologica Scripta, 2018)
The Cercosaurini tribe stands out from other Gymnophthalmidae lizards for including several species with morphological adaptations to aquatic lifestyle (“Crocodile‐Like Morphology” – CLM ). Recent molecular phylogenies of Cercosaurini demonstrated the paraphyly of CLM species, implicitly suggesting that adaptations to the aquatic life evolved more than once. However, CLM species have remained poorly sampled, and a number of uncertainties persist, such as the monophyly of Neusticurus and the placement of Potamites apodemus within the tribe. Based on a more extensive molecular and morphological data set, we propose a phylogenetic hypothesis for Neusticurus and investigate, for the first time, the phylogenetic position of P . apodemus . We recovered a monophyletic Neusticurus clade; however, Neusticurus rudis as currently understood was recovered as paraphyletic, with two lineages that also show consistent morphological diagnosis; as a result, we resurrect and provide a taxonomic redescription of Neusticurus surinamensis Müller, . Moreover, because P. apodemus was recovered as sister to all other Echinosaura , we propose a new combination for this species ( Echinosaura apodema ). We also review the distribution of Neusticurus species, offering a comprehensive view of their biogeography. Lastly, our ancestral character reconstruction and dating analyses indicate that the CLM phenotype evolved four times independently during Cercosaurini′s evolutionary history. We hypothesize that the CLM phenotype and subsequent adaptation to aquatic life may be linked to the development of the Pebas Lake in western Amazonia during the Miocene.

Periphyton nutrient content, biomass and algal community on artificial substrate: response to experimental nutrient enrichment and the effect of its interruption in a tropical reservoir - Suele Aparecida Mendes Santos; Thiago Rodrigues dos Santos; Mariana S. R. Furtado; Raoul Henry; Carla Ferragut (Limnology, 2018)

Embryonic and larval development and fatty‐acid profile of Epinephelus marginatus spawned in captivity: tools applied to captive rearing - P. H. Mello; B. C. Araújo; M. F. Campos; J. A. Rodrigues‐Filho; C. E. O. Garcia; R. G. Moreira (Journal of Fish Biology, 2018)
Development, ontogeny of the digestive system and the fatty‐acid (FA) profile, were analysed during development of Epinephelus marginatus . Larvae were analysed 7 and 17 days post fertilization (dpf) to evaluate fatty‐acid profile and morphological variables, respectively. Epinephelus marginatus larvae have relatively slow development of digestive structures, but were able to capture, ingest and digest prey by 5 dpf. Eggs were composed of high percentages of polyunsaturated fatty acids (PUFA) in phospholipids. The percentage of n3 PUFAs was higher than n6, especially docosahexaenoic acid (DHA), which exhibited higher levels compared with other marine species during the first 3 days of development, both in terms of phospholipids and triglycerides. The larvae present a high content of docosahexaenoic acid–eicosapentaenoic acid (DHA–EPA) and, during this phase, live food of small size was required (copepods or SS‐strain Brachionus rotundiformes ), enriched with DHA–EPA. These results may guide future studies on the contribution of FAs required during this stage of the life cycle of E. marginatus , to advance knowledge of the use of these FAs throughout ontogeny and contribute to the culture of this species commercial production or restocking.

Circulating extracellular vesicles in the aging process: impact of aerobic exercise - Karine Bertoldi; Laura Reck Cechinel; Bruna Schallenberger; Giana Blume Corssac; Samuel Davies; Irene Clemes Külkamp Guerreiro; Adriane Belló-Klein; Alex Sander R. Araujo; Ionara Rodrigues Siqueira (Molecular and Cellular Biochemistry, 2018)

Seismic assessment of a heavy-timber frame structure with ring-doweled moment-resisting connections - Leonardo G. Rodrigues; Jorge M. Branco; Luís A. C. Neves; André R. Barbosa (Bulletin of Earthquake Engineering, 2018)

Changes in the patterns of extreme rainfall events in southern Brazil - Laís G. Fernandes; Regina R. Rodrigues (International Journal of Climatology, 2018)
In this study we have examined changes in frequency and intensity of extreme rainfall events for the state of Santa Catarina (SC) in southern Brazil during austral spring and summer. The results show that changes in El Niño‐Southern Oscillation (ENSO) between 1979–1999 and 2000–2015 due to different phases of Interdecadal Pacific Oscillation have an impact on the teleconnection patterns from the Pacific to South America. As a consequence, precipitation over SC in the late period is less likely to be linked to ENSO. Moreover, there have been changes not only in the frequency and intensity of extreme events between the two periods but also in the mechanisms that cause the extremes affecting the spatial distribution of the extremes. In spring, the extreme events are less likely to occur during El Niño events and more frequent during La Niña and neutral years. The classical mechanism, of an enhanced South Atlantic Lower Level Jet (SALLJ) bringing moisture to SC, is no longer responsible for the extremes in the spring. The current main mechanism is associated with the presence of frontal systems during ENSO years and the presence of the South Atlantic Convergence Zone (SACZ) to the north combined with an anticyclonic system off the South American coast during neutral years. As a consequence the extreme events are currently more frequent at stations in the eastern side of SC. In summer during neutral years, SACZ events have become less frequent at the same time that atmospheric blocking events have become more frequent, explaining the decrease in extremes. On the other hand, SACZ events have become more frequent during La Niña years and so do the extremes in SC, with El Niño events playing a less important role.

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Mining noise affects loud call structures and emission patterns of wild black-fronted titi monkeys - M. H. L. Duarte; M. C. Kaizer; R. J. Young; M. Rodrigues; R. S. Sousa-Lima (Primates, 2018)

In situ germination of two tropical recalcitrant seeds and changes in activity of ROS-scavenging enzymes - Elizabeth R. Marques; Tatiana A. A. Vaz; Ailton G. Rodrigues-Junior; Antonio C. Davide; Anderson C. José (Trees, 2017)

Methylphenidate Decreases ATP Levels and Impairs Glutamate Uptake and Na+,K+-ATPase Activity in Juvenile Rat Hippocampus - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Mateus Grings; Bruna Zanotto; Daniella M. Coelho; Carmen R. Vargas; Guilhian Leipnitz; Angela T. S. Wyse (Molecular Neurobiology, 2017)

Organosulfur compound protects against memory decline induced by scopolamine through modulation of oxidative stress and Na+/K+ ATPase activity in mice - Fernanda D. da Silva; Mikaela P. Pinz; Renata L. de Oliveira; Karline C. Rodrigues; Francine R. Ianiski; Mariana M. Bassaco; Claudio C. Silveira; Cristiano R. Jesse; Silvane S. Roman; Ethel A. Wilhelm; Cristiane Luchese (Metabolic Brain Disease, 2017)

Role of Dynein Axonemal Heavy Chain 6 Gene Expression as a Possible Biomarker for Huntington’s Disease: a Translational Study - Lorena B. Areal; Lorraine P. Pereira; Fabiola M. Ribeiro; Isabella G. Olmo; Marcelo R. Muniz; Maria do Carmo Rodrigues; Patrik F. Costa; Cristina Martins-Silva; Stephen S. G. Ferguson; Daniela A. M. Guimarães; Rita G. W. Pires (Journal of Molecular Neuroscience, 2017)

Diversity and succession of pelagic microorganism communities in a newly restored Illinois River floodplain lake - Michael J. Lemke; Sara F. Paver; Keenan E. Dungey; Luiz Felipe M. Velho; Angela D. Kent; Luzia Cleide Rodrigues; Doyn M. Kellerhals; Michelle R. Randle (Hydrobiologia, 2017)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Spittlebugs (Hemiptera: Cercopidae) and their host plants: a strategy for pasture diversification - R. Alvarenga; Alexander M. Auad; Jair C. Moraes; Sandra E. B. Silva; Brunno S. Rodrigues; Giani B. Silva (Applied Entomology and Zoology, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Wax Removal and Diamondback Moth Performance in Collards Cultivars - G. A. Silva; R. M. Pereira; N. Rodrigues-Silva; T. C. Souza; D. O. Ferreira; E. A. Queiroz; G. A. R. Silva; M. C. Picanço (Neotropical Entomology, 2017)

MPP+-Lesioned Mice: an Experimental Model of Motor, Emotional, Memory/Learning, and Striatal Neurochemical Dysfunctions - Mauricio P. Cunha; Francis L. Pazini; Vicente Lieberknecht; Josiane Budni; Ágatha Oliveira; Júlia M. Rosa; Gianni Mancini; Leidiane Mazzardo; André R. Colla; Marina C. Leite; Adair R. S. Santos; Daniel F. Martins; et al. (Molecular Neurobiology, 2017)

Evaluation of Mycotube, a modified version of Lowenstein–Jensen (LJ) medium, for efficient recovery of Mycobacterium tuberculosis (MTB) - R. Nambiar; S. Chatellier; N. Bereksi; A. van Belkum; N. Singh; B. Barua; A. Shetty; C. Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Convergent Traits in Mammals Associated with Divergent Behaviors: the Case of the Continuous Dental Replacement in Rock-Wallabies and African Mole-Rats - Helder Gomes Rodrigues; Lionel Hautier; Alistair R. Evans (Journal of Mammalian Evolution, 2017)

Evidence for a correlation between total lead concentrations in soils and the presence of geological faults - Marcos R. Moreira-Silva; Carlos A. Tello Sáenz; João O. Rodrigues Nunes; Manoel Godoy; Marcos F. S. Teixeira (Environmental Chemistry Letters, 2017)

N-acylhydrazones containing thiophene nucleus: a new anticancer class - Laura N. F. Cardoso; Thais C. M. Nogueira; Felipe A. R. Rodrigues; Augusto Cesar Aragão Oliveira; Maria Claudia dos Santos Luciano; Claudia Pessoa; Marcus V. N. de Souza (Medicinal Chemistry Research, 2017)

Biology of the relict fungus-farming ant Apterostigma megacephala Lattke, including descriptions of the male, gyne, and larva - J. Sosa-Calvo; A. Ješovnik; C. T. Lopes; A. Rodrigues; C. Rabeling; M. Bacci; H. L. Vasconcelos; T. R. Schultz (Insectes Sociaux, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

P transformations in cacao agroforests soils in the Atlantic forest region of Bahia, Brazil - S. Aleixo; A. C. Gama-Rodrigues; M. G. Costa; M. V. S. Sales; E. F. Gama-Rodrigues; J. R. B. Marques (Agroforestry Systems, 2017)

Larval development and allometric growth of the black‐faced blenny Tripterygion delaisi - F. N. Solomon; D. Rodrigues; E. J. Gonçalves; E. A. Serrão; R. Borges (Journal of Fish Biology, 2017)
Larval development and allometric growth patterns of the black‐faced blenny Tripterygion delaisi are described from a larval series (body length, L B = 3·30–12·10 mm) caught by light traps at the Arrábida Marine Park, Portugal. Larvae of T. delaisi possess distinctive morphometric and meristic characteristics which can be used to identify this species from related taxa. Pigmentation is sparse but characteristic, consisting of pigmented eyes, gas bladder pigmentation in the dorsal region, anal pigmentation and a row of regularly spaced postanal ventral melanophores. This pattern is present from as early as the yolk‐sac stage and persists throughout all stages with just the addition of head and caudal pigmentation during the flexion and postflexion stages, respectively. The majority of fin development (with the exception of the caudal fin), occurs in the later stages of development. Myomere counts range between 37 and 45 for all stages. Growth is allometric during larval development. When inflexion points of growth were detected, growth was found to be biphasic with the inflexion points occurring within a very narrow range of L B (8·70–8·90 mm) close to the mean ± s.d. (9·44 ± 1·48 mm L B ) of postflexion larvae. Considering allometric growth patterns and ontogenetic descriptions together, the first developmental phase includes the preflexion and flexion stage larvae, while the second phase characterises the postflexion larvae prior to the transition from larvae to juvenile.

Copper effect in petroleum hydrocarbons biodegradation by microorganisms associated to Juncus maritimus: role of autochthonous bioaugmentation - I. P. F. M. Montenegro; A. P. Mucha; I. Reis; P. Rodrigues; C. M. R. Almeida (International Journal of Environmental Science and Technology, 2017)

Benthic dinoflagellate blooms in tropical intertidal rock pools: elucidation of photoprotection mechanisms - J. S. Patil; R. V. Rodrigues; P. Paul; K. Sathish; M. Rafi; A. C. Anil (Marine Biology, 2017)

Assessing in vivo digestibility and effects on immune system of sheep fed alfalfa hay supplemented with a fixed amount of Ulva rigida and Gracilaria vermiculophylla - Ana R. J. Cabrita; Alexandra Correia; Ana R. Rodrigues; Paulo P. Cortez; Manuel Vilanova; António J.M. Fonseca (Journal of Applied Phycology, 2017)

Preparation of Extruded Snacks with Flavored Flour Obtained from the Carcasses of Nile Tilapia: Physicochemical, Sensory, and Microbiological Analysis - Alex P. Justen; Maria Luiza Rodrigues de Souza; Antonio R. G. Monteiro; Jane M. G. Mikcha; Eliane Gasparino; Ádina B. Delbem; Maria Regina B. de Carvalho; Ana P. Del Vesco (Journal of Aquatic Food Product Technology, 2017)

An index of Brazil’s vulnerability to expected increases in natural flash flooding and landslide disasters in the context of climate change - Nathan S. Debortoli; Pedro Ivo M. Camarinha; José A. Marengo; Regina R. Rodrigues (Natural Hazards, 2017)

Caffeine Reverts Memory But Not Mood Impairment in a Depression-Prone Mouse Strain with Up-Regulated Adenosine A2A Receptor in Hippocampal Glutamate Synapses - Nuno J. Machado; Ana Patrícia Simões; Henrique B. Silva; Ana Paula Ardais; Manuella P. Kaster; Pedro Garção; Diana I. Rodrigues; Daniela Pochmann; Ana Isabel Santos; Inês M. Araújo; Lisiane O. Porciúncula; Ângelo R. Tomé; et al. (Molecular Neurobiology, 2017)

Pramipexole, a Dopamine D2/D3 Receptor-Preferring Agonist, Prevents Experimental Autoimmune Encephalomyelitis Development in Mice - Vicente Lieberknecht; Stella C. Junqueira; Mauricio P. Cunha; Thaís A. Barbosa; Luiz F. de Souza; Igor S. Coelho; Adair R. S. Santos; Ana Lúcia S. Rodrigues; Alcir L. Dafré; Rafael C. Dutra (Molecular Neurobiology, 2017)

Exploring 1,2,3-triazole derivatives by using in vitro and in silico assays to target new antifungal agents and treat Candidiasis - Taísa F. Santos; Jéssica B. de Jesus; Paulo M. Neufeld; Alessandro K. Jordão; Vinícius R. Campos; Anna C. Cunha; Helena C. Castro; Maria C. B. V. de Souza; Vitor F. Ferreira; Carlos R. Rodrigues; Paula A. Abreu (Medicinal Chemistry Research, 2017)

Synthesis, antimicrobial activity and cytotoxic investigation of novel trifluoromethylated tetrazolo[1,5-a]pyrimidines - Elisandra Scapin; Clarissa P. Frizzo; Leticia V. Rodrigues; Geórgia C. Zimmer; Rodrigo A. Vaucher; Michelle R. Sagrillo; Janice L. Giongo; Carlos A. M. Afonso; Patrícia Rijo; Nilo Zanatta; Helio G. Bonacorso; Marcos A. P. Martins (Medicinal Chemistry Research, 2017)

3-D distribution of the radioelements in the granitic rocks of northern and central Portugal and geothermal implications - R. Lamas; M. M. Miranda; A. J. S. C. Pereira; L. J. P. F. Neves; N. Ferreira; N. V. Rodrigues (Journal of Iberian Geology, 2017)

Adaptative processes, control measures, genetic background, and resilience of malaria vectors and environmental changes in the Amazon region - W. P. Tadei; I. B. Rodrigues; M. S. Rafael; R. T. M. Sampaio; H. G. Mesquita; V. C. S. Pinheiro; J. A. C. Zequi; R. A. Roque; J. M. M. dos Santos (Hydrobiologia, 2017)

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

“Why throw away something useful?”: Attitudes and opinions of people treated for bipolar disorder and their relatives on organ and tissue donation - Carolina S. Padoan; Lucas F. Garcia; Aline A. Rodrigues; Lucas M. Patusco; Mariana V. Atz; Flavio Kapczinski; José R. Goldim; Pedro V. S. Magalhães (Cell and Tissue Banking, 2017)

Selection and Characterization of Bacillus thuringiensis (Berliner) (Eubacteriales: Bacillaceae) Strains for Ecdytolopha aurantiana (Lima) (Lepidoptera: Tortricidae) Control - J Zorzetti; A P S Ricietto; F A P Fazion; A M Meneguim; P M O J Neves; L A Vilas-Boas; R B Rodrigues; G T Vilas-Bôas (Neotropical Entomology, 2017)

Prevalence of hepatitis E virus antibodies in workers occupationally exposed to swine in Portugal - J. Teixeira; J. R. Mesquita; S. S. Pereira; R. M. S. Oliveira; J. Abreu-Silva; A. Rodrigues; M. Myrmel; K. Stene-Johansen; J. Øverbø; G. Gonçalves; M. S. J. Nascimento (Medical Microbiology and Immunology, 2017)

Single-channel EEG sleep stage classification based on a streamlined set of statistical features in wavelet domain - Thiago L. T. da Silveira; Alice J. Kozakevicius; Cesar R. Rodrigues (Medical & Biological Engineering & Computing, 2017)

Elucidating constraints for differentiation of major human Klebsiella pneumoniae clones using MALDI-TOF MS - C. Rodrigues; Â. Novais; C. Sousa; H. Ramos; T. M. Coque; R. Cantón; J. A. Lopes; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Extraction and electrophoretic analysis of large dsRNAs from desiccated plant tissues infected with plant viruses and biotrophic fungi - S. Khankhum; C. Escalante; E. Rodrigues de Souto and; R. A. Valverde (European Journal of Plant Pathology, 2017)

Methylene Blue Adsorption on Chitosan-g-Poly(Acrylic Acid)/Rice Husk Ash Superabsorbent Composite: Kinetics, Equilibrium, and Thermodynamics - Marcelo G. Vaz; Antonio G. B. Pereira; André R. Fajardo; Antônio C. N. Azevedo; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2017)

Male spider mites use chemical cues, but not the female mating interval, to choose between mates - Leonor R. Rodrigues; Alexandre R. T. Figueiredo; Susana A. M. Varela; Isabelle Olivieri; Sara Magalhães (Experimental and Applied Acarology, 2017)

Erratum to: Origin and introduction history of the least weasel (Mustela nivalis) on Mediterranean and Atlantic islands inferred from genetic data - Mónica Rodrigues; Arthur R. Bos; Patrick J. Schembri; Ricardo F. de Lima; Petros Lymberakis; Lluís Parpal; Michele Cento; Sandrine Ruette; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Biological Invasions, 2017)

Origin and introduction history of the least weasel (Mustela nivalis) on Mediterranean and Atlantic islands inferred from genetic data - Mónica Rodrigues; Arthur R. Bos; Patrick J. Schembri; Ricardo F. de Lima; Petros Lymberakis; Lluís Parpal; Michele Cento; Sandrine Ruette; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Biological Invasions, 2017)

Performance of Eriopis connexa (Coleoptera: Coccinellidae) resistant to lambda-cyhalothrin after extended recovery from knockdown - D S Santos; A R S Rodrigues; J B Torres; R Lira (Neotropical Entomology, 2016)

Creatine, Similar to Ketamine, Counteracts Depressive-Like Behavior Induced by Corticosterone via PI3K/Akt/mTOR Pathway - Francis L. Pazini; Mauricio P. Cunha; Julia M. Rosa; André R. S. Colla; Vicente Lieberknecht; Ágatha Oliveira; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2016)

Chromium Displacement in Subtropical Soils Fertilized with Hydrolysed Leather: A Laboratory Study - Jovana Bavaresco; Jessé R. Fink; Maria Lucia K. Rodrigues; Clesio Gianello; Vidal Barrón; José Torrent (Bulletin of Environmental Contamination and Toxicology, 2016)

Fitness Advantage in Heterozygous Ladybird Beetle Eriopis connexa (Germar) Resistant to Lambda-Cyhalothrin - R Lira; A R S Rodrigues; J B Torres (Neotropical Entomology, 2016)

Effect of petroleum hydrocarbons in copper phytoremediation by a salt marsh plant (Juncus maritimus) and the role of autochthonous bioaugmentation - I. P. F. M. Montenegro; A. P. Mucha; I. Reis; P. Rodrigues; C. M. R. Almeida (Environmental Science and Pollution Research, 2016)

Essential oils to control ichthyophthiriasis in pacu, Piaractus mesopotamicus (Holmberg): special emphasis on treatment with Melaleuca alternifolia - G M R Valladão; S U Gallani; C V Ikefuti; C da Cruz; N Levy‐Pereira; M V N Rodrigues; F Pilarski (Journal of Fish Diseases, 2016)
In vitro effect of the Melaleuca alternifolia , Lavandula angustifolia and Mentha piperita essential oils ( EO s) against Ichthyophthirius multifiliis and in vivo effect of M. alternifolia for treating ichthyophthiriasis in one of the most important South American fish, Piaractus mesopotamicus (Holmberg), were evaluated. The in vitro test consisted of three EO s, each at concentrations of 57 μL L −1 , 114 μL L −1 , 227 μL L −1 and 455 μL L −1 , which were assessed once an hour for 4 h in microtitre plates (96 wells). The in vitro results demonstrated that all tested EO s showed a cytotoxic effect against I. multifiliis compared to control groups ( P 0.05). The in vivo treatment for white spot disease was performed in a bath for 2 h day −1 for 5 days using the M. alternifolia EO (50 μL L −1 ). In this study, 53.33% of the fish severely infected by I. multifiliis survived after the treatment with M. alternifolia (50 μL L −1 ) and the parasitological analysis has shown an efficacy of nearly 100% in the skin and gills, while all the fish in the control group died. Furthermore, the potential positive effect of M. alternifolia EO against two emergent opportunistic bacteria in South America Edwardsiella tarda and Citrobacter freundii was discussed.

Distribution patterns of the ghost crab Ocypode cursor on sandy beaches of a tropical island in the Cabo Verde archipelago, Eastern Central Atlantic - E Rodrigues; R Freitas; N de C Delgado; A Soares-Gomes (African Journal of Marine Science, 2016)

Whole genome and exome sequencing realignment supports the assignment of KCNJ12, KCNJ17, and KCNJ18 paralogous genes in thyrotoxic periodic paralysis locus: functional characterization of two polymorphic Kir2.6 isoforms - Rolf M. Paninka; Diego R. Mazzotti; Marina M. L. Kizys; Angela C. Vidi; Hélio Rodrigues; Silas P. Silva; Ilda S. Kunii; Gilberto K. Furuzawa; Manoel Arcisio-Miranda; Magnus R. Dias-da-Silva (Molecular Genetics and Genomics, 2016)

Interleukin-1 Receptor Antagonist Decreases Hypothalamic Oxidative Stress During Experimental Sepsis - Fazal Wahab; Nilton N. Santos-Junior; Rodrigo Pereira de Almeida Rodrigues; Luis Henrique A. Costa; Carlos Henrique R. Catalão; Maria Jose A. Rocha (Molecular Neurobiology, 2016)

Modulation of aquaporins 3 and 9 after exposure of ovine ovarian tissue to cryoprotectants followed by in vitro culture - A. D. Sales; A. B. G. Duarte; R. R. Santos; K. A. Alves; L. F. Lima; G. Q. Rodrigues; I. R. Brito; C. H. Lobo; J. B. Bruno; Y. Locatelli; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Research, 2016)

Incomplete species recognition entails few costs in spider mites, despite first-male precedence - Salomé H. Clemente; Leonor R. Rodrigues; Rita Ponce; Susana A. M. Varela; Sara Magalhães (Behavioral Ecology and Sociobiology, 2016)

A spatially explicit estimate of the prewhaling abundance of the endangered North Atlantic right whale - Sophie Monsarrat; M. Grazia Pennino; Tim D. Smith; Randall R. Reeves; Christine N. Meynard; David M. Kaplan; Ana S.L. Rodrigues (Conservation Biology, 2016)
The North Atlantic right whale (NARW) (Eubalaena glacialis) is one of the world's most threatened whales. It came close to extinction after nearly a millennium of exploitation and currently persists as a population of only approximately 500 individuals. Setting appropriate conservation targets for this species requires an understanding of its historical population size, as a baseline for measuring levels of depletion and progress toward recovery. This is made difficult by the scarcity of records over this species’ long whaling history. We sought to estimate the preexploitation population size of the North Atlantic right whale and understand how this species was distributed across its range. We used a spatially explicit data set on historical catches of North Pacific right whales (NPRWs) (Eubalaena japonica) to model the relationship between right whale relative density and the environment during the summer feeding season. Assuming the 2 right whale species select similar environments, we projected this model to the North Atlantic to predict how the relative abundance of NARWs varied across their range. We calibrated these relative abundances with estimates of the NPRW total prewhaling population size to obtain high and low estimates for the overall NARW population size prior to exploitation. The model predicted 9,075–21,328 right whales in the North Atlantic. The current NARW population is thus

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Aspects of fish conservation in the upper Patos Lagoon basin - N. F. Fontoura; J. P. Vieira; F. G. Becker; L. R. Rodrigues; L. R. Malabarba; U. H. Schulz; O. O. Möller; A. M. Garcia; F. S. Vilella (Journal of Fish Biology, 2016)
The Patos Lagoon basin is a large (201 626 km 2 ) and complex drainage system in southern Brazil. The lagoon is 250 km long and 60 km wide, covering an area of 10 360 km 2 . The exchange of water with the Atlantic Ocean occurs through a 0·8 km wide and 15 m deep inlet, fixed by 4 km long jetties, at the southernmost part of the Patos Lagoon. The estuarine area is restricted to its southern portion (10%), although the upper limit of saline waters migrates seasonally and year to year, influenced by the wind regime and river discharge. The known number of recorded limnetic fish species is 200, but this number is expected to increase. A higher endemism is observed in fish species occurring in upper tributaries. The basin suffers from the direct impact of almost 7 million inhabitants, concentrated in small to large cities, most with untreated domestic effluents. There are at least 16 non‐native species recorded in natural habitats of the Patos Lagoon basin, about half of these being from other South American river basins. Concerning the fishery, although sport and commercial fisheries are widespread throughout the Patos Lagoon basin, the lagoon itself and the estuarine area are the main fishing areas. Landing statistics are not available on a regular basis or for the whole basin. The fishery in the northern Patos Lagoon captures 31 different species, nine of which are responsible for most of the commercial catches, but only three species are actually sustaining the artisanal fishery: the viola Loricariichthys anus : 455 kg per 10 000 m 2 gillnet per day, the mullet Mugil liza : 123 kg per 10 000 m 2 gillnet per day and the marine catfish Genidens barbus : 50 kg per 10 000 m 2 gillnet per day. A decline of the fish stocks can be attributed to inadequate fishery surveillance, which leads to overfishing and mortality of juveniles, or to decreasing water quality because of urban and industrial activities and power production. Global climatic changes also represent a major threat to the Patos system by changing the frequency of El Niño‐La Niña‐Southern Oscillation ( ENSO ).

Genetic pool structure of local apple cultivars from Portugal assessed by microsatellites - V. Ferreira; A. M. Ramos-Cabrer; V. Carnide; O. Pinto-Carnide; A. Assunção; A. Marreiros; R. Rodrigues; S. Pereira-Lorenzo; I. Castro (Tree Genetics & Genomes, 2016)

Leaf water potential and sap flow as indicators of water stress in Crimson ‘seedless’ grapevines under different irrigation strategies - S. Shahidian; P. Valverde; R. Coelho; A. Santos; M. Vaz; A. Rato; J. Serrano; S. Rodrigues (Theoretical and Experimental Plant Physiology, 2016)

Thioridazine inhibits gene expression control of the cell wall signaling pathway (CWI) in the human pathogenic fungus Paracoccidioides brasiliensis - Daniela Leite Jabes; Ana Claudia de Freitas Oliveira; Valquíria Campos Alencar; Fabiano Bezerra Menegidio; Débora Liliane Souza Reno; Daiene Souza Santos; David Aciole Barbosa; Renata Ozelami Vilas Boas; Rodrigo Luiz de Oliveira Rodrigues Cunha; Tiago Rodrigues; Regina Costa de Oliveira; Luiz R. Nunes (Molecular Genetics and Genomics, 2016)

Complete genome sequence of bean rugose mosaic virus, genus Comovirus - M. H. S. Picoli; A. Garcia; A. A. L. Barboza; Eliezer Rodrigues de Souto; A. M. R. Almeida (Archives of Virology, 2016)

Chronic Treatment with a Clinically Relevant Dose of Methylphenidate Increases Glutamate Levels in Cerebrospinal Fluid and Impairs Glutamatergic Homeostasis in Prefrontal Cortex of Juvenile Rats - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Daniella M. Coelho; Ben Hur Mussulini; Mery S. L. Pereira; Mariana M. Parisi; Florencia Barbé-Tuana; Diogo L. de Oliveira; Carmen R. Vargas; Angela T. S. Wyse (Molecular Neurobiology, 2016)

Taxonomic status and origin of the Egyptian weasel (Mustela subpalmata) inferred from mitochondrial DNA - Mónica Rodrigues; Arthur R. Bos; Richard Hoath; Patrick J. Schembri; Petros Lymberakis; Michele Cento; Wissem Ghawar; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Genetica, 2016)

Mating system and pollen dispersal in Eugenia dysenterica (Myrtaceae) germplasm collection: tools for conservation and domestication - Eduardo B. Rodrigues; Rosane G. Collevatti; Lázaro J. Chaves; Lucas R. Moreira; Mariana P. C. Telles (Genetica, 2016)

Exposure to different glyphosate formulations on the oxidative and histological status of Rhamdia quelen - Camila R. Murussi; Maiara D. Costa; Jossiele W. Leitemperger; Luciana Guerra; Cintia C. R. Rodrigues; Charlene C. Menezes; Eduardo S. Severo; Fábio Flores-Lopes; Joseânia Salbego; Vania L. Loro (Fish Physiology and Biochemistry, 2016)

How sensitive are the Pacific–tropical North Atlantic teleconnections to the position and intensity of El Niño-related warming? - A. S. Taschetto; R. R. Rodrigues; G. A. Meehl; S. McGregor; M. H. England (Climate Dynamics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Leaf gas exchange and multiple enzymatic and non-enzymatic antioxidant strategies related to drought tolerance in two oil palm hybrids - Priscilla A. Silva; Igor V. Oliveira; Kátia C. B. Rodrigues; Vanessa S. Cosme; Abel J. R. Bastos; Kelly S. C. Detmann; Roberto L. Cunha; Reginaldo A. Festucci-Buselli; Fábio M. DaMatta; Hugo A. Pinheiro (Trees, 2016)

On the estimation of the bed-material transport and budget along a river segment: application to the Middle Loire River, France - B. Camenen; R. C. Grabowski; A. Latapie; A. Paquier; L. Solari; S. Rodrigues (Aquatic Sciences, 2016)

Fungi associated with rocks of the A tacama D esert: taxonomy, distribution, diversity, ecology and bioprospection for bioactive compounds - Vívian N. Gonçalves; Charles L. Cantrell; David E. Wedge; Mariana C. Ferreira; Marco Aurélio Soares; Melissa R. Jacob; Fabio S. Oliveira; Douglas Galante; Fabio Rodrigues; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; et al. (Environmental Microbiology, 2016)
Summary This study assessed the diversity of cultivable rock‐associated fungi from A tacama D esert. A total of 81 fungal isolates obtained were identified as 29 Ascomycota taxa by sequencing different regions of DNA. C ladosporium halotolerans , P enicillium chrysogenum and P enicillium cf. citrinum were the most frequent species, which occur at least in four different altitudes. The diversity and similarity indices ranged in the fungal communities across the latitudinal gradient. The F isher‐α index displayed the higher values for the fungal communities obtained from the siltstone and fine matrix of pyroclastic rocks with finer grain size, which are more degraded. A total of 23 fungal extracts displayed activity against the different targets screened. The extract of P . chrysogenum afforded the compounds α‐linolenic acid and ergosterol endoperoxide, which were active against C ryptococcus neoformans and methicillin‐resistance S taphylococcus aureus respectively. Our study represents the first report of a new habitat of fungi associated with rocks of the A tacama D esert and indicated the presence of interesting fungal community, including species related with saprobes, parasite/pathogen and mycotoxigenic taxa. The geological characteristics of the rocks, associated with the presence of rich resident/resilient fungal communities suggests that the rocks may provide a favourable microenvironment fungal colonization, survival and dispersal in extreme conditions.

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

Description of Dichelacera (Dichelacera) walteri n. sp. (Diptera: Tabanidae) with a Key to Related Species in the Subgenus Dichelacera Macquart - R R Guimarães; I S Gorayeb; R Rodrigues-Guimarães; G S Seppa; R W Carvalho (Neotropical Entomology, 2015)

Oxidative stress markers in fish (Astyanax sp. and Danio rerio) exposed to urban and agricultural effluents in the Brazilian Pampa biome - D. G. Costa-Silva; M. E. M Nunes; G. L. Wallau; I. K. Martins; A. P. P Zemolin; L. C. Cruz; N. R. Rodrigues; A. R. Lopes; T. Posser; J. L. Franco (Environmental Science and Pollution Research, 2015)

Characterization of antiproliferative potential and biological targets of a copper compound containing 4′-phenyl terpyridine - Ana Soraia Mendo; Sara Figueiredo; Catarina Roma-Rodrigues; Paula A. Videira; Zhen Ma; Mário Diniz; Miguel Larguinho; Pedro M. Costa; João C. Lima; Armando J. L. Pombeiro; Pedro V. Baptista; Alexandra R. Fernandes (JBIC Journal of Biological Inorganic Chemistry, 2015)

New Trends and Technological Challenges in the Industrial Production and Purification of Fructo-oligosaccharides - Clarisse Nobre; José A. Teixeira; Lígia R. Rodrigues (Critical Reviews in Food Science and Nutrition, 2015)

First clues on the ecology of whale falls in the deep A tlantic O cean: results from an experiment using cow carcasses - Ana Hilario; Marina R. Cunha; Luciana Génio; Ana Raquel Marçal; Ascensão Ravara; Clara F. Rodrigues; Helena Wiklund (Marine Ecology, 2015)
Sunken whale carcasses, known as ‘whale falls’, deliver large pulses of organic material to the seafloor and serve as habitat islands for unique assemblages of deep‐sea fauna that include generalist scavenging species, chemosynthetic fauna related to those from hydrothermal vents and cold seeps, and bone‐specialist species. Despite the growing interest in this peculiar habitat in the last decade, all long‐term studies of deep‐sea whale‐falls have been restricted to the Pacific and the ecology of these habitats in the Atlantic Ocean has been overlooked. Here we report the first study on large mammal carcasses in the deep Atlantic Ocean. Cow carcasses amounting to 570 kg were deployed at 1000 m in the Setubal canyon, where cetaceans naturally occur. Eighteen months after deployment, all soft tissues had been consumed and the visible remains of the carcasses consisted solely of skeletal material that supported a diverse macrofaunal assemblage distinct from that of the background, including organic‐enrichment respondents, sulphophiles and bone‐specialists. The trophic structure of this assemblage denotes an overlap of successional stages previously described in whale falls. Our results provide important insights into the contribution of mammal falls to deep‐sea biodiversity in the NE Atlantic, species distribution and biogeography of bone specialists, and the potential role of these habitats as dispersal stepping‐stones for vent and seep species. Additionally we show that cow carcasses may serve as an accessible model system for the study of ecological processes at deep‐sea whale‐falls.

Disease alters macroecological patterns of N orth A merican bats - Winifred F. Frick; Sébastien J. Puechmaille; Joseph R. Hoyt; Barry A. Nickel; Kate E. Langwig; Jeffrey T. Foster; Kate E. Barlow; Tomáš Bartonička; Dan Feller; Anne‐Jifke Haarsma; Carl Herzog; Ivan Horáček; et al. (Global Ecology and Biogeography, 2015)
Aim We investigated the effects of disease on the local abundances and distributions of species at continental scales by examining the impacts of white‐nose syndrome, an infectious disease of hibernating bats, which has recently emerged in N orth A merica. Location N orth A merica and E urope. Methods We used four decades of population counts from 1108 populations to compare the local abundances of bats in N orth A merica before and after the emergence of white‐nose syndrome to the situation in E urope, where the disease is endemic. We also examined the probability of local extinction for six species of hibernating bats in eastern N orth A merica and assessed the influence of winter colony size prior to the emergence of white‐nose syndrome on the risk of local extinction. Results White‐nose syndrome has caused a 10‐fold decrease in the abundance of bats at hibernacula in N orth A merica, eliminating large differences in species abundance patterns that existed between E urope and N orth A merica prior to disease emergence. White‐nose syndrome has also caused extensive local extinctions (up to 69% of sites in a single species). For five out of six species, the risk of local extinction was lower in larger winter populations, as expected from theory, but for the most affected species, the northern long‐eared bat ( M yotis septentrionalis ), extinction risk was constant across winter colony sizes, demonstrating that disease can sometimes eliminate numerical rarity as the dominant driver of extinction risk by driving both small and large populations extinct. Main conclusions Species interactions, including disease, play an underappreciated role in macroecological patterns and influence broad patterns of species abundance, occurrence and extinction.

A non-homogeneous poisson model with spatial anisotropy applied to ozone data from Mexico City - Eliane R. Rodrigues; Dani Gamerman; Mario H. Tarumoto; Guadalupe Tzintzun (Environmental and Ecological Statistics, 2015)

Assessing families’ and patients’ attitudes toward brain donation for research purposes in a Brazilian population sample - M. K. Fonseca; E. Rodrigues-Neto; A. S. R. Costa; M. A. B. C. Rockembach; R. S. Padilha; L. L. Fernandez; F. H. Oliveira; L. P. Garcia; A. Hilbig (Cell and Tissue Banking, 2015)

Sugar Ester Surfactants: Enzymatic Synthesis and Applications in Food Industry - Nair S. Neta; José A. Teixeira; Lígia R. Rodrigues (Critical Reviews in Food Science and Nutrition, 2015)

The effect of conventional mechanical periodontal treatment on red complex microorganisms and clinical parameters in Down syndrome periodontitis patients: a pilot study - M. H. Tanaka; T. O. Rodrigues; L. S. Finoti; S. R. L. Teixeira; M. P. A. Mayer; R. M. Scarel-Caminaga; E. M. A. Giro (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Molecular characterization of carbapenem-resistant Enterobacteriaceae at a tertiary care laboratory in Mumbai - M. Kazi; L. Drego; C. Nikam; K. Ajbani; R. Soman; A. Shetty; C. Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Occurrence and analysis of endocrine-disrupting compounds in a water supply system - A. R. M Carvalho; V. V. Cardoso; A. Rodrigues; E. Ferreira; M. J. Benoliel; E. A. Duarte (Environmental Monitoring and Assessment, 2015)

Evaluation of (2S,3R)-2-(amino)-[4-(N-benzylarenesulfonamido)-3-hydroxy-1-phenylbutane derivatives: a promising class of anticancer agents - Victor Facchinetti; Marcele Moreth; Claudia R. B. Gomes; Cláudia do Ó Pessoa; Felipe A. R. Rodrigues; Bruno C. Cavalcanti; Augusto C. A. Oliveira; Teiliane R. Carneiro; Ivson Lelis Gama; Marcus V. N. de Souza (Medicinal Chemistry Research, 2015)

Oysters as hot spots for mimivirus isolation - Kétyllen R. Andrade; Paulo P. V. M. Boratto; Felipe P. Rodrigues; Lorena C. F. Silva; Fábio P. Dornas; Mariana R. Pilotto; Bernard La Scola; Gabriel M. F. Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Phylogeny and recombination analysis of Brazilian yellow passion fruit isolates of Cowpea aphid-borne mosaic virus: origin and relationship with hosts - Leilane K. Rodrigues; Leonardo A. Silva; Renata M. Garcêz; Alexandre L. R. Chaves; Ligia M. L. Duarte; José S. Giampani; Addolorata Colariccio; Ricardo Harakava; Marcelo Eiras (Australasian Plant Pathology, 2015)

Novel isomannide-based peptide mimetics containing a tartaric acid backbone as serine protease inhibitors - Bárbara Abrahim-Vieira; Emmerson C. B. da Costa; Pedro H. R. de A. Azevedo; Aline C. Portela; Luiza R. S. Dias; Sergio Pinheiro; Amilcar Tanuri; Anne M. Capaccia; Gustavo T. Ventura; Ronaldo Mohana-Borges; Carlos R. Rodrigues; Alessandra M. T. de Souza; et al. (Medicinal Chemistry Research, 2014)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Nutrient stocks in litterfall and litter in cocoa agroforests in Brazil - A. G. Fontes; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. V. S. Sales; M. G. Costa; R. C. R. Machado (Plant and Soil, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Acute ethanol intake induces mitogen-activated protein kinase activation, platelet-derived growth factor receptor phosphorylation, and oxidative stress in resistance arteries - Natália A. Gonzaga; Glaucia E. Callera; Alvaro Yogi; André S. Mecawi; José Antunes-Rodrigues; Regina H. Queiroz; Rhian M. Touyz; Carlos R. Tirapelli (Journal of Physiology and Biochemistry, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Chemical composition of the essential oil of Lippia gracilis Schauer leaves and its potential as modulator of bacterial resistance - Vanessa de Carvalho Nilo Bitu; Heberty Di Tarso Fernandes Fecundo; José Galberto Martins da Costa; Henrique Douglas Melo Coutinho; Fabíola Fernandes G. Rodrigues; Nathalia Matos de Santana; Marco Antônio Botelho; Irwin R. Alencar Menezes (Natural Product Research, 2014)

A poly-ε-caprolactone based biofilm carrier for nitrate removal from water - A. L. Rodrigues; A. V. Machado; J. M. Nóbrega; A. Albuquerque; A. G. Brito; R. Nogueira (International Journal of Environmental Science and Technology, 2014)

Lectin of Abelmoschus esculentus (okra) promotes selective antitumor effects in human breast cancer cells - Leonardo G. Monte; Tatiane Santi-Gadelha; Larissa B. Reis; Elizandra Braganhol; Rafael F. Prietsch; Odir A. Dellagostin; Rodrigo Rodrigues e Lacerda; Carlos A. A. Gadelha; Fabricio R. Conceição; Luciano S. Pinto (Biotechnology Letters, 2014)

Dermatophytosis in Military in the Central-West Region of Brazil: Literature Review - Diniz Pereira Leite; Janaina Vasconcellos R. de Souza Amadio; Sara de Almeida Alves Simões; Sebastião Martins de Araújo; Nicolina Maria Rodrigues da Silva; Mariana Cazelli Anzai; Rosane Christine Hahn (Mycopathologia, 2014)

Increasing the Added-Value of Onions as a Source of Antioxidant Flavonoids: A Critical Review - M. R. Pérez-Gregorio; J. Regueiro; J. Simal-Gándara; A. S. Rodrigues; D. P. F. Almeida (Critical Reviews in Food Science and Nutrition, 2014)

Investigation of blood parasites of pygoscelid penguins at the King George and Elephant Islands, South Shetlands Archipelago, Antarctica - Ralph Eric Thijl Vanstreels; Flavia R. Miranda; Valeria Ruoppolo; Ana Olívia de Almeida Reis; Erli Schneider Costa; Adriana Rodrigues de Lira Pessôa; João Paulo Machado Torres; Larissa Schmauder Teixeira da Cunha; Roberta da Cruz Piuco; Victor Hugo Valiati; Daniel González-Acuña; Marcelo B. Labruna; et al. (Polar Biology, 2014)

Biological and molecular characterization of a Trypanosoma cruzi isolate obtained from Panstrongylus megistus captured in Sao Paulo State, Brazil - Luciamáre P.A. Martins; Roberto E.P. Castanho; Altino L.S. Therezo; Aline R. Ribeiro; Luciana Lima; Marta M.G. Teixeira; Márcia A. Sperança; Vera L.C. Rodrigues; João A. da Rosa (Acta Parasitologica, 2014)
An isolate of Trypanosoma cruzi obtained from P. megistus captured in the peridomicile area of a home in Santo Antonio do Jardim city in the State of Sao Paulo, denominated T. cruzi Mogi, was characterized biologically and molecularly. The RFLP analysis of the D7 divergent domain in the 24Sα rDNA and of the mini-exon positioned the T. cruzi isolate within the TcI group. Phylogenetic analysis performed with the trypanosomatid barcode confirmed that the isolate belongs to the TcI group, with high homology to the 3014 c1 T.cruzi strain. The biological characterization of the isolate in rats showed a prepatent period of about 8 days, low parasitemia and tropism for cardiac, skeletal and colonic muscles. In Swiss mice the T. cruzi Mogi isolate showed a prepatent period of about 22 days, intermittent parasitemia in some animals, and tropism for cardiac and colonic muscles. Despite the inherent difficulty of identifying correlations amongst the molecular and biological characteristics of different T. cruzi groups, the tropism for colonic muscle demonstrated by T. cruzi Mogi represented a peculiarity of this isolate within the TcI group.

Evaluation of dihydroisocoumarins produced by the endophytic fungus Arthrinium state of Apiospora montagnei against Schistosoma mansoni - Henrique P. Ramos; Marilia R. Simão; Julia M. de Souza; Lizandra G. Magalhães; Vanderlei Rodrigues; Sérgio R. Ambrósio; Suraia Said (Natural Product Research, 2013)

Effect of forced aeration on citric acid production by Aspergillus sp. mutants in SSF - Cristine Rodrigues; Luciana P. S. Vandenberghe; Wilerson Sturm; Dario E. A. Dergint; Michele Rigon Spier; Júlio Cesar de Carvalho; Carlos R. Soccol (World Journal of Microbiology and Biotechnology, 2013)

Effect of ultraviolet-B radiation in laboratory on morphological and ultrastructural characteristics and physiological parameters of selected cultivar of Oryza sativa L. - Sérgio L. de Almeida; Éder C. Schmidt; Debora Tomazi Pereira; Marianne Kreusch; Marthiellen R. de L. Felix; Luz K. P. Osorio; Roberta de Paula Martins; Alexandra Latini; Fernanda Ramlov; Fungyi Chow; Marcelo Maraschin; Ana C. Rodrigues; et al. (Protoplasma, 2013)

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Mauritic acid: a new dammarane triterpene from the roots of Mauritia flexuosa L.f. (Arecaceae) - Hector H.F. Koolen; Elzalina R. Soares; Felipe M.A. da Silva; Aimêe A. de Oliveira; Antonia Q.L. de Souza; Lívia S. de Medeiros; Edson Rodrigues-Filho; Bruno C. Cavalcanti; Cláudia O. Pessoa; Manoel O. Moraes; Marcos J. Salvador; Afonso D.L. de Souza (Natural Product Research, 2013)

The antidepressant-like effect of inosine in the FST is associated with both adenosine A1 and A2A receptors - Manuella P. Kaster; Josiane Budni; Marta Gazal; Mauricio P. Cunha; Adair R. S. Santos; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2013)

Biological impacts of ocean acidification: a postgraduate perspective on research priorities - Samantha L. Garrard; R. C. Hunter; A. Y. Frommel; A. C. Lane; J. C. Phillips; R. Cooper; R. Dineshram; U. Cardini; S. J. McCoy; M. Arnberg; B. G. Rodrigues Alves; S. Annane; et al. (Marine Biology, 2013)

Systematics of spiny‐backed treefrogs ( H ylidae: O steocephalus ): an A mazonian puzzle - Karl‐Heinz Jungfer; Julián Faivovich; José M. Padial; Santiago Castroviejo‐Fisher; Mariana M. Lyra; Bianca V. M. Berneck; Patricia P. Iglesias; Philippe J. R. Kok; Ross D. MacCulloch; Miguel T. Rodrigues; Vanessa K. Verdade; Claudia P. Torres Gastello; et al. (Zoologica Scripta, 2013)
Spiny‐backed tree frogs of the genus O steocephalus are conspicuous components of the tropical wet forests of the A mazon and the G uiana S hield. Here, we revise the phylogenetic relationships of O steocephalus and its sister group T epuihyla , using up to 6134 bp of DNA sequences of nine mitochondrial and one nuclear gene for 338 specimens from eight countries and 218 localities, representing 89% of the 28 currently recognized nominal species. Our phylogenetic analyses reveal (i) the paraphyly of O steocephalus with respect to T epuihyla , (ii) the placement of ‘ H yla’ warreni as sister to T epuihyla , (iii) the non‐monophyly of several currently recognized species within O steocephalus and (iv) the presence of low ( O . taurinus and O . oophagus ) for the 16 S gene fragment used in amphibian DNA barcoding. We propose a new taxonomy, securing the monophyly of O steocephalus and T epuihyla by rearranging and redefining the content of both genera and also erect a new genus for the sister group of O steocephalus . The colouration of newly metamorphosed individuals is proposed as a morphological synapomorphy for O steocephalus . We recognize and define five monophyletic species groups within O steocephalus , synonymize three species of O steocephalus ( O . germani , O . phasmatus and O . vilmae ) and three species of T epuihyla ( T . celsae , T . galani and T . talbergae ) and reallocate three species ( H yla helenae to O steocephalus , O . exophthalmus to T epuihyla and O . pearsoni to D ryaderces gen. n.). Furthermore, we flag nine putative new species (an increase to 138% of the current diversity). We conclude that species numbers are largely underestimated, with most hidden diversity centred on widespread and polymorphic nominal species. The evolutionary origin of breeding strategies within O steocephalus is discussed in the light of this new phylogenetic hypothesis, and a novel type of amplexus (gular amplexus) is described.

Genetic structure of the Atlantic Rainforest tree species Luehea divaricata (Malvaceae) - André R. O. Conson; Eduardo A. Ruas; Bruna G. Vieira; Luana A. Rodrigues; Bruno F. Costa; Edmílson Bianchini; Alberto José Prioli; Claudete de Fátima Ruas; Paulo M. Ruas (Genetica, 2013)

Some Dependence Models for the Time Between Ozone Exceedances in Mexico City - Jorge A. Achcar; Eliane R. Rodrigues; Edilberto Cepeda-Cuervo (Environmental Modeling & Assessment, 2013)

Genetic and QTL analyses of yield and a set of physiological traits in pepper - N. A. Alimi; M. C. A. M. Bink; J. A. Dieleman; M. Nicolaï; M. Wubs; E. Heuvelink; J. Magan; R. E. Voorrips; J. Jansen; P. C. Rodrigues; G. W. A. M. van der Heijden; A. Vercauteren; et al. (Euphytica, 2013)

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

Presence of Torque Teno Virus (TTV) in Tap Water in Public Schools from Southern Brazil - Andréia Dalla Vecchia; Mariana Kluge; Joseane V. dos Santos da Silva; Juliana Comerlato; Manoela T. Rodrigues; Juliane D. Fleck; Roger B. da Luz; Thais F. Teixeira; Paulo M. Roehe; Roberta Capalonga; Ana Beatriz Oliveira; Fernando R. Spilki (Food and Environmental Virology, 2013)

A complex picture of associations between two host mussels and symbiotic bacteria in the Northeast Atlantic - Clara F. Rodrigues; Marina R. Cunha; Luciana Génio; Sébastien Duperron (The Science of Nature, 2013)

Autophagy is decreased in mesenteric fat tissue but not in intestinal mucosae of patients with Crohn’s disease - Raquel F. Leal; Cláudio S. R. Coy; Lício A. Velloso; Sushila Dalal; Mariana Portovedo; Viviane S. Rodrigues; Andressa Coope; Maria L. S. Ayrizono; João J. Fagundes; Marciane Milanski (Cell and Tissue Research, 2012)

Spread of an OmpK36-modified ST15 Klebsiella pneumoniae variant during an outbreak involving multiple carbapenem-resistant Enterobacteriaceae species and clones - Â. Novais; C. Rodrigues; R. Branquinho; P. Antunes; F. Grosso; L. Boaventura; G. Ribeiro; L. Peixe (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Infective endocarditis in intravenous drug abusers: an update - C. Sousa; C. Botelho; D. Rodrigues; J. Azeredo; R. Oliveira (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Carbon, nitrogen, organic phosphorus, microbial biomass and N mineralization in soils under cacao agroforestry systems in Bahia, Brazil - F. C. Zaia; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. K. S. Moço; A. G. Fontes; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2012)

Reproductive cycle of the Azorean endemic land snail Oxychilus ( Drouetia ) brincki Riedel, 1964 (Gastropoda: Pulmonata) - A.F. Ferreira; A.M. Frias Martins; R. Tristão da Cunha; P.C. Melo; A.S. Rodrigues (Invertebrate Reproduction & Development, 2012)

Immunological Aspects in Amyotrophic Lateral Sclerosis - Maria Carolina O. Rodrigues; Júlio C. Voltarelli; Paul R. Sanberg; Cesario V. Borlongan; Svitlana Garbuzova-Davis (Translational Stroke Research, 2012)

Revising the M235T Polymorphism Position for the AGT Gene and Reporting a Modifying Variant in the Brazilian Population with Potential Cardiac and Neural Impact - R. R. Lemos; S. G. de Lima; J. E. Gomes da Cunha; D. F. Oliveira; M. B. Rodrigues de Souza; C. F. J. Ayres; M. F. P. M. Albuquerque; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

First record of a whale shark Rhincodon typus in continental Europe - N. V. Rodrigues; J. P. S. Correia; J. T. C. Graça; F. Rodrigues; R. Pinho; M. Hirofumi (Journal of Fish Biology, 2012)
A whale shark Rhincodon typus was found in a set‐net in southern Portugal in October 2011. This was the first record for continental Europe and represents an increase of the species' known range. Upwelling events and increase in sea‐surface temperatures are possible reasons for this occurrence.

Occupational exposure to formaldehyde in an institute of morphology in Brazil: a comparison of area and personal sampling - Soraya de M. Ochs; Lucas de O. Grotz; Luciara S. Factorine; Mauro R. Rodrigues; Annibal D. Pereira Netto (Environmental Science and Pollution Research, 2012)

An electronic study of pyrazolones drugs on agranulocytosis - J. Rodrigues Silva; A. Noronha Queiroz; E. A. Fontes Junior; M. V. Santos Silva; A. Manoel Herculano; A. M. J. Chaves Neto; R. Santos Borges (Medicinal Chemistry Research, 2012)

The Male-produced Sex Pheromone of the True Bug, Phthia picta, is an Unusual Hydrocarbon - Rafael A. Soldi; Mauro A. C. M. Rodrigues; Jeffrey R. Aldrich; Paulo H. G. Zarbin (Journal of Chemical Ecology, 2012)

The smaller vesicomyid bivalves in the genus Isorropodon (Bivalvia, Vesicomyidae, Pliocardiinae) also harbour chemoautotrophic symbionts - Clara F. Rodrigues; Marina R. Cunha; Karine Olu; Sébastien Duperron (Symbiosis, 2012)

Evolutionary insight from whole‐genome sequencing of experimentally evolved microbes - JEREMY R. DETTMAN; NICOLAS RODRIGUE; ANITA H. MELNYK; ALEX WONG; SUSAN F. BAILEY; REES KASSEN (Molecular Ecology, 2012)
Experimental evolution (EE) combined with whole‐genome sequencing (WGS) has become a compelling approach to study the fundamental mechanisms and processes that drive evolution. Most EE‐WGS studies published to date have used microbes, owing to their ease of propagation and manipulation in the laboratory and relatively small genome sizes. These experiments are particularly suited to answer long‐standing questions such as: How many mutations underlie adaptive evolution, and how are they distributed across the genome and through time? Are there general rules or principles governing which genes contribute to adaptation, and are certain kinds of genes more likely to be targets than others? How common is epistasis among adaptive mutations, and what does this reveal about the variety of genetic routes to adaptation? How common is parallel evolution, where the same mutations evolve repeatedly and independently in response to similar selective pressures? Here, we summarize the significant findings of this body of work, identify important emerging trends and propose promising directions for future research. We also outline an example of a computational pipeline for use in EE‐WGS studies, based on freely available bioinformatics tools.

BMPRIB and BMPRII mRNA expression levels in goat ovarian follicles and the in vitro effects of BMP-15 on preantral follicle development - Isadora Machado T. Lima; Ivina R. Brito; Rafael Rossetto; Ana Beatriz G. Duarte; Giovanna Q. Rodrigues; Márcia Viviane A. Saraiva; José Jackson N. Costa; Mariana Aragão M. Donato; Christina A. Peixoto; José Roberto V. Silva; José Ricardo de Figueiredo; Ana Paula R. Rodrigues (Cell and Tissue Research, 2012)

Statistical Optimization of Sugarcane Leaves Hydrolysis into Simple Sugars by Dilute Sulfuric Acid Catalyzed Process - R. O. Moutta; Anuj K. Chandel; R. C. L. B. Rodrigues; M. B. Silva; G. J. M. Rocha; S. S. Silva (Sugar Tech, 2012)

The dual crop coefficient approach using a density factor to simulate the evapotranspiration of a peach orchard: SIMDualKc model versus eddy covariance measurements - T. A. Paço; M. I. Ferreira; R. D. Rosa; P. Paredes; G. C. Rodrigues; N. Conceição; C. A. Pacheco; L. S. Pereira (Irrigation Science, 2012)

Savanna soil fertility limits growth but not survival of tropical forest tree seedlings - Ricardo A. G. Viani; Ricardo R. Rodrigues; Todd E. Dawson; Rafael S. Oliveira (Plant and Soil, 2011)

Heavy Metals Contamination in Century-Old Manmade Technosols of Hope Bay, Antarctic Peninsula - Marcelo Braga Bueno Guerra; Carlos Ernesto G. R. Schaefer; Paula de Freitas Rosa; Felipe N. B. Simas; Thiago T. C. Pereira; Edenir Rodrigues Pereira-Filho (Water, Air, & Soil Pollution, 2011)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

Ultrastructural changes during early infection of Vigna unguiculata and Phaseolus vulgaris leaves by Xanthomonas axonopodis pv. phaseoli and an unexpected association between chloroplast and mitochondrion - André de O. Carvalho; Maura Da Cunha; Rosana Rodrigues; Cláudia P. Sudré; Izabela S. Santos; Kátia V. S. Fernandes; Guilherme R. Rabelo; Valdirene M. Gomes (Acta Physiologiae Plantarum, 2011)

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil - Regine H. S. F. Vieira; Renata A. Costa; Francisca G. R. Menezes; Giselle C. Silva; Grace N. D. Theophilo; Dália P. Rodrigues; Rodrigo Maggioni (Current Microbiology, 2011)

C and N Content in Density Fractions of Whole Soil and Soil Size Fraction Under Cacao Agroforestry Systems and Natural Forest in Bahia, Brazil - Joice Cleide O. Rita; Emanuela Forestieri Gama-Rodrigues; Antonio Carlos Gama-Rodrigues; Jose Carlos Polidoro; Regina Cele R. Machado; Virupax C. Baligar (Environmental Management, 2011)

Comparing the Number of Ozone Exceedances in Different Seasons of the Year in Mexico City - Jorge Alberto Achcar; Douglas Ernesto Fazioni Sousa; Eliane R. Rodrigues; Guadalupe Tzintzun (Environmental Modeling & Assessment, 2011)

Using stochastic volatility models to analyse weekly ozone averages in Mexico City - Jorge A. Achcar; Eliane R. Rodrigues; Guadalupe Tzintzun (Environmental and Ecological Statistics, 2011)

Microbial diversity in Frenulata (Siboglinidae, Polychaeta) species from mud volcanoes in the Gulf of Cadiz (NE Atlantic) - Clara F. Rodrigues; Ana Hilário; Marina R. Cunha; Andrew J. Weightman; Gordon Webster (Antonie van Leeuwenhoek, 2011)

Variation in Nectar and Pollen Availability, Sucrose Preference, and Daily Response in the Use of Flowers by Heliconius erato phyllis - Elisete A. Barp; Geraldo L. G. Soares; Erica J. M. Giani; Daniela Rodrigues; Gilson R. P. Moreira (Journal of Insect Behavior, 2011)

Evaluation Antimicrobial and Antiadhesive Properties of the Biosurfactant Lunasan Produced by Candida sphaerica UCP 0995 - Juliana M. Luna; Raquel D. Rufino; Leonie A. Sarubbo; Lígia R. M. Rodrigues; José A. C. Teixeira; Galba M. de Campos-Takaki (Current Microbiology, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Base excision repair genes XRCC1 and APEX1 and the risk for prostate cancer - H. Kuasne; I. S. Rodrigues; R. Losi-Guembarovski; M. B. Reis; P. E. Fuganti; E. P. Gregório; F. Libos Junior; H. M. Matsuda; M. A. F. Rodrigues; M. O. Kishima; I. M. S. Cólus (Molecular Biology Reports, 2011)

Spectrofluorimetric Determination of Coumarin in Commercial Tablets - Mirian Marcolan; Priscila Alfonso Martins; Valber A. Pedrosa; Maira R. Rodrigues; Hueder P. M. de Oliveira; Lucia Codognoto (Journal of Fluorescence, 2011)

Distribution of oxidizable organic C fractions in soils under cacao agroforestry systems in Southern Bahia, Brazil - Patrícia A. B. Barreto; Emanuela F. Gama-Rodrigues; A. C. Gama-Rodrigues; Alexandre G. Fontes; José C. Polidoro; Maria Kellen S. Moço; Regina C. R. Machado; V. C. Baligar (Agroforestry Systems, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Wheat resistance to leaf blast mediated by silicon - M. S. Xavier Filha; F. A. Rodrigues; G. P. Domiciano; H. V. Oliveira; P. R. Silveira; W. R. Moreira (Australasian Plant Pathology, 2011)

A novel melanoma-targeting peptide screened by phage display exhibits antitumor activity - Alisson L. Matsuo; Aparecida S. Tanaka; Maria A. Juliano; Elaine G. Rodrigues; Luiz R. Travassos (Journal of Molecular Medicine, 2010)

Non-homogeneous Poisson models with a change-point: an application to ozone peaks in Mexico city - Jorge Alberto Achcar; Eliane R. Rodrigues; Carlos Daniel Paulino; Paulo Soares (Environmental and Ecological Statistics, 2010)

Fructooligosaccharide production by Penicillium expansum - Margarida B. Prata; Solange I. Mussatto; Lígia R. Rodrigues; José A. Teixeira (Biotechnology Letters, 2010)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

Nitrogen aboveground turnover and soil stocks to 8 m depth in primary and selectively logged forest in southern Amazonia - TED R. FELDPAUSCH; EDUARDO G. COUTO; LUIZ CARLOS RODRIGUES; DANIELA PAULETTO; MARK S. JOHNSON; TIMOTHY J. FAHEY; JOHANNES LEHMANN; SUSAN J. RIHA (Global Change Biology, 2010)
Extensive areas of Amazonia undergo selective logging, modifying forest structure and nutrient cycles. Anthropogenic‐accelerated rates of nitrogen (N) turnover could increase N loss and affect regeneration, carbon sequestration and timber production. We quantified leaf area reduction, canopy opening and downed biomass and resultant N flux from reduced impact logging (RIL) activities. We compared canopy reduction, surface soil moisture and nitrate to 8 m depth between logged gaps and intact primary forest to determine if logging activities increase subsoil nitrate. To test long‐term logging effects, we evaluated surface N stocks along a 12‐year postlogging chronosequence. At the harvest rate of 2.6 trees ha −1 , total N additions in logging gaps, including leaves and wood from felled crowns (24.8 kg N ha −1 ) and other killed trees (41.9 kg N ha −1 ), accounted for over 80% of the total N addition to aboveground necromass from all logging activities (81.9 kg N ha −1 ). Despite this N turnover by logging, belowground nitrate storage to 8 m depth did not differ between logging gaps and primary forest at the low harvest rate and disturbance intensity of this study. Soil water depletion also did not differ between gaps and primary forest over 1 year, indicating the impact on belowground inorganic N was low. Compared with primary forest, nitrate concentrations to 8 m depth in logging gaps were only significantly higher at 60–100 cm, suggesting some N redistribution beyond the bulk of the fine roots in logging gaps. Extrapolated to the Amazon Basin scale, we provide a conservative estimate that logging damage and bole export under RIL would turn over 0.14 ± 0.07 to 0.23 ± 0.12 Tg N yr −1 based on 1999–2002 selective logging rates. Greater damage during conventional selective logging would cause higher N turnover throughout the Amazon Basin than our results based on RIL.

Mappings between a macroscopic neural-mass model and a reduced conductance-based model - Serafim Rodrigues; Anton V. Chizhov; Frank Marten; John R. Terry (Biological Cybernetics, 2010)

Carbon Storage in Soil Size Fractions Under Two Cacao Agroforestry Systems in Bahia, Brazil - Emanuela F. Gama-Rodrigues; P. K. Ramachandran Nair; Vimala D. Nair; Antonio C. Gama-Rodrigues; Virupax C. Baligar; Regina C. R. Machado (Environmental Management, 2010)

A method for detecting false bifurcations in dynamical systems: application to neural-field models - Serafim Rodrigues; David Barton; Frank Marten; Moses Kibuuka; Gonzalo Alarcon; Mark P. Richardson; John R. Terry (Biological Cybernetics, 2010)

Transitions to spike-wave oscillations and epileptic dynamics in a human cortico-thalamic mean-field model - Serafim Rodrigues; David Barton; Robert Szalai; Oscar Benjamin; Mark P. Richardson; John R. Terry (Journal of Computational Neuroscience, 2009)

Butyltin levels in several Portuguese coastal areas - Pedro N. Carvalho; Pedro Nuno R. Rodrigues; M. Clara P. Basto; M. Teresa S. D. Vasconcelos (Environmental Monitoring and Assessment, 2009)

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Evaluating the resistance to posaconazole by E-test and CLSI broth microdilution methodologies of Candida spp. and pathogenic moulds - R. Araujo; S. Costa-de-Oliveira; I. Coutinho; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Influence of high-pressure processing on the structure and memory effect of synthetic layered double hydroxides - Jaqueline C. Rodrigues; Tania Maria Haas Costa; Márcia R. Gallas; Celso C. Moro (Physics and Chemistry of Minerals, 2009)

Haplotype and quantitative transcript analyses of Portuguese breast/ovarian cancer families with the BRCA1 R71G founder mutation of Galician origin - Catarina Santos; Ana Peixoto; Patrícia Rocha; Ana Vega; Maria José Soares; Nuno Cerveira; Susana Bizarro; Manuela Pinheiro; Deolinda Pereira; Helena Rodrigues; Fernando Castro; Rui Henrique; et al. (Familial Cancer, 2009)

Synthesis and antimalarial activities of optically active labdane-type diterpenes - José Villamizar; Jean P. Pittelaud; Juan R. Rodrigues; Neira Gamboa; Nieves Canudas; Eleonora Tropper; Franklin Salazar; Juan Fuentes (Natural Product Research, 2009)

Assessment of high-level gentamicin and glycopeptide-resistant Enterococcus faecalis and E. faecium clonal structure in a Portuguese hospital over a 3-year period - R. Mato; F. Almeida; R. Pires; P. Rodrigues; T. Ferreira; I. Santos-Sanches (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Influence of silicon on some components of resistance to anthracnose in susceptible and resistant sorghum lines - Renata S. Resende; Fabricio Á. Rodrigues; Juliana M. Soares; Carlos R. Casela (European Journal of Plant Pathology, 2009)

Soil and litter fauna of cacao agroforestry systems in Bahia, Brazil - M. K. da Silva Moço; E. F. da Gama-Rodrigues; A. C. da Gama-Rodrigues; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2009)

A role for atorvastatin and insulin combination in protecting from liver injury in a model of type 2 diabetes with hyperlipidemia - P. Matafome; E. Nunes; T. Louro; C. Amaral; J. Crisóstomo; L. Rodrigues; A. R. Moedas; P. Monteiro; A. Cipriano; R. Seiça (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Spectrofluorimetric Determination of Second Critical Micellar Concentration of SDS and SDS/Brij 30 Systems - Ana Paula Romani; Antonio Eduardo da Hora Machado; Noboru Hioka; Divinomar Severino; Mauricio S. Baptista; Lúcia Codognoto; Maira R. Rodrigues; Hueder Paulo Moisés de Oliveira (Journal of Fluorescence, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Detection of Polymolecular Associations in Hydrophobized Chitosan Derivatives using Fluorescent Probes - Máira R. Rodrigues; Adriana Lima; Lúcia Codognoto; Antonio Balbin Villaverde; Marcos Tadeu Tavares Pacheco; Hueder P. Moisés de Oliveira (Journal of Fluorescence, 2008)

Effect of additives on the esterification activity of immobilized Candida antarctica lipase - Dasciana S. Rodrigues; George P. Cavalcante; Giovanilton F. Silva; Andrea L. O. Ferreira; Luciana R. B. Gonçalves (World Journal of Microbiology and Biotechnology, 2008)

Benefits of membrane electrodes in the electrochemistry of metalloproteins: mediated catalysis of Paracoccus pantotrophus cytochrome c peroxidase by horse cytochrome c: a case study - P. M. Paes de Sousa; S. R. Pauleta; D. Rodrigues; M. L. Simões Gonçalves; G. W. Pettigrew; I. Moura; J. J. G. Moura; M. M. Correia dos Santos (JBIC Journal of Biological Inorganic Chemistry, 2008)

Effect of the Herbicide Roundup® on Perkinsus olseni in vitro Proliferation and in vivo Survival when Infecting a Permissive Host, the Clam Ruditapes decussatus - L. M. Elandalloussi; R. B. Leite; P. M. Rodrigues; R. Afonso; M. L. Cancela (Bulletin of Environmental Contamination and Toxicology, 2008)

Attempts at a peptide vaccine against paracoccidioidomycosis, adjuvant to chemotherapy - Luiz R. Travassos; Elaine G. Rodrigues; Leo K. Iwai; Carlos P. Taborda (Mycopathologia, 2008)

First report of bristleworm predator of the reef octocoral Carijoa riisei - J. R. B. Souza; H. A. Rodrigues; B. M. Neves; C. D. Perez (Coral Reefs, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Comparative phylogeography of Trypanosoma rangeli and Rhodnius (Hemiptera: Reduviidae) supports a long coexistence of parasite lineages and their sympatric vectors - F. MAIA DA SILVA; A. C. V. JUNQUEIRA; M. CAMPANER; A. C. RODRIGUES; G. CRISANTE; L. E. RAMIREZ; Z. C. E. CABALLERO; F. A. MONTEIRO; J. R. COURA; N. AÑEZ; M. M. G. TEIXEIRA (Molecular Ecology, 2007)
To make reliable interpretations about evolutionary relationships between Trypanosoma rangeli lineages and their insect vectors (triatomine bugs of the genus Rhodnius ) and, thus, about the determinant factors of lineage segregation within T. rangeli , we compared phylogenies of parasite isolates and vector species. Sixty‐one T. rangeli isolates from invertebrate and vertebrate hosts were initially evaluated in terms of polymorphism of the spliced‐leader gene (SL). Further analysis based on SL and SSUrRNA sequences from 33 selected isolates, representative of the overall phylogenetic diversity and geographical range of T. rangeli , supported four phylogenetic lineages within this species. By comparing the phylogeny of Rhodnius species with that inferred for T. rangeli isolates and through analysis of the geographical range of the isolates, we showed that there is a very significant overlap in the distribution of Rhodnius species and T. rangeli lineages. Congruence between phylogeographical analysis of both T. rangeli lineages and complexes of Rhodnius species are consistent with the hypothesis of a long coexistence of parasites and their vectors, with lineage divergence associated with sympatric species of Rhodnius apparently without association with particular vertebrate hosts. Separation of T. rangeli isolates from vectors of distinct complexes living in sympatry favours the absence of gene flow between the lineages and suggests evolution of T. rangeli lineages in independent transmission cycles, probably associated to specific Rhodnius spp. ecotopes. A polymerase chain reaction assay based on SL intergenic sequences was developed for simultaneous identification and lineage genotyping of T. rangeli in epidemiological surveys.

Catalase, Bax and p53 expression in the visual system of the crab Ucides cordatus following exposure to ultraviolet radiation - Nadia Campos de Oliveira Miguel; Inês Júlia R. Wajsenzon; Christina Maeda Takiya; Leonardo Rodrigues de Andrade; Giovane G. Tortelote; Marcelo Einicker-Lamas; Silvana Allodi (Cell and Tissue Research, 2007)

Repeated-Batch Xylitol Bioproduction Using Yeast Cells Entrapped in Polyvinyl Alcohol–Hydrogel - M. A. A. Cunha; R. C. B. Rodrigues; J. C. Santos; A. Converti; S. S. da Silva (Current Microbiology, 2007)

Water tank and numerical model studies of flow over steep smooth two-dimensional hills - J. B. R. Loureiro; D. V. Soares; J. L. A. Fontoura Rodrigues; F. T. Pinho; A. P. Silva Freire (Boundary-Layer Meteorology, 2007)

BRCA1 and BRCA2 germline mutational spectrum and evidence for genetic anticipation in Portuguese breast/ovarian cancer families - Ana Peixoto; Natália Salgueiro; Catarina Santos; Graça Varzim; Patrícia Rocha; Maria José Soares; Deolinda Pereira; Helena Rodrigues; Maria José Bento; António Fráguas; Graça Moura; Fernando Regateiro; et al. (Familial Cancer, 2006)

Acute heat exposure increases high-intensity performance during sprint cycle exercise - Ana Cristina R. Lacerda; Fernando Gripp; Luiz Oswaldo C. Rodrigues; Emerson Silami-Garcia; Cândido C. Coimbra; Luciano S. Prado (European Journal of Applied Physiology, 2006)

Evaluation of the use of salivary lead levels as a surrogate of blood lead or plasma lead levels in lead exposed subjects - Fernando Barbosa; Maria Heloísa Corrêa Rodrigues; Maria R. Buzalaf; Francisco J. Krug; Raquel F. Gerlach; José Eduardo Tanus-Santos (Archives of Toxicology, 2006)

The effects of fructose-1,6-bisphosphate and dexamethasone on acute inflammation and T-cell proliferation - R. Pestana Lopes; A. Lunardelli; T. Preissler; C. E. Leite; J. C. F. Alves-Filho; F. Bordignon Nunes; J. Rodrigues de Oliveira; M. E. Bauer (Inflammation Research, 2006)

In situ probing of Xylella fastidiosa in honeydew of a xylem sap‐feeding insect using 16S rRNA‐targeted fluorescent oligonucleotides - Jorge L. M. Rodrigues; Maria E. Silva‐Stenico; Adriane N. De Souza; João R. S. Lopes; Siu M. Tsai (Environmental Microbiology, 2006)
Summary Xylella fastidiosa is a plant pathogen that threatens a US$ 4.6 billion worldwide wine and citrus industry. Monitoring its presence and distribution in plants and vectors is crucial for designing control strategies, as well as for understanding its ecological role and fate. We developed two fluorescent oligonucleotide probes complementary to different regions of the 16S rRNA gene of X. fastidiosa . The specificity of the newly designed probes S‐S‐X.fas‐0067‐a‐A‐18 and S‐S‐X.fas‐1439‐a‐A‐18 was demonstrated using fluorescence in situ hybridization (FISH) for 12 Xylella isolates, 15 closely related microorganisms and three plant endophytes. These probes were used to detect and quantify X. fastidiosa in plant sap (average value of 2.9 ± 0.3 × 10 6 cells ml −1 ) from three different citrus orchards. In a second experiment, cells were quantified in honeydew (2.2 ± 0.2 × 10 4 cells ml −1 ) collected from the insect vector Bucephalogonia xanthophis during the acquisition access period on an infected plant. The number of pathogen cells retained or digested by the insect is 10 000 times greater than the estimated minimum value to ensure an efficient transmission. Polymerase chain reaction (PCR) amplification using specific primers with plant sap and honeydew samples, followed by sequencing, confirmed the presence of the plant pathogen. This is the first demonstration of FISH being used for environmental samples, such as plant sap and insect honeydew, to estimate the abundance of a plant pathogen during infection.

Modulation of endocytosis in pollen tube growth by phosphoinositides and phospholipids - D. Monteiro; P. Castanho Coelho; C. Rodrigues; L. Camacho; H. Quader; R. Malhó (Protoplasma, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Meiotic instability of chicken ultra-long telomeres and mapping of a 2.8 megabase array to the W-sex chromosome - K. L. Rodrigue; B. P. May; T. R. Famula; M. E. Delany (Chromosome Research, 2005)

Lead Concentrations in Ruffed Grouse, Rock Ptarmigan, and Willow Ptarmiganin Québec - J Rodrigue; R McNicoll; D Leclair; J.-F Duchesne (Archives of Environmental Contamination and Toxicology, 2005)

Anther culture and cold treatment of floral buds increased symmetrical and extra nuclei frequencies in soybean pollen grains - Lia R. Rodrigues; Joo Marcelo S. Oliveira; Jorge E. A. Mariath; Leandro B. Irano; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

GENEHUNTER versus SimWalk2 in the context of an extended kindred and a qualitative trait locus - Sandra Romero-Hidalgo; Eliane R. Rodrigues; Eduardo Gutirrez-Pea; Laura Riba; Mara Teresa Tusi-Luna (Genetica, 2005)

Inorganic chemical composition of native trees of the Atlantic Forest - E. J. França; E. A. De Nadai Fernandes; M. A. Bacchi; R. R. Rodrigues; T. G. Verburg (Environmental Monitoring and Assessment, 2005)

Histology of embryogenic responses in soybean anther culture - Lia R. Rodrigues; Joo Marcelo S. Oliveira; Jorge E.A. Mariath; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Molecular marker-mediated validation of morphologically defined landraces of Pejibaye (Bactris gasipaes) and their phylogenetic relationships - Doriane P. Rodrigues; Spartaco Astolfi Filho; Charles R. Clement (Genetic Resources and Crop Evolution, 2005)

Mitochondrial DNA and RAPD polymorphisms in the haploid mite Brevipalpus phoenicis (Acari: Tenuipalpidae) - J. C. V. Rodrigues; M. Gallo-meagher; R. Ochoa; C. C. Childers; B. J. Adams (Experimental and Applied Acarology, 2004)

Mitochondrial DNA and RAPD polymorphisms in the haploid mite Brevipalpus phoenicis (Acari: Tenuipalpidae) - J.C.V. Rodrigues; M. Gallo-meagher; R. Ochoa; C.C. Childers; B.J. Adams (Experimental and Applied Acarology, 2004)

Origin of Embryo-Like Structures in Soybean Anther Culture Investigated Using SSR Marker - Lia R. Rodrigues; Tatiana de F. Terra; Fernanda Bered; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Numerical Analyses of Soft Bottom Macroinvertebrates to Diagnose the Pollution in Tropical Coastal Waters - Sadanand N. Harkantra; Nimi R. Rodrigues (Environmental Monitoring and Assessment, 2004)

Differential expression of sialylglycoconjugates and sialidase activity in distinct morphological stages of Fonsecaea pedrosoi - Jos N. S. S. Couceiro; Rosangela M. A. Soares; Celuta S. Alviano; Andr L. S. Santos; Marcio L. Rodrigues; Daniela S. Alviano; Catia A. Almeida; Luiz R. Travassos (Archives of Microbiology, 2004)

Resistance to common bacterial blight in Phaseolus vulgaris L. recombinant inbred lines under natural infection of Xanthomonas axonopodis pv. phaseoli - C. Fortes Ferreira; M. Gonzaga Pereira; A. da Silva dos Santos; R. Rodrigues; R.E. Bressan-Smith; A. PioViana; R. Figueiredo Daher (Euphytica, 2003)

Severe Disseminated Tuberculosis After Intravesical Instillation of Bacillus Calmette-Gurin - R. Proena; M. Toscano Rico; O. Cardoso; C. Salvado; P. Rodrigues; J. Machado (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Citrus Leprosis and its Status in Florida and Texas: Past and Present - C.C. Childers; J.C.V. Rodrigues; K.S. Derrick; D.S. Achor; J.V. French; W.C. Welbourn; R. Ochoa; E.W. Kitajima (Experimental and Applied Acarology, 2003)

Chromosomal studies in Callicebus donacophilus pallescens, with classic and molecular cytogenetic approaches: Multicolour FISH using human and Saguinus oedipus painting probes - R. M. S. Barros; C. Y. Nagamachi; J. C. Pieczarka; L. R. R. Rodrigues; M. Neusser; E. H. de Oliveira; J. Wienberg; J. A. P. C. Muniz; J. D. Rissino; S. Muller (Chromosome Research, 2003)

The interhepatocytic macrophages and pale‐grey cells in brown trout liver ontogenesis - A. D. Resende; E. Rocha; R. A. F. Monteiro; P. Rodrigues (Journal of Fish Biology, 2002)
Pale‐grey cells appeared in the livers of healthy and non‐stressed brown trout Salmo trutta 3 weeks post‐hatching whereas interhepatocytic macrophages appeared at 5 months. Cells with intermediate morphological characteristics between those of pale‐grey cells and macrophages were identified in all ages studies. Cell ultrastructure supported the idea that pale‐grey cells probably belonged to the macrophage lineage, being eventual precursors of the active phagocytes residing amongst hepatocytes.

Sialylglycoconjugates and sialyltransferase activity in the fungus Cryptococcus neoformans - Marcio L. Rodrigues; Andrey S. S. Dobroff; José Nelson dos S. S. Couceiro; Celuta S. Alviano; Roland Schauer; Luiz R. Travassos (Glycoconjugate Journal, 2002)

Plant-soil interactions in multistrata agroforestry in the humid tropicsa - G. Schroth; J. Lehmann; M. R. L. Rodrigues; E. Barros; J. L. V. Macêdo (Agroforestry Systems, 2001)

Pharmacological demonstration of the differential involvement of protein kinase C isoforms in short- and long-term memory formation and retrieval of one-trial avoidance in rats - Monica R. M. Vianna; Daniela M. Barros; Tiago Silva; Humberto Choi; Cristina Madche; Cleverson Rodrigues; Jorge H. Medina; I. Izquierdo (Psychopharmacology, 2000)

Varying responses of herbivorous and invertebrate-feeding fishes to macroalgal reduction on a coral reef - T. R. McClanahan; V. Hendrick; M. J. Rodrigues; N. V. C. Polunin (Coral Reefs, 1999)

Identification of two novel mutations in OCTN2 of three patients with systemic carnitine deficiency - F.M. Vaz; H.R. Scholte; J. Ruiter; L.M. Hussaarts-Odijk; R. Rodrigues Pereira; S. Schweitzer; J.B.C. de Klerk; H.R. Waterham; R.J.A. Wanders (Human Genetics, 1999)

Identification of two novel mutations in OCTN2 of three patients with systemic carnitine deficiency - F.M. Vaz; H.R. Scholte; J. Ruiter; L.M. Hussaarts-Odijk; R. Rodrigues Pereira; S. Schweitzer; J.B.C. de Klerk; H.R. Waterham; R.J.A. Wanders (Human Genetics, 1999)

Unexpected richness of reef corals near the southern Amazon River mouth - R. Leão de Moura; M.C. Martins Rodrigues; R.B. Francini-Filho; I. Sazima (Coral Reefs, 1999)

Two new species of the genus Sporobolomyces and a new Rhodotorula species from leaf surfaces - R. G. Shivas; L. Rodrigues de Miranda (Antonie van Leeuwenhoek, 1983)

Cryptococcus phylloplanus and Cryptococcus hinnuleus, two new yeast species - R. G. Shivas; L. Rodrigues de Miranda (Antonie van Leeuwenhoek, 1983)

Pichia sorbitophila sp nov. - L. Rodrigues de Miranda; K. R. Appel; H. Seyfarth (Antonie van Leeuwenhoek, 1980)

Pichia humboldtii sp. nov., the perfect state of Candida ingens - L. Rodrigues de Miranda; T. Trk (Antonie van Leeuwenhoek, 1976)